Transcriptome and metabolome analyses reveal the effects of 2,4-epibrassinolide (EBR) on the postharvest softening of ‘Wushancuili’ plum (Prunus salicina Lindl.) - Zhuoheng Chi; Xue Li; Qian Zhao; Yuanping Chen; Zheng Wu (Postharvest Biology and Technology, 2027)

Dietary selenium nanoparticles alleviate heat stress-induced reproductive impairment in Onychostoma macrolepis, with MeSeCys as a key bioactive selenium species - Chao Zhu; Weiping Pan; Jianbo Zheng; Shili Liu; Meili Chi; Wenping Jiang; Shun Cheng; Junzhi Luo; Wuzi Dong; Zhilong Chen; Fei Li (Theriogenology, 2026)

A near-infrared fluorescent probe for point-of-care screening of male infertility in seminal plasma - Mengyongwei Li; Shijun Chen; Qiye Liu; Cailing Fan; Yanlin Ma; Wei Shu; Weijie Chi; Chaoyuan Zeng (Analytica Chimica Acta, 2026)

Calcium isotopes constrain magmatic–hydrothermal evolution and Nb–REE decoupling in the Bayan Obo carbonatite system - Zhuoming Li; Qingyan Tang; Chi Zhao; Hailong Jin; Shang Liu; Jiaolong Zhao; Biao Chen; Yanjiang Liu; Yan Zhang; Tianyu Qin; Min Qiao; Xinrui Bai; et al. (Gondwana Research, 2026)

High-speed air circulation preserves curcumin bioactivity and enables pH-dependent intestinal release in oyster-based functional foods for IBD dietary intervention - Shuang Gao; Xue Jiang; Yi Rong; Huanhuan Chi; Ci Song; Shujia Wang; Ying Li; Jingjing Chen; Lida Yang; Huawei Ma (Food Research International, 2026)

Physical confinement dominates the stabilization of maya blue-type pigments: Experimental and computational insights from a thioindigo analogue - Guanzheng Zhuang; Xiaofang Li; Chi Zhang; Meiyi Li; Bin Xiao; Meiqing Chen; Weirui Chen; Maguy Jaber; Francisco Rodrigues (Applied Clay Science, 2026)

Hypoxia-enhanced PbDREB1A alleviates superficial scald in pear fruit by suppressing ethylene biosynthesis - Yanmin Du; Chen Li; Junpeng Niu; Qian Yu; Chi Qin; Yihan Wang; Wenhui Wang; Shaoling Zhang (Postharvest Biology and Technology, 2026)

Construction of a heterojunction based on polyphthalocyanine and defective ZnIn2S4 for enhanced CO₂ photoreduction performance - Yuxuan Liu; Yuning Liang; Weimeng Chi; Shuohui Li; Yanhua Gao; Ying Chen (Journal of Environmental Chemical Engineering, 2026)

Characterization of coconut oil from cold plasma-treated coconut flakes and protein-dependent whipping behavior in plant-based cream systems - Enxi Fu; Junxia Jiang; Yang Chen; Pengyin Li; Huibei Sun; Zihan Zhang; Ruihao Chi; Dongyu Hu; Changyi Chen; Yuqi Wang; Tian Li; Weimin Zhang (Food Research International, 2026)

Lead-induced apoptosis in Sertoli cells is associated with Ca2+ dysregulation - Chi Zhang; Yunting Li; Yangle Zhang; Hanming Qiao; Shaoguan Lu; Chen Zhang; Ziqiong Wang; Haitao Ma (Food and Chemical Toxicology, 2026)

Full-scale experimental and numerical study on hydrogen explosion and RC wall response: Confinement effect - Di Chen; Jun Li; Kaiyi Chi; Pengtao Wu; Jian Liu; Shenchun Xu; Zhenhuan Xu; Li Chen; Chengqing Wu (Engineering Structures, 2026)

Turning waste into wealth: Enhanced recovery of rare earth elements using agricultural waste-derived biolixiviants - Ni He; Chi Zhang; Yu Zhao; Kui Zou; Zhu Chen; Xiaoyu Meng; Li Shen; Hongbo Zhao (Chemical Engineering Journal, 2026)

Acoustic cavitation-adaptively amplified ZIF nanocomplexes for synergistic immunotherapy of colorectal cancer - Xiaoling Xu; Xiaokai Chi; Weijing Li; Jiaren Zhang; Jianwen Fang; Jingqi Sun; Shuyuan Tian; Hong Yu; Wei Chen (Chemical Engineering Journal, 2026)

Scalable cancer cell-derived liposome capable of homologous tumor-homing to encapsulate near-infrared light-responsive drug delivery nanocomposites for enhanced combination therapy - Fang-Yi Hsu; Wen-Jyun Wang; Li-Ting Yang; Yi-Zi Chen; Ting-Chi Lo; Jia-Sin Chen; Wei-Lun Huang; Yen-Liang Li; Hidenobu Takahashi; Wen-Chun Hung; Chi-Wen Luo; Shu-Yi Lin; et al. (Chemical Engineering Journal, 2026)

Multifunctional microneedle patches with sequential drug release for antimicrobial and regenerative treatment of infectious keratitis - Xiaojun Hu; Rui Liu; Qin Chen; Yunzhe Wang; Chi Zhang; Chang Liu; Yiwen Fan; Bin Kong; Xingtao Zhou; Meiyan Li (Chemical Engineering Journal, 2026)

Rational linker engineering enables near-infrared visualization of cysteine fluctuations in vivo - Shuangying Su; Xianzhe Yu; Qiye Liu; Shijun Chen; Qinlin Yuan; Binjie Zhang; Tianchu Li; Cailing Fan; Weijie Chi; Chaoyuan Zeng (Analytica Chimica Acta, 2026)

Multiplexed EDL-FET biosensor with tannic acid stabilization for simultaneous p-Tau217 and Aβ42/Aβ40 detection in plasma and whole blood from stroke patients - Shang-Chi Chien; I-Yin Chang; Yong-Chuan Chen; Yi-Zhen Lai; Yu-Fang Chen; Pei-Lun Sun; Bor-Ran Li; Yu-Lin Wang; Jung-Chih Chen (Analytica Chimica Acta, 2026)

Dual-ionic strategy modulates fibroblast fate for dynamically preventing ventricular aneurysm in mice - Yuxuan Pan; Jianfeng Zhong; Xiliang Mo; Chi Zhang; Shanghai Li; Xu Shi; Xiaodong Ning; Xueting Liu; Xueqin Shi; Jiaqi He; Yanan Jia; Bin Yu; et al. (Chemical Engineering Journal, 2026)

Functional characterization of the Cbr1 gene in regulating alkaline tolerance in grass carp - Jianbo Zheng; Yi Xu; Qi Chen; Fei Li; Shili Liu; Chao Zhu; Shun Cheng; Wenping Jiang; Meili Chi; Junzhi Luo; Caiyan Li; Xiaohui Xu; et al. (Aquaculture, 2026)

Visible-light photocatalytic degradation of polychlorinated biphenyls (PCBs) in water over alkyl-chain-functionalized hydrophobic g-C3N4: Performance and mechanism - Dejun Zhang; Yifei Gao; Jingyi Xu; Ying Zhou; Jundong Li; Yun Weng; Jie Chen; Huajie Huang; Xinyan Xiong; Hainan Wu; Wei Xiong; Chi Zhang (Journal of Hazardous Materials, 2026)

Integrated geophysical insights into the structural controls on geothermal systems in the Tatun Volcano group, northern Taiwan - T. Lan-Chi Nguyen; Wen-Jeng Huang; Chien-Chih Chen; Chi-Shu Yen; Yi-Heng Li; Horng-Yuan Yen (Geothermics, 2026)

Physicochemical and structural characterization of self-assembled nanoparticles from whey protein isolate–dextran Maillard conjugates and binding mechanism with capsaicin - Chen Huang; Xinjing Li; Guzalnur Askar; Heping Cui; Jingyang Yu; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Chemistry, 2026)

Solvent-toughened ultra-stretchable poly(ionic liquid) gels for multifunctional wearable bioelectronics - Yongkang Bai; Xiaoli Liang; Didi Wen; Zhoujing Chen; Chi Zhang; Zhun Hu; Wei Fan; Yuqi Li (Chemical Engineering Journal, 2026)

Plasma-engineered chitosan couples red-light bioenergetics to diabetic wound regeneration through programmable microenvironments - Lekshmi Rethi; Hoa Duc Chau; Erlina Febriani; Yan-Ting Chen; Szu-Yu Tung; Pei-Ru Jheng; Yu-Wen Tseng; Rou Li; Min-Lang Tsai; Chun-Chi Chang; Van Khiet Pham; Hieu Trung Nguyen; et al. (Carbohydrate Polymers, 2026)

Impact of intraguild predation between Neoseiulus barkeri and Lasioseius scapulatus on thrips control in cowpea - Yuanming Chi; Chen Yu; Yilin Zhu; Kai Shu; Ying Gong; Huiyin Yang; Ning Nong; Zihan Zhao; Mingyue Feng; Maoqing Li; Yanyu Chen; Xinzheng Huang; et al. (Journal of Pest Science, 2026)

Contrasting mineral–microbial pathways drive phosphorus bioavailability under moderate pH shifts in agricultural soils - Meng Qi; Rongyang Cui; Anqiang Chen; Xinmei Zhao; Ming Ni; Zhiwu Li; Hui Yan; Chi Wang; Bin Fu (Applied Soil Ecology, 2026)

Assessing the Potential of a Formalin‐Killed Cells (FKC) Vaccine Against Edwardsiella anguillarum in Milkfish ( Chanos chanos ) - Atiek Rahmawaty; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2026)
Edwardsiella anguillarum causes Edwardsiellosis in fish, resulting in severe internal organ lesions and substantial economic losses in aquaculture. The limited efficacy of antibiotics in treating this disease, coupled with concerns regarding resistance and side effects, has driven interest in exploring fish vaccines. Various vaccine candidates derived from E. anguillarum, including inactivated cells and protein subunits, have shown potential. Here, we developed a vaccine against E. anguillarum in milkfish, and its efficacy was evaluated through vaccination challenge trials using milkfish as the target species. The formalin‐killed vaccine (FKC) in combination with an adjuvant exhibited superior efficacy, achieving a relative percent survival (RPS) of 83.4%. Furthermore, the agglutination titers indicated a robust immune response in the FKC + Adjuvant group, suggesting a potent and sustained antibody response. Additionally, serum lysozyme activity was significantly higher in vaccinated fish than in controls. Immune‐related gene expression analysis in spleen and head kidney revealed that IL‐1β peaked at 14 days post‐vaccination, indicating early pro‐inflammatory response, while MHC‐II showed progressive elevation, suggesting sustained antigen presentation and humoral immunity. Overall, this study underscores the effectiveness of the FKC + Adjuvant combination in enhancing immune response and protecting against bacterial pathogens in aquaculture, presenting a promising strategy for disease control.

Genetic selection response and genomic basis of resistance to Cryptocaryon irritans in large yellow croaker (Larimichthys crocea) - Yin Li; Ji Zhao; Jiaying Wang; Qiaozhen Ke; Hongshu Chi; Sijing Chen; Yujia Chen; Huasong Weng; Fei Pu; Ning Li; José M. Yáñez; Tao Zhou; et al. (Marine Life Science & Technology, 2026)

A mechanism investigation on the effective strategy for alleviating acute myocardial infarction associated with sleep deprivation - Haiyang Chen; Lijun Zhang; Meiyan Liu; Yanwei Li; Dajian Wei; Jingjing Wei; Xiaofeng Li; Dongfang He; Yunpeng Chi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Vegetation-driven shifts in soil bacterial community structure: insights from karst rocky desertification mitigation in southwestern China - Shiyao Wu; Shuzhen Song; Xingyan Chen; Qiang Wu; Shengnan Li; Xueling Wang; Yuehua Song; Yongkuan Chi (Plant and Soil, 2026)

Multivariate seismic intensity measures and vulnerability assessment framework for multistory masonry structures under near-field and far-field earthquake sequences - Si-Qi Li; Peng-Chi Chen (Bulletin of Earthquake Engineering, 2026)

DEM-PBM Simulation of Sandstone Fragmentation Under Blasting - Zhongwei Chen; Xudong Li; Guowen Xu; Jiong Gao; Chi Zhang; Zhuolin Wu (Rock Mechanics and Rock Engineering, 2026)

Seismic fragility models of highway reinforced concrete bridges between cities considering the effects of aging and time-varying degradation - Si-Qi Li; Lin-Lin Zheng; Peng-Chi Chen; Can Zhang (Bulletin of Earthquake Engineering, 2026)

Photoactive and self-sustaining: How soil organic matter drives the natural remediation of Cr(VI) via photochemical pathways at the soil-water interface - Yaoning Chen; Mengwei Luo; Yuanping Li; Jun Wang; Hongjuan Jiang; Mengyang Zhao; Yaoqin Nie; Bin Zou; Qianruyu Wang; Nianping Chi (Water Research, 2026)

Efficient modeling of blast loading and structural response in hydrogen-air detonations - Di Chen; Jun Li; Ruizhe Shao; Kaiyi Chi; Chengqing Wu (Process Safety and Environmental Protection, 2026)

Optimization of the backfilling ratio for pressure relief and gangue disposal in protective-seam mining - Yunbo Wang; Meng Li; Jixiong Zhang; Chi Chen; Daoxiong Zhang; Zhangyu Li; Zhibo Cui (Process Safety and Environmental Protection, 2026)

Influence of roughness on overtopping flow at a dike using deep learning-based video measurement techniques - Weiqiu Chen; Xinrui Sun; Chi Zhang; Yi Xu; Shanhang Chi; Titi Sui; Yuan Li; Fei He; Jinhai Zheng (Ocean Engineering, 2026)

USV anti-submarine patrol path planning based on an improved PPO algorithm - Wenjing Li; Yu Shi; Qingjia Chi; Tianqi Yang; Hu Chen; Xiaonan Zhang (Ocean Engineering, 2026)

Corrigendum to ‘Wavelength-dependent photobiomodulation attenuates synovial inflammation in fibroblast-like synoviocytes and a collagenase-induced osteoarthritis model’ [Journal of Photochemistry & Photobiology B: Biology Volume 272 (2025) 113276] - Tianxiang Fan; Peng Xia; Safayet Ahmed; Yuen H. Tsang; Zhi Yao; Deli Wang; Ziyu Chen; Lixiang Xue; Dongquan Shi; Bo Wang; Chi Fai Cheung; Marco Y.C. Pang; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Outdoor artificial light at night exposure and risk of myopia: A cross-sectional and prospective cohort study among Hong Kong children - Yingan Li; Yuzhou Zhang; Ka Wai Kam; Yuhan Cui; Poemen Chan; Patrick Ip; Wei Zhang; Alvin Young; Chi Pui Pang; Clement C. Tham; Li Jia Chen; Mei Po Kwan; et al. (Environmental Research, 2026)

Dual mechanical-solar driven PVDF/g-C3N4-CN fibrous membranes for efficient piezo-photocatalytic uranium extraction - Shuang Xie; Lu Wang; Zekai Li; Lina Lv; Xiaoyu Li; Baihua Chen; Tingting Deng; He Chen; Zhixuan Wang; Chao Jiang; Yutao Zhuang; Junwu Wei; et al. (Desalination, 2026)

A 3D Ubiquitous Multiple Joint Model for stability analysis in large underground caverns within jointed rock masses - Bo Ni; Qin Chen; An-chi Shi; Jia-wen Zhou; Hai-bo Li (Computers and Geotechnics, 2026)

Lycii Fructus-derived extracellular vesicles-like particles attenuate sodium iodate-induced retinal injury by transporting bioactive cargo molecules - Pan Huang; Xiao-Bo Zhang; Jia-Qi Li; Guan-Wen He; Ying Chen; Ling-Yun Yang; Zai-Long Chi (Chemical Engineering Journal, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

A study on vegetation specular reflection removal method based on fusion of Mueller matrix polarization parameters and spectral information - Guofeng Zhang; Siyuan Li; Wei Chen; Youguang Zhao; Chi Wang (Computers and Electronics in Agriculture, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Withanolides from Datura stramonium: two unprecedented B-ring-seco derivatives and anti-inflammatory active analogues - Juan Pan; Gang-Tao Bu; Si-Yi Wang; Jia-Tong Wu; Meng-Meng Li; Wei Guan; Qing-Shan Chen; Li-Li Zhang; Xiao-Chi Ma; Hai-Xue Kuang; Yan Liu (Phytochemistry, 2026)

Crack propagation and coalescence of ice with flaws under SHPB impact loading: Experimental investigation and peridynamic simulation - Chen Chi; Yiheng Zhang; Ying Tang; Xiaobin Li; Wei Chen; Qing Wang; Duanfeng Han; Yinggang Li (Ocean Engineering, 2026)

Rice-crab co-culture mitigates reactive gaseous N losses and increases economic benefits - Feng Zhang; Guimin Xia; Yuanze Qiu; Hongwei Han; Haixia Liu; Benji Yi; Bohao Li; Daocai Chi; Taotao Chen (Field Crops Research, 2026)

Engineering over-oxidized cu on CNTs for sensitive non-enzymatic glucose sensing and energy applications - Songxin Zhong; Rida Li; Hui Chen; Chao Xiao; Yining Lan; Qi-an Chen; Jian Li; Changqiang Feng; Shizhan Li; Hengchan Qi; Chi Gong; Zukun He; et al. (Chemical Engineering Journal, 2026)

Comprehensive phylogenomic analyses of ciliated protists with a revised classification of the phylum Ciliophora (Eukaryota, Alveolata) - Yurui Wang; Ying Yan; Zhenzhen Yi; Yan Zhao; Qianqian Zhang; Yong Chi; Tengyue Zhang; Weiwei Liu; Mingjian Liu; Borong Lu; Mingzhen Ma; Wenbao Zhuang; et al. (Science China Life Sciences, 2026)

A Modified Coupled Peridynamics Least Squares Minimization and Finite Element Method for Mixed-Mode Crack Propagation in Rock - Pengyu Mu; Xiangshang Li; Jiamin Wang; Shouguang Wang; Chi Liu; Huaguang Liu; Chunyuan Li; Yulong Chen (Rock Mechanics and Rock Engineering, 2026)

Suicide attempt risk among patients receiving methylphenidate: a retrospective cohort study - Tai-Long Pan; Li-Chi Chen; Ju-Wei Hsu; Ya-Mei Bai; Shih-Jen Tsai; Tzeng-Ji Chen; Mu-Hong Chen (Psychopharmacology, 2026)
Background Methylphenidate may reduce suicide risk among patients with attention-deficit hyperactivity disorder. Several studies have noted that the association between methylphenidate use and suicidality is weakening. Methods Data were collected from Taiwan’s National Health Insurance Research Database to assess the association between methylphenidate exposure and suicide attempt risk across two exposure periods (main analysis: 2001–2002; duplication analysis: 2004–2005). We compared suicide attempt risk between patients who initiated methylphenidate treatment and those with no recorded psychiatric treatment or methylphenidate exposure during the same period. Results In both the main and duplication analyses, patients receiving methylphenidate exhibited a higher subsequent risk of suicide attempts than unexposed individuals. A duration–response pattern was observed in both cohorts: the hazard ratio of suicide attempts declined with longer cumulative methylphenidate use, from 1.60/1.84 for < 30 days to 1.45/1.65 for ≥ 180 days. Because hazard ratios were closely aligned across 2001–2002 and 2004–2005, the association of methylphenidate with reduced suicide attempt risk did not appear to decrease over time. Discussion Longer use of methylphenidate was associated with a lower risk of subsequent suicide attempts among patients in Taiwan receiving methylphenidate. The beneficial effect of methylphenidate on suicide risk remained consistent over time.

Extracting cropping patterns from remotely sensed images in a mixed single-, double-, and triple-cropping region of Southern China - Yifan Li; Chen Cheng; Xiaoming Shi; Hong Chi; Yifei Han; Fei Zhao; Jinliang Huang; Feng Ling (Environmental Monitoring and Assessment, 2026)

Food-microbiota interactions in the oral cavity: A comprehensive review of how food compositions affect oral microbiota homeostasis and oral health - Siyu Chen; Xiaohan Zhang; Yuan Liu; Ran Wang; Tongtong Chen; He Li; Xinqi Liu; Chi Zhang (Trends in Food Science & Technology, 2026)

Mixed exposure to brominated flame retardants adversely affects vaccine-induced antibody titers: Risk prioritization and benchmark dose modeling - Zihui Zhao; Chi Zhang; Xueyu Chen; Yongheng Yan; He Jiao; Xianhao Wang; Ruxu Yan; Yiqian Wang; Meng Liu; Xianfeng Yue; Yuqian Sui; Xia Li; et al. (Toxicology Letters, 2026)

Decoding tetrachlorantraniliprole fate in agricultural soils: Mechanistic insight into major imide-type metabolites and their enhanced aquatic risk - Leyuan Ji; Yingge Wang; Xiaopeng Li; Feng Chen; Chi Wu; Zhou Lu; Yanli Man; Liangang Mao; Lizhen Zhu; Lan Zhang; Xingang Liu (Journal of Hazardous Materials, 2026)

Coupling virtual and physical water optimization: a bi-level stochastic model for basin water scarcity mitigation - Wei Li; Hao Yang; Mingshuai Chen; Jiajun Cui; Junlong Zhang; Chi Han; Li You; Yongping Li; Guohe Huang (Journal of Cleaner Production, 2026)

First mapping of subsurface soil temperature profiles by integrating diurnal cycles of microwave and thermal infrared observations - Dabiao Chen; Huazhu Xue; Tianjie Zhao; Yuyang Xiong; Ning Li; Jingyao Zheng; Yipeng Cao; Yu Bai; Songbo Qu; Ling Yao; Tang Liu; Chi Wang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Effects of fermentation with feruloyl esterase-producing Lactobacillus johnsonii on the composition, structure, physicochemical properties, and in vitro hypoglycemic activity of soluble dietary fiber from rice bran - Xiangfei Li; Menghan Wang; Jie Liu; Fei Gao; Xinyi Pang; Jing Sun; Chi Chen; Yingjian Lu (Food Chemistry, 2026)

Dietary lipid levels modulate enrofloxacin-induced antibiotic resistance and metabolic dysfunction in Pacific white shrimp (Litopenaeus vannamei): assessing the dietary risk and metabolic impact in edible tissues - Jiahao Song; Yucheng Liu; Yifei Pan; Kangyuan Qu; Bin Huang; Xianjie Chen; Yuxuan Ma; Youxi Li; Jiajie Chen; Shuyan Chi; Beiping Tan; Shiwei Xie (Food Chemistry, 2026)

Genomic insights and vaccine evaluation of a virulent MLST ST234 Bacillus cereus infecting Asian sea bass (Lates calcarifer) - Li-Wu Cheng; Qiong-Yi Huang; Nopadon Pirarat; Abisheik Rajandran; Sayuj Poudyal; Pei-Chi Wang; Shih-Chu Chen (Fish & Shellfish Immunology, 2026)

In situ preparation of heterometallic polyphthalocyanine/ZnIn2S4 heterojunction for efficient photocatalytic CO2 reduction - Yuxuan Liu; Yuning Liang; Weimeng Chi; Shuohui Li; Yanhua Gao; Ying Chen (Environmental Research, 2026)

Molnupiravir: A Prodrug of the Ribonucleoside β‐D‐N4‐Hydroxycytidine Triphosphate Inhibits the Propagation of Nervous Necrosis Virus in Grouper Brain Cells - Chen‐Kung Chi; Vertika Bajpai; Chen‐Hung Li; Hsin‐Yi Tsai; Chien‐Wen Chen; Chao‐An Cheng; Hsia‐Wei Liu; Chi‐Yao Chang (Journal of Fish Diseases, 2026)
Nervous necrosis virus (NNV) is the causative agent of viral nervous necrosis, otherwise known as viral encephalopathy and retinopathy in larval and juvenile marine fish worldwide. The pandemic outbreaks have caused nearly 100% mortality in hatcheries, leading to significant economic losses in the aquaculture industry. Since NNV attacks the insufficient immune competence fish at early developmental stages, there is an urgent need for effective antiviral drugs. Several nucleoside analogues, including Molnupiravir, have been developed to target viral RNA‐dependent RNA polymerase (RdRp). This study examines the antiviral activity of Molnupiravir against NNV isolated from giant grouper (GG), Epinephelus lanceolatus (Bloch), using grouper brain (GB) cells as an infection model. The inhibition concentration for 50% of maximal effect (EC 50 ) of Molnupiravir on GGNNV propagation in GB cells was determined as 1.87 μM. Surprisingly, the titre of GGNNV reduced 50,000 at 100 μM of Molnupiravir treatment at 4‐day post‐infection, whereas treatment with 200 μM of Molnupiravir resulted in a 10 5 reduction in viral titre. The inhibition of viral replication and translation was further examined using RNA‐fluorescence in situ hybridization (FISH) and immunocytochemistry detection, respectively. Moreover, administration of 100 μM Molnupiravir at early time 0 hpi resulted in a dramatic decrease in viral load, reducing cell‐associated virus by approximately 4000‐fold and released virus by 6000‐fold. Finally, the molecular docking simulation model supports the interaction between NHC‐TP and GGNNV RdRp for the successful therapeutics. These results demonstrated that Molnupiravir is a very effective therapeutic drug for controlling viral nervous necrosis caused by NNV infection.

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

A scalable consensus docking decision-support pipeline for aquaculture bridging foodomics and affordability - Chen-Hsun Liu; Chiu-Hui Kuo; William Chih-Wei Chang; Chih-Hsuan Fan; Bonien Chen; Li-Lian Liu; Fen-Chen Wu; Pao-Chi Liao; Kuohsun Chiu (Computers and Electronics in Agriculture, 2026)

Integrated in-situ electrochemical-membrane process for ammonia valorization and sustainable water reuse - Paula Jungwon Choi; Xinning Zhang; Wing Chi Au; Adel Tayara; Noman Khalid Khanzada; Yingying Xiang; Li Ling; Di Wu; Am Jang; Ho Kyong Shon; Chii Shang; Guanghao Chen; et al. (Water Research, 2026)

Integrating phosphorus sustainability and environmental burden mitigation through systemwide-optimized strategy in China's Yangtze River Economic Belt - Zhiwen Li; Wei Liu; Wenhao Zhang; Xiuyu Liang; Tian Qin; Zhiqin Chen; Zugen Liu; Huoqing Xiao; Yanqi Liu; Wuhu Guo; Evgeny Abakumov; Xuejun Liu; et al. (Journal of Cleaner Production, 2026)

A distinct zearalenone detoxification strategy mediated by cytochrome P450 - Ziwei Liu; Rouming Peng; Qian Li; Chun-Chi Chen; Lilan Xin; Kangkang Li; Jian-Wen Huang; Xin Liu; Xiaodong Zhang; Linzhen Hu; Shangwen Luo; Haibing Zhou; et al. (Food Chemistry, 2026)

A core-shell fiber membrane with synergistic radiative cooling and thermal buffering for all-weather personal comfort - Xiaohong Wu; Akbar Bashir; Chak-Yin Tang; Gary Chi-Pong Tsui; Ziqi Li; Nanhao Chen; Yichi Zhang; Yan Chen; Jie Cui; Juncheng Zhuang; Chen Liu; Yuanyuan Li; et al. (Chemical Engineering Journal, 2026)

Experimental investigation on profile evolution of beach-dune system exposed to irregular waves - Yuan Li; Chi Zhang; Yanyu He; Weiqiu Chen; Jianhui Liu; Titi Sui; Shanhang Chi; Jinhai Zheng (Coastal Engineering, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Notes on the life cycle of a new marine ciliate, Metafolliculina songi n. sp. (Protozoa, Ciliophora, Heterotrichea), with description of its infraciliature and phylogeny - Tingting Ye; Mingzhen Ma; Jemin Park; Mann Kyoon Shin; Yaohan Jiang; Wen Song; Lifang Li; Yong Chi; Xiangrui Chen (Marine Life Science & Technology, 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Machine learning revealed geochemical drivers of cadmium availability and methane emissions in hydrologically fluctuating paddy soils - Qiuyue Chen; Mengmeng Yin; Chengjie Hong; Bowen Fan; Jialin Chi; Zongqiang Zhu; Kai Liu; Xiaoxia Zhou; Liping Fang; Fangbai Li (Journal of Hazardous Materials, 2026)

Establishing tracer gas dilution as a potential reference method for in-stack CO2 emission metrology - Yayong Liu; Zhe Bi; Xiaoping Song; Chi Tu; Keyu Chen; Shao-Meng Li (Journal of Cleaner Production, 2026)

Strengthening operational stability of decentralized rural sewage bio-trickling filters under fluctuating influent loads by activating microbial oxidative stress in oligotrophic regions - Yulei Chi; Dianbao Li; Zhiting Chen; Xuan Shi; Pengkang Jin; Wuang Ren (Journal of Environmental Management, 2026)

Corrigendum to “Fragmentation characteristics and energy components of cylindrical rock specimens in a novel collision system” [Int J Rock Mech Min Sci 191 (2025) 106114] - Zong-Xian Zhang; Li Yuan Chi; Zida Liu; Toochukwu Ozoji; Chen Huang; Wuxing Wu; Nikhil Bakkamuntala (International Journal of Rock Mechanics and Mining Sciences, 2026)

Biodegradable bacterial cellulose hesperetin nanoparticle composite films for food packaging with antibacterial, antioxidant, and UV-blocking properties - Tao Chen; Yangjing Li; Xuesong Chi; Xinru Tang; Lihang Chen; Di Wu; Jiangning Hu (Food Chemistry, 2026)

Thermal runaway behaviour induced by localised aluminium-water reaction at low temperature - Hai-Fang Mao; Jia-Wei Fang; Yi-Kang Deng; Jun Zhang; Yan-Li Zhao; Yao Feng; Min Xiong; Hui-Ting Gu; Xiao Feng; Jian-Hao Fang; Jian-Hua Chen; Chi-Min Shu; et al. (Chemical Engineering Journal, 2026)

Sugarcane Phenotypic Parameters Modeling Using Unmanned Aerial Vehicle Multispectral Data - Yanli Chen; Lu Huang; Mingzhi Li; Ming Sun; Meihua Ding; Lining Huang; Ruisheng Ma; Chi Liang; Xin Yang; Cheng Chen (Sugar Tech, 2026)

Multi-omics analyses of the Alviniconcha holobiont reveal multi-faceted adaptations to deep-sea hydrothermal vents - Hui Wang; Yuran Dai; Chong Chen; Xing He; Menggong Li; Yadong Zhou; Jack Chi-Ho Ip; Jin Sun (Science China Life Sciences, 2026)

Tracing fluid evolution forming multistage wolframite mineralization in vein-type tungsten (-tin) deposit: new insight from LA-ICP-MS analysis of fluid inclusion - Zhi-Lin Cheng; Jun-Yi Pan; Pei Ni; Li-Li Chen; Jian-Ming Cui; Zhe Chi; Jun-Ying Ding (Mineralium Deposita, 2026)

Integrated analysis of PM2.5 chemical characteristics and multi-pollutant health risks in Central Taiwan: Implications for optimizing the air quality health index (AQHI) during the COVID-19 pandemic - Po Jui Chen; Tuan Hung Ngo; Shahzada Amani Room; Yuan Cheng Hsu; Yan Cing Li; Shih Yu Pan; Ta Chih Hsiao; Yu-Cheng Chen; Kai Hsien Chi (Science of The Total Environment, 2026)

Multi-satellite derived data reveals spatiotemporal dynamics of carbon-water coupling and its drivers in tropical ecosystems - Xiang Wang; Zheng Fu; Philippe Ciais; Josep Peñuelas; Jingfeng Xiao; Xing Li; Xiangzhong Luo; Chi Chen; Haoyu Xia; Tao Zhou; Paul C. Stoy; Julia K. Green; et al. (Remote Sensing of Environment, 2026)

Sustainable postharvest management practices for kiwifruit: Principles, approaches, and future directions - Qinhong Liao; Xiaojiao Li; Shixian Zeng; Wenxuan Chen; Ping Huang; Zihao Wang; Chi Yan; Qiqiang Wu; Qiuhong Niu; Yong Wang; Zhenshuo Wang (Postharvest Biology and Technology, 2026)

A treasure waiting to be discovered: the potential of tourmaline's spontaneously polarized electric field for environmental applications - Mengyang Zhao; Yihuan Liu; Yaoning Chen; Yuanping Li; Huayue Kang; Longbo Jiang; Chen Zhao; Bin Zou; Nianping Chi; Jingxia Huang; Tianyun Zhou (Journal of Environmental Management, 2026)

Aroma formation in peptide-involved Maillard reaction: mechanistic insights, key factors, and control strategies - Tong Zhou; Heping Cui; Xinjing Li; Chen Huang; Guzalnur Askar; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Chemistry, 2026)

Heyndrickxia coagulans JF1 with potent ethanol-degrading capacity: In vitro screening and functional characterization - Feiyu Yang; Xiangfei Li; Jing Sun; Xinyi Pang; Yonghong Hu; Chi Chen; Yingjian Lu; Fengxia Lv (Food Bioscience, 2026)

A functional dietary fiber composite film developed from grapefruit processing waste: superior UV-shielding capacity, hypoglycemic and hypolipidemic activities in vitro, and maintaining the good quality of New Year cakes - Zhanpeng Chen; Xuhao Zhu; Chi Hu; Yuting Wei; Fengsong Liu; Haibo Qin; Zhaolong Wu; Bingzheng Li; Chongxing Huang (Food Hydrocolloids, 2026)

Unlocking potassium sustainability: Rice-crab co-culture system enhances potassium balance - Haixia Liu; Xuran Liu; Feng Zhang; Hongwei Han; Yinghao Li; XiaoLi Wu; Guangyan Liu; Daocai Chi; Jun Meng; Taotao Chen (Field Crops Research, 2026)

Prenatal and postpartum residential greenness and behavioral development in early Childhood: Findings from a birth cohort - Wen-Chi Chao; Ming-Lun Zou; Chih-Da Wu; Jian-Pei Huang; Heng-Kien Au; Chen-Li Lin; Shih-Peng Mao; Hsing-Jasmine Chao; Ling-Chu Chien; Hsueh-Wen Hsu; Pilyoung Kim; Yi-Hua Chen (Environmental Research, 2026)

Machine learning-based prediction of phenanthrene accumulation and toxicity in earthworms across soils - Guo-feng Li; Yong-kai Liao; Hai-feng Chi; You-chi Zhang; Chang-er Chen; Chao Cai (Environmental Research, 2026)

Bimetallic atom incorporation in MOFs: Real-time patch to existing synthesis/characterization insights and initial observations on their applications in water purification - Bin Zou; Yaoning Chen; Huayue Kang; Yuanping Li; Mengyang Zhao; Hongjuan Jiang; Jun Wang; Yihuan Liu; Xuyang Jia; Nianping Chi; Li Zhu (Environmental Research, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

Deciphering silicate weathering archives registered in the late Quaternary sediments of Asian continent marginal seas - Jinniu Chen; Chao Li; Wenshen Xiao; Nicholas Chia Wei Ng; Weibo Lai; Junfei Chen; Chi Zhang; Shouye Yang (Earth-Science Reviews, 2026)

Construction of multifunctional PVA/PA/SiO2 hydrophilic anti-fogging coating with anti-icing, flame-retardant, self-cleaning, and self-healing properties - Xiao Zhang; Jie Li; Jingmiao Zhou; Chi Ma; Hongming Kao; Xinran Yu; Xiangpeng Xu; Jing Chen; Xiang Cui (Chemical Engineering Journal, 2026)

Hierarchical 3D inverse opal MOF composites for synergistic toluene adsorption-photothermal desorption - Liming Liu; Xuehui Jia; Jingyu Bao; Xinqi Luan; Changhao Li; Chi Xu; Liqin Zhou; Jianmin Chen; Zhaowei Jia; Ruimeng Wang; Zhongxing Zhao; Zhenxia Zhao (Chemical Engineering Journal, 2026)

Imiquimod-induced colitis: A novel ROS/ERK-driven model of intestinal inflammation and barrier dysfunction - Kuang-Ting Liu; Shu-Hao Chang; Kuan-Chen Wu; Zheng-Yi Li; Mao-Chia Chang; Yen-Chu Huang; Mu-Chi Chung; Shih-Chung Wang; Yi-Ju Chen; Jeng-Jer Shieh (Chemico-Biological Interactions, 2026)

Balancing Accuracy and Speed: Improved D-FINE for Real-Time Ocean Internal Wave Detection - Lu Yu; Yanping Tian; Jie Chen; Cheng Chi; Tingting Li; Jianwei Li (Journal of Marine Science and Engineering, 2026)
Ocean internal waves (IWs), induced by density stratification and fluid perturbations, are significant oceanic phenomena prevalent across global oceans, profoundly impacting marine environments and engineering safety. Although one-stage object detection models are favored in practical applications due to their efficient inference, they often suffer from insufficient accuracy in IW detection tasks. To address this, we introduce a novel one-stage, anchor-free detection approach based on Transformer for IW detection, proposing a new algorithm named IW-D-FINE, which balances detection accuracy and inference efficiency. On the public SAR dataset, IW-D-FINE achieves an AP@0.5 of 90.5, significantly outperforming existing one-stage methods while maintaining faster inference speeds than mainstream two-stage models. Furthermore, to mitigate the scarcity of internal wave samples, we construct a small-scale IWs dataset, YH3-IW-2025, and validate the algorithm thoroughly on this dataset. Experimental results demonstrate that IW-D-FINE exhibits robust performance under complex background interference, highlighting its application potential and scalability in IW detection tasks.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

miR-17195 promotes infectious bronchitis virus proliferation and macrophage-mediated inflammation via the PLCβ2-TAK1 axis - Zheng Wang; Chi Liu; Xuan Chen; Jianlan Li; Waner Li; Zhaxi Duoji; Qingcheng Yang; Ting Xu; Anyun Zhang; Peng Ma; Hongning Wang (Veterinary Microbiology, 2026)

Light signal transduction networks regulating phenylpropanoid, terpenoid and alkaloid biosynthesis in horticultural plants - Yadi Chen; Lanxi Shi; Qingtao Xu; Chi Zhang; Li Wang; Weixing Li (Journal of Plant Physiology, 2026)

A physics-informed neural network for predicting depth-averaged velocities of flows with submerged vegetation: Integrating analytical formulas with deep learning - Zhipeng Chen; Feng Luo; Yuan Li; Aifeng Tao; Chi Zhang; Jinhai Zheng (Journal of Hydrology, 2026)

Joint inversion method of acoustic emission location and imaging in hydraulic fracturing experiment - Wei Zhu; Yulong Chen; Haitao Li; Hongyu Zhai; Xu Chang; Chi Liu; Yuhua Hou (Journal of Applied Geophysics, 2026)

Spatiotemporal evolution of natural gas leakage and explosion in confined buildings: Insights from accident-driven full-cycle simulation - Minghua Chi; Diya Hou; Fangzhou He; Bin Chen; Wei Li; Yuhao Tan; Hongye Jiang; Xiangguo Zeng (Fuel, 2026)

Study on the mechanism of supercritical ethylene decomposition induced by tert-butyl peroxybenzoate - Zhichen Zhang; Yao Chen; Yahui Li; Yunfeng Zhu; Fangxu Lu; Suocheng Chi; Zhiping Shi; Haowen Chen; Haipeng Jiang; Bing Sun; Wei Xu (Fuel, 2026)

In-situ fabrication of magnetic prussian blue composites for highly selective rubidium recovery from high-salinity brine - Zheng Li; Zilong Chen; Chi Ma; Wei Qin; Jiantuan Jia; Guang Han; Yafei Guo; Tong Pan; Tianlong Deng (Desalination, 2026)

Efficient defect passivation via a branched ammonium salt for 20.46%-efficiency semi-transparent wide-bandgap perovskite solar cells - Chenyu Wang; Haobo Wang; Tianye Xie; Bilal Mehmood; Wei Jiang; Zhijia Chen; Denggao Li; Qindi Wang; Boyi Shi; Haozhen Chen; Zhangbo Lu; Shihua Huang; et al. (Chemical Engineering Journal, 2026)

Nonlinear modeling and interpretation of typhoon disaster losses using machine learning and SHAP values: a case study in Zhejiang Province - Qiuyu Wu; Chi Zhang; Xinru Wang; Lin Zhao; Shao Sun; Tangao Hu; Zhe Li; Ying Chen; Meirong Lu (Natural Hazards, 2026)

Whole‐Genome Single Nucleotide Polymorphism Analysis and High‐Resolution Melting ( HRM ) Differentiation of Edwardsiella anguillarum and Edwardsiella piscicida - Atiek Rahmawaty; Li Wu Cheng; Jue‐Liang Hsu; Shun Maekawa; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2026)
This study aimed to develop a method to differentiate between two closely related bacterial species within the genus Edwardsiella , namely Edwardsiella anguillarum and Edwardsiella piscicida , which cause Edwardsiellosis in fish aquaculture. Whole‐genome single nucleotide polymorphism (SNP) analysis was conducted to assess the genetic relationships among E. piscicida , E. anguillarum and Edwardsiella ictaluri . SNP distance matrices and phylogenetic trees demonstrated that isolates within each species clustered together, confirming genetic SNP distinctiveness. SNP annotation and distance comparisons identified key genes— artI , dnaK , hlyB , ubiB , hutW , ydgD , MCP and fliC —that exhibited significant divergence. We designed specific primers targeting SNPs in these genes and used these primers for real‐time PCR and High‐Resolution Melting (HRM) analysis. HRM analysis using designed primer pairs revealed distinct melting temperature ( Tm ) peaks for E. anguillarum and E. piscicida . HRM analysis of 37 isolates that were previously identified as E. tarda based on phenotypic characteristics identified them as either E. anguillarum (35) or E. piscicida (2). These results showed that hlyB was the most reliable target gene for distinguishing between E. anguillarum and E. piscicida . The HRM technique is a fast, cost‐effective method for differentiating these closely related bacterial species and provides insights into the genetic variation among different species of Edwardsiella and host‐specific strains.

Single-cell immune atlas of mouse testes unveils metabolic reprogramming of FOLR2 + macrophages in orchestrating testicular immunity during aging - Xinyu Li; Min Zhang; Ani Chi; Jiahui Mo; Xiaofeng Tan; Hongde Chen; Chunhua Deng; Xiangzhou Sun; Xin Feng; Zhihong Chen (GeroScience, 2026)

Linking Sidescan Sonar Backscatter Intensity to Seafloor Sediment Grain Size Fractions: Insight from Dongluo Island - Songyang Ma; Bin Li; Peng Wan; Chengfu Wei; Zhijian Chen; Ruikeng Li; Zhenqiang Zhao; Chi Chen; Jiangping Yang; Jun Tu; Mingming Wen (Journal of Marine Science and Engineering, 2026)
Accurate characterization of seafloor sediment properties is critical for marine engineering design, resource assessment, and environmental management. Sidescan sonar offers efficient wide-area mapping capabilities, yet establishing robust quantitative relationships between acoustic backscatter intensity and sediment texture remains challenging, particularly in heterogeneous coastal environments. This study investigates the correlation between sidescan sonar backscatter intensity and sediment grain size parameters in waters southwest of Hainan Island, China. High-resolution acoustic data (450 kHz) were acquired alongside surface sediment samples from 18 stations spanning diverse sediment types. Backscatter intensity, represented by grayscale values, was systematically compared with grain size distributions and individual size fractions. Results reveal that mean grain size shows no meaningful correlation with backscatter intensity; however, fine sand fraction content (0.075–0.25 mm) exhibits a strong negative linear relationship (R2 = 0.87 under optimal conditions). Distribution-level analysis demonstrates that backscatter variability mirrors sediment textural complexity, with coarse sediments producing broad, elevated intensity distributions and fine sediments yielding narrow, suppressed distributions. Inter-survey variability highlights the sensitivity of absolute intensity values to environmental conditions during acquisition. Spatial distribution analysis reveals that sediment grain size follows a systematic NE-SW gradient controlled by hydrodynamic energy, with notable local anomalies controlled by reef structures (producing coarse bioclastic sediment) and topographic sheltering (maintaining fine-grained deposits in shallow areas). These findings provide a quantitative basis for fraction-specific acoustic classification approaches while emphasizing the importance of multi-scale analysis incorporating both regional hydrodynamic trends and local morphological controls. The established relationship between fine sand abundance and acoustic response enables semi-quantitative sediment prediction from remotely sensed data, supporting improved seafloor mapping protocols for offshore infrastructure siting, aggregate resource evaluation, and coastal zone management in morphologically complex environments.

Current progress in the ginger oleoresin: bioactivities, extraction and encapsulation technologies - Chen Huang; Heping Cui; Xinjing Li; Guzalnur Askar; Jingyang Yu; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Critical Reviews in Food Science and Nutrition, 2026)

Dynamic frailty trajectories and risk of age-related macular degeneration: a prospective cohort study in UK Biobank - Yu Peng; Yuzhou Zhang; Ka Wai Kam; Mary Ho; Simon Sezto; Sunny Au; Charlene C. Yim; Xiujuan Zhang; Mandy P. H. Ng; Patrick Ip; Alvin Young; Chi Pui Pang; et al. (GeroScience, 2026)
Age-related macular degeneration (AMD) is a leading cause of irreversible vision loss in the aging population. Although frailty has been recognized as a potential risk factor, previous studies relying on static assessments cannot capture its dynamic nature. This study aims to prospectively evaluate the association between dynamic frailty trajectories and incident AMD. The baseline cohort included 462,573 UK Biobank participants who were free of AMD and had frailty phenotype (FP) data at enrollment. Among them, 53,059 with at least one follow-up FP assessment comprised the trajectory cohort. Participants were categorized as nonfrail, prefrail, or frail based on their FP scores. Annualized frailty progression (ΔFP/year) was estimated via linear regression. Cox models assessed hazard ratios (HRs) and 95% confidence intervals (CIs) for AMD. During a median follow-up of 11.8 years in the baseline cohort, 13,428 incident AMD cases (2.9%) were documented. Prefrail (HR:1.14; 95% CI:1.10–1.18) and frail (HR:1.36; 95% CI: 1.26–1.47) individuals had significantly higher AMD risks compared to nonfrail participants. In the frailty trajectory analysis with a median follow-up duration of 3.3 years, 852 incident AMD cases (1.6%) were recorded. Each 1-point FP increase conferred 28% higher AMD risk (HR: 1.28; 95% CI: 1.18–1.38), while each 0.1-point/year ΔFP increase independently elevated risk by 15% (HR: 1.15; 95% CI: 1.10–1.21). Compared to stable nonfrail, prefrailty aggravation showed highest AMD risk (HR: 2.26; 95% CI: 1.51–3.37), followed by frailty alleviation (HR: 1.73; 95% CI: 0.98–3.04) and frailty maintenance (HR: 1.72; 95% CI: 0.86–3.41). Progressive frailty trajectories, independent of baseline status, is associated with increased incident AMD risk. Early interventions targeting frailty progression may mitigate AMD risk in aging populations.

Unraveling the drivers of corn yield response to optimization fertilization in plateau acidic red soils - Zhengfa Chen; Keyu Yan; Hui Yan; Xiaohan Mei; Chi Wang; Xingwei Chen; Wanli Hu; Bin Fu; Ming Ni; Zhiwu Li; Qingsong Duan; Yanmei Hu; et al. (Field Crops Research, 2026)

A pH/glucose dual-responsive Janus dressing with optimized gradient modulus/tissue adhesion promotes diabetic wound healing by dynamic drug-payload release - Huabiao Ye; Ting Dong; Ruoxuan Li; Lihua Fang; Kaifang Xie; Guangting Han; Que Chen; Shan Chi; Jia-Horng Lin; Ching-Wen Lou (Chemical Engineering Journal, 2026)

Confinement-desolvation-interfacial matching trilogy boost wide-temperature-range zinc‑iodine batteries - Shang Sun; Hao Luo; Wenjing Zhang; Yu Fu; Fan Li; Min Zhou; Shunyao Li; Chi Chen; Hanna He; Lina Ma (Chemical Engineering Journal, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Unveiling the effects of reactor configurations on the performance of lignin removal in the ozone micro-nano-bubble system - Yin Lu; Xuyin Yuan; Haiming Kan; Chi Zhang; Lin Chen; Alessandro Gottuso; Francesco Parrino; Tong Li; Shishu Zhu; Dawei Wang (Chemical Engineering Journal, 2026)

Ion-dipole interactions regulated interface for stable high-depth of discharge Zn anode - Pengyan Jiang; Xiaobin Hui; Yuyang Yi; Renjie Li; Jingya Yu; Feiyang Chen; Liucheng Cao; Chi Fai Cheung; Kai Qi; Bao Yu Xia; Zheng-Long Xu (Chemical Engineering Journal, 2026)

Synergistic effects of spatial morphology and thermal comfort on pedestrian activities in residential areas: A field-based study in Wuhan, China - Shen Xu; Siyi Liu; Chi Zhang; Shuangquan Shao; Hongbo Li; Xufeng Chen; Minghao Wang (Building and Environment, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

The Biological Basis, Mechanisms of Action, and Optimization Strategies of Exosomes Derived from Mesenchymal Stem Cells for the Treatment of Alzheimer’s Disease - Can Zhang; Weihong Long; Junjie Ni; Zhuo Chen; Xu Wu; Mingxing Li; Fukuan Du; Yueshui Zhao; Jing Shen; Chi Hin Cho; Xi He; Zhangang Xiao (Molecular Neurobiology, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Editorial Expression of Concern: Minocycline Protects Against NLRP3 Inflammasome-Induced Inflammation and P53-Associated Apoptosis in Early Brain Injury After Subarachnoid Hemorrhage - Jianru Li; Jingsen Chen; Hangbo Mo; Jingyin Chen; Cong Qian; Feng Yan; Chi Gu; Qiang Hu; Lin Wang; Gao Chen (Molecular Neurobiology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Active and targeted micro/nanoplastics remediation via engineered microalgae co-displaying polymer-binding peptides and plastic-degrading enzymes: A critical review and perspectives - Ling Wang; Mingjing Zhang; Jialin Wang; Chen Hu; Zhanyou Chi; Lei Li; Wenjun Luo; Chengze Li; Chenba Zhu (Algal Research, 2026)

Discovery of lignans and curcuminoids as the effective inhibitors of pancreatic lipase: structure-activity relationship and inhibitory mechanism - Jie Mu; Rui-Dong Wang; Yi-Shu Zhao; Tian-Chi Lu; Si-Si Chen; Yi-Jing Wang; Hua Wei; Li-Wei Zou (Natural Product Research, 2025)

PRINCE: Advanced classification algorithm for rice grain recognition in clustered images - Bidong Chen; Lingui Li; Han Zhu; Meijuan Tan; Guanhua Liu; Haiyang Chi; Xu Yang; Yapeng Wang (Computers and Electronics in Agriculture, 2025)

Resilience of coastal human-environment composite systems of the 21st century maritime silk road: Theory, model, and spatial patterns - Jie Zhong; Yongchao Liu; Luodan Cao; Chao Ying; Chi Zhou; Yiyu Cao; Hongjia Chen; Jialin Li (Marine Pollution Bulletin, 2025)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Research on cracking behavior of ice specimens containing single and double flaws under uniaxial compression - Chen Chi; Yiheng Zhang; Ying Tang; Xiaobin Li; Wei Chen; Qing Wang; Duanfeng Han; Yinggang Li (Ocean Engineering, 2025)

Gradient elution method for treating the residual ammonium from the weathered crust elution-deposited rare earth tailings - Kejia Wu; Ruipu Wang; Jia Wang; Xiaodi Li; Yuchi Chen; Li Guo; Qingbiao Zhao; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi; Junxia Yu (Minerals Engineering, 2025)

Transforming glyphosate mother liquor into zirconium‑phosphorus composite adsorbent for effective Pb (II) removal from lead‑zinc tailing leachate - Bowen Dong; Ruipu Wang; Shuang Xi; Yuanping Guo; Jing Wang; Yuting Li; Li Guo; Yuchi Chen; Ruan Chi; Jia Wang; Junxia Yu (Journal of Water Process Engineering, 2025)

Determination of dissolved inorganic carbon export and the controlling factors in small mountainous Rivers, Taiwan - Man-Ching Choi; Pei-Hao Chen; Chi-Wang Tsui; Jr-Chuan Huang; Jun-Yi Lee; Li-Chin Lee (Journal of Hydrology, 2025)

Fingerprinting sediment sources of the largest desert reservoir in Asia and its environmental implications - Guoxiang Chen; Zheng Chi; Zhibao Dong; Aimin Liang; Xiaokang Liu; Guang Li (Journal of Hydrology, 2025)

Computational toxicology Insights into pyriproxyfen and its transformation products: An overlooked driver of aquatic toxicity and endocrine disruption - Min Li; Lang Chen; Han Gao; Leyuan Ji; Feng Chen; Lan Zhang; Liangang Mao; Lizhen Zhu; Xingang Liu; Chi Wu (Journal of Environmental Management, 2025)

Reaction mechanism and kinetics for selective recovery of REEs from Nd-Fe-B magnet sludge by low-temperature chlorination - Haiyan Chen; Haibo Xu; Yeyin Li; Zhibin Li; Xin Wang; Bo Jiang; Rongshun Lai; Wenbin Fan; Chuntao Xiang; Zhi Yang; Xiao Chi; Qiang Ma (Journal of Environmental Chemical Engineering, 2025)

ALM-LED: autonomous LiDAR mapping in underground space with Luojia explorer anti-collision drone - Shangzhe Sun; Chi Chen; Bisheng Yang; Yuhang Xu; Leyi Zhao; Yong He; Ang Jin; Liuchun Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Nitrate modulates high CO2 effects on carbon partitioning in Gracilariopsis lemaneiformis: Trade-offs between particulate and dissolved organic carbon sequestration - Jichen Chen; Chi Song; Yicheng Ke; Mengmeng Wang; Jianing Qiu; Liujun Nie; Gang Li; Guang Gao (Environmental Research, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Unleashing instant on-site naked-eye detection by a portable NIR-SPR platform with organic upconversion - Li-Chen Su; Xin-Hui Wang; Chun-Jen Shih; Zhi-Hao Huang; Ying-Feng Chang; Chen-Kai Chang; Chi-Yun Wang; Yu-Ching Huang; Shun-Wei Liu (Chemical Engineering Journal, 2025)

Negative-pressure induced controllable foaming reaction for ultralight and flame-retardant phenyl-containing silicone rubber foam nanocomposites modified with low content of graphene oxide - Shuai-Chi Liu; Yun-Hao Qu; Dun-Peng Bao; De-Mei Kong; Zhi-Hao Xu; Zuan-Yu Chen; Yang Li; Jie-Feng Gao; Yong-Qian Shi; Pingan Song; Guo-Dong Zhang; Long-Cheng Tang (Chemical Engineering Journal, 2025)

Hydrophobic sponge spicule-mediated transdermal vaccination combines controlled skin inflammation as self-adjuvant with dual immune activation - Yutong Zeng; Huichao Xie; Mengzhu Liu; Qixia Jiao; Hui Huang; Shuxian Fu; Bao Li; Yongfeng Chen; Chi Zhang; Pingtian Ding; Ming Chen; Keda Zhang (Chemical Engineering Journal, 2025)

Predicting offshore downhole rock drillability in complex geological conditions using explainable machine learning and Multi-Source data - Huayang Li; Quanyou Liu; Jiaao Chen; Chi Zhang; Dantong Liu; Zehui Shi; Xinyi Wang (Earth Science Informatics, 2025)

Full-genome sequence of a novel potyvirus infecting Sauropus androgynus - Li-Juan Zhu; Shulian Su; Jingke Li; Yubin Chi; Yankun Zhu; Xing Chen; Lan-Yi Su; Juncheng Zhang; Zhongtian Xu (Virus Genes, 2025)

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Norsesquiterpenes from the stems and leaves of Pinellia pedatisecta Schott - Xu Chen; Yan-gang Cao; Fang-Ge Chi; Yan-ling Liu; Kai-li Ye; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2025)

Characteristics of bulk wave run-up on shoreface-nourished beach - Yuan Li; Shubin Chen; Jiatao Cai; Shaohua Zhao; Fan Yu; Hongshuai Qi; Chi Zhang (Ocean Engineering, 2025)

Wavelength-dependent photobiomodulation attenuates synovial inflammation in fibroblast-like synoviocytes and a collagenase-induced osteoarthritis model - Tianxiang Fan; Peng Xia; Safayet Ahmed; Yuen H. Tsang; Zhi Yao; Deli Wang; Ziyu Chen; Lixiang Xue; Dongquan Shi; Bo Wang; Chi Fai Cheung; Marco Y.C. Pang; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

Correlation between saltiness-enhancement and fluorescence intensity of Maillard reaction intermediates from corn peptides and taste stability during subsequent thermal reaction - Xinjing Li; Tong Zhou; Chen Huang; Guzalnur Askar; Jingyang Yu; Shiqing Song; Foxin Zhang; Shahzad Hussain; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Chemistry, 2025)

Five/six carbon monosaccharides-glycated coconut protein-stabilized emulsions: Impact on stability and digestion - Zhen Yang; Mi Tian; Chili Zeng; Liang Chen; Zengzhao Chi; Lianzhou Jiang; Dongze Li; Zhaoxian Huang (Food Chemistry, 2025)

Elucidating the degradation mechanisms for capacity fading in cylindrical-type rechargeable alkaline Ni-Zn batteries - Liting Deng; Long Gu; Xian Li; Wencheng Su; Yuying Zhang; Jiajun Chen; Jianan Yu; Bin Wang; Chi-Wing Tsang; Chunzhen Yang (Chemical Engineering Journal, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Reconstruction of vertical temperature profile based on sea surface variables using convolutional neural network - Mengzhu Li; Chi Zhang; Jun Li; Xin Chen; Zichen Wang; Taihong Li (Acta Oceanologica Sinica, 2025)

A steroid-rich fraction from parasitic climber Cocculus hirsutus (L.) W.Theob inhibits coronavirus disease and neutrophilic inflammation - Vidya Febrasca Tenderly; Thiyagarajan Raviraj; Yen Chi Loo; Olha Mykhailenko; Marcela Safratova; Stefan Kosturko; Mahendra Jadhao; Yu-Li Chen; Tsong-Long Hwang; Fang-Rong Chang; Michal Korinek (Phytochemistry Letters, 2025)

Discovery of a new 1-monoglyceride from Streptomyces albogriseolus JM128 symbiotic with Lendenfeldia sponge - Yun-Ting Zeng; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; You-Ying Chen; Li-Guo Zheng; Chih-Yin Huang; Hsi-Wen Sun; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Clay minerals limit nanoplastic uptake in wheat plant - Jie Yang; Chen Tu; Ruijie Li; Lianzhen Li; Ying Liu; Zijian Liu; Meiting Chi; Yongming Luo (Journal of Hazardous Materials, 2025)

Gamma-irradiation-driven fabrication of robust underwater superoleophobic nylon mesh for high-efficiency oil/water separation - Chao Shen; Canran Li; Xianghui Li; Haijun Chen; Dongxun Zhang; Gang Deng; Peng Li; Haolong Wang; Chi Zhao (Journal of Environmental Chemical Engineering, 2025)

Dual-fixation strategy for preparing PCM/PVA electrospun membranes: High encapsulation efficiency and thermal reliability - Chi Hu; Yuqing Sun; Zhijun Zhang; Xuanyu Chen; Zihang Li; Xiong Liang; Bainan Li; Chongxing Huang (Journal of Environmental Chemical Engineering, 2025)

Environmental nanotechnology for dual-functional water remediation: Mg-doped magnetic biochar overcomes recyclability-adsorption trade-off in nutrient recovery - Qi Wu; Yi Zhao; Xiaolong Liu; Daocai Chi; Haifeng Liu; Wei Chen; Hongbo Zhang; Yanqi Li; Ye Jin; Qingliang Liu; Yang Sun (Journal of Environmental Chemical Engineering, 2025)

Flavoromics analysis and sensory evaluation of wines produced from nine red grape cultivars in Manas region, Xinjiang, China: Implications for terroir adaptation - Ning Shi; Yi-Fan Zhao; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Jia-Yi Deng; Jia-Yan Wei; Ai-Sai Chen; Chi-Fang Cheng; Shu-De Li; Fei He; Keji Yu; et al. (Food Chemistry, 2025)

Carbon sequestration in mangrove ecosystems: Sources, transportation pathways, influencing factors, and its role in the carbon budget - Shafiqa Ali; Gobinda Dey; Nguyen Hoang Kim Nuong; Abdur Rahman; Liang-Chi Wang; Uttara Sukul; Koyeli Das; Raju Kumar Sharma; Shan-Li Wang; Chien Yen Chen (Earth-Science Reviews, 2025)

Synergistic passivation by fluorinated aromatic amines enables 22.11 %-efficient wide-bandgap perovskite solar cells - Zhijia Chen; Chenyu Wang; Denggao Li; Ziyu Li; Qindi Wang; Boyi Shi; Shihua Huang; Dan Chi (Chemical Engineering Journal, 2025)

Sulfur-induced electron migration in thin-layered Bi2MoO6 triggers 1O2-dominated pathway for selective NO photoconversion - Hongjing Liu; Shan Ren; Xiaodi Li; Qingqing Zhou; Yao Yang; Peng Chen; Shouning Chai; Chi He; Bofeng Bai; Fan Dong (Chemical Engineering Journal, 2025)

A feasible method for preparing garnet matrix with vertically aligned microchannels for all-solid-state lithium batteries - Ruotong Ma; Chi Zhang; Wenyi Xiang; Lihan Chen; Zongzi Jin; Cui Li; Lei Zhang; Weiwei Ping; Chusheng Chen; Chengwei Wang (Chemical Engineering Journal, 2025)

Residual polyacrylamide-induced membrane fouling in short-flow coagulation-ultrafiltration: Behavior and mechanism - Mohan Wei; Yaozhong Zhang; Xing Zheng; Chi Zhang; Jiheng Duan; Kai Guo; Menghan Wang; Dongfei Li; Tianshuo Huang; Rong Chen (Chemical Engineering Journal, 2025)

Seasonal growth and biomass production of cold-tolerant Napier Grass line L2201 - Swee-Suak Ko; Tzu-Rung Li; Jo-Chi Hung; Hsien-Chang Kuo; Min-Jeng Li; Jeng-Bin Lin; Ping-Han Chung; Lin-Hsiang Lee; Yueh-Hua Lin; Hong-Ping Lin; Charles C.-K Chou; Kuo-Chen Yeh (Biomass and Bioenergy, 2025)

Changes in the physiological indicators and gene expression for grass carp (Ctenopharyngodon idella) in response to alkaline stress - Qi Chen; Jianbo Zheng; Yi Xu; Fei Li; Shili Liu; Wenping Jiang; Meili Chi; Shun Cheng; Haiqi Zhang (Aquaculture International, 2025)

A selenium nanozyme: Light/mercury dual-enhanced oxidase mimicry for simultaneous ultra-sensitive detection and efficient removal of mercury ions, and superior photocatalytic bacterial disinfection - Yu Shi; Dong-hui Li; Chi Zhang; Zheng-ren Wang; Yi-ran Wang; Ru-kang Chen; Yen-ho Chu; Yu-gang Shi; Rammile Ettelaie; Qing Gu (Water Research, 2025)

Genomic characterization of Gillisia xinjiangensis sp. nov.: insights into nitrogen metabolism, stress adaptation, and application potential - Hao-hao Wang; Chi Zhang; Ya-qin Chen; Yi-fan Guo; Li-jian Ding; Sheng-fa Zhang; Gai-jun Du; Wei-yan Zhang; Shan He (Systematic and Applied Microbiology, 2025)

Mapping drag coefficient using CFD and machine learning with application to urban canopy model - Jie Chen; Ziwei Mo; Congyu Li; Wai-Chi Cheng; Chun-Ho Liu (Sustainable Cities and Society, 2025)

RNA target-independent non-canonical activation (RINCA) of Cas13 trans-nuclease activity - Wenjun Liu; Xuena Zhu; Yuanyuan Xue; Xiaoyan Wang; Lei Chang; Shanshan Wang; Ling Li; Jinyan Huang; Ying Zhang; Cheng Jiang; Hongjie Chi; Yanbin Zhang; et al. (Science Bulletin, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Novel genetically engineered silk materials for recycling polyethylene terephthalate (PET) plastic waste - Chi Tian; Yuancheng Wang; Dihua Yuan; Yanglin Li; Xinyu Tang; Yinlin Chen; Tinghao Luo; Guanwang Shen; Ping Zhao; Qingyou Xia (Journal of Hazardous Materials, 2025)

Estrogenic and transgenerational effects of perfluorocarboxylic acids through estrogen-related receptor γ pathway - Sha Shi; Wei Zheng; Xi-Long Zhang; Minjie Li; Cheng Ye; Lu Chen; Wen-Jun Hong; Chuan-Hai Li; Huiyu Chi; Fangfang Li; Liang-Hong Guo (Journal of Hazardous Materials, 2025)

Innovative application of recyclable magnetic LDO beads for enhancing the remediation of Cd and Pb contamination and the humification during composting - Hongjuan Jiang; Zhigang Yi; Yaoning Chen; Yuanping Li; Mengyang Zhao; Jun Wang; Yihuan Liu; Xuyang Jia; Mengwei Luo; Yaoqin Nie; Nianping Chi (Journal of Hazardous Materials, 2025)

Multiple defects construction of Co loading on Ni foam to activate water for promoting catalytic ozonation of dichloromethane - Yongtao Li; Chujun Luan; Fawei Lin; Xueyan Zhu; Beibei Yan; Zhanjun Cheng; Guanyi Chen; Chi He (Journal of Hazardous Materials, 2025)

Molecular identification of salty and saltiness-enhancing peptides from Stropharia Rugosoannulata and their salinity perception with secondary structure and sodium chloride - Guzalnur Askar; Xue Xia; Xinjing Li; Chen Huang; Foxin Zhang; Shahzad Hussain; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Chemistry, 2025)

Selecting a representative tea for risk assessment of pesticide residue in tea:Afidopyropen as a case - Mingming Guo; Zhaoqun Li; Yujie Qin; Kexin Qian; Chi Su; Jiawei Yu; Hezhi Sun; Xinzhong Zhang; Xinru Wang; Mei Yang; Fengjian Luo; Zongmao Chen; et al. (Food Chemistry, 2025)

Novel multifunctional phenanthro[9,10-d]oxazole-based fluorophore towards efficient blue and two-color white OLEDs with high color rendering index - Hao-Sen Liao; Bao-Yue Wang; Dong Chen; Jia-Hao Liu; Ruo-Tong Zhao; Hai-jun Chi; Yan-Li Lv; Bo Zhao; Xiao Li (Chemical Engineering Journal, 2025)

Design of 2D/2D Pt SA-MoS2/ZnIn2S4 photocatalysts for boosting hydrogen production - Xue-Lu Chen; Miao Ni; Yan-Ru Li; Yi-An Pan; Chen Chi; Yi Yang; Si-Meng Li; Sudip Biswas; Yi-Bai Sun; Xing-Hua Xia (Chemical Engineering Journal, 2025)

Interfacial molecular engineering with p-F-MBAI achieves 22.43% efficiency and exceptional stability in wide-bandgap perovskite solar cells - Ziyu Li; Tianye Xie; Chenyu Wang; Zhijia Chen; Denggao Li; Qindi Wang; Boyi Shi; Shihua Huang; Fan Zheng; Dan Chi (Chemical Engineering Journal, 2025)

In-situ secondary organic aerosol formation from ambient air in suburban Eastern China: Substantially distinct characteristics between summer and winter - Jibin Dou; Tengyu Liu; Dafeng Ge; Ying Zhang; Junchao Yin; Lei Wang; Haoyu Liu; Duzitian Li; Guangdong Niu; Liangduo Chen; Jiaping Wang; Ximeng Qi; et al. (Atmospheric Environment, 2025)

Exploring the potential of Trichoderma asperellum TCS007 on growth promotion of pecan seedlings as well as rhizosphere soil nutrients and microbial community - Hao Cao; Xue-song Li; Hao Han; Sai Chen; Jing Jin; Jing Yuan; Chi-zhou Liang; Jian-fei Lu; Feng Cui; Jie Chen (Plant and Soil, 2025)

Assessing landslide risks across varied land-use types in the face of climate change - Chi-Wen Chen; Yu-Shiang Tung; Fang-Yi Chu; Hsin-Chi Li; Yung-Ming Chen (Landslides, 2025)

Synergistic ammonium and carbon removal in aquaculture effluent using red seaweed Agardhiella subulata - Zi-Yan Xu; Bonien Chen; Chiu-Hui Kuo; Chen-Hsun Liu; Li-Lian Liu; Yu-Yun Chen; Jui-Kuo Kao; Feng-Cheng Wu; Pao-Chi Liao; Kuohsun Chiu (Environmental Science and Pollution Research, 2025)

Seismic risk and loss assessment models for highway continuous girder bridges in large-scale zones - Si-Qi Li; Peng-Fei Qin; Peng-Chi Chen; Yi-Ru Li; Jia-Cheng Han; Jian Zhong (Soil Dynamics and Earthquake Engineering, 2025)

Bioactive terpenoids and sterols from the fruiting bodies of Fomitopsis pinicola - Huan Yu; Qian Chen; Tian-Chi Xu; Yue Wang; Wen-Feng Xu; Min Li; Xu Zhang; Chuan Zhao; Dong-Li Zhang; Peng-Fei Jin; Shao-Yong Li; Sheng-An Tang (Phytochemistry, 2025)

Impacts of environmentally persistent free radicals on the denitrification toxicity of photoaged tire wear particles in estuarine sediments - Jinyu Ye; Yuhan Zhang; Yuan Gao; Chen Li; Baoping Zou; Ruotong Cheng; Baoyan Chi; Xiangdong Xue; Carlos Domingo-Félez (Journal of Hazardous Materials, 2025)

WITHDRAWN: Field investigation of the profile development of artificial sandy beach impacted by wave overwash - Zhubin Cao; Jinhai Zheng; Chi Zhang; Weiqiu Chen; Shanhang Chi; Yuan Li; Hang Yin (Estuarine, Coastal and Shelf Science, 2025)

Origins of synoptic and intraseasonal variabilities in the Northwestern Pacific monsoon trough - Hongyu Chen; Chi Qin; Tim Li (Climate Dynamics, 2025)

Assessment of the seismic risk and vulnerability of low-rise masonry structures considering a simplified regression model - Si-Qi Li; Peng-Chi Chen (Bulletin of Earthquake Engineering, 2025)

Fungal community is more sensitive to the short-term application of biochar in saline farmland soil than bacterial community - Bin Zhu; Jinqiu Li; Jizhi Li; Xin Chen; Guangyu Chi (Applied Soil Ecology, 2025)

Eremothecium species from Cardiospermum halicacabum and Koelreuteria henryi, and their associated soapberry bugs - Cheng-Hsuan Li; Jie-Hao Ou; Chi-Yu Chen (Mycological Progress, 2025)

Direct recovery of high-purity uranium from fluoride-containing nuclear wastewater via extraction materials with ensemble Lewis sites and a tandem electrochemical device - Guo Li; Yan Liu; Chi Jiao; Zhengyu Jiang; Juan Zhang; Tao Chen; Tao Lin; Rong He; Wenkun Zhu; Xiangke Wang (Water Research, 2025)

Fragmentation characteristics and energy components of cylindrical rock specimens in a novel collision system - Zong-Xian Zhang; Li Yuan Chi; Zida Liu; Toochukwu Ozoji; Chen Huang; Wuxing Wu; Nikhil Bakkamuntala (International Journal of Rock Mechanics and Mining Sciences, 2025)

Dual-functional Zn@melanin nanoparticles for enhanced antibacterial activity and prolonged fruit preservation - Yangjing Li; Wei Tian; Tao Chen; Yanfei Li; Runan Zhao; Yuxin Li; Xuesong Chi; Di Wu; Yinan Du; Jiangning Hu (Food Chemistry, 2025)

Impacts of production wastewater reuse on water quality safety and microbial community dynamics in drinking water treatment plants - Hailong Zhu; Weiying Li; Dawei Zhang; Chen Zhang; Guozheng Chi; Zhongqing Wei; Xingzhong Xu (Environmental Research, 2025)

Porous carbon with predominant graphitic nitrogen and abundant defects mediated by reductive molten salt enables boosted sulfur conversion for room-temperature sodium-sulfur batteries - Kejian Tang; Xiangqi Peng; Ziying Zhang; Yingxinjie Wang; Guohao Li; Jie Wang; Chi Chen; Xiuqiang Xie; Zhenjun Wu (Chemical Engineering Journal, 2025)

Screening and fermentation optimization of Methylophilus sp. HN238 for efficient microbial protein production using methanol - Aijia Shi; Menghan Chi; Zhen Zhu; Wenqin Bai; Jinling Cai; Limei Chen; Demao Li (Systems Microbiology and Biomanufacturing, 2025)

Mechanism of adaptive laboratory evolution for improving polyunsaturated fatty acid biosynthesis in Aurantiochytrium sp. through enhancing high-glucose adaptability - Zhipeng Li; Danling Tang; Lifen He; Yuanzhen Song; Wei Hang; Huipeng Liu; Guoxiang Chi; Tao Hong; Hui Ni; Qingbiao Li; Zhen Chen; Ning He (Algal Research, 2025)

Analysis of the migration mechanisms of tire wear Particles in quartz sand: Insights into aging pathways and pH regulation effects - Jianghua Yu; Chi Liu; Zhangle Chen; Zidong Ye; Kun Li (Journal of Environmental Chemical Engineering, 2025)

Preparation and functional characteristics of starch-lipid complexes with different oleic acid-rich glycerolipids - Huijing Chen; Shanliang Zhong; Guoxiang Chi; Huiying Li; Kewei Chen; Zhirong Wang; Jianquan Kan (Food Chemistry, 2025)

Composite antimicrobial films activated by essential oil pickering emulsions: Preparation, characterization and application in pork preservation - Lin Liu; Tanghui Liu; Guihong Li; Qingqing Tan; Anjun Tang; TingTing Wen; Ziming Li; Hai Chi; Hongrui Chen; Jie Tang; Xingzhong Zhang (Food Bioscience, 2025)

Development of a novel LBL@DHBA/Cu-MOF coating on titanium implants to accelerate early osseointegration by promoting neural-vascular-bone coupling regeneration - Peng Hua; Xiaoyi Pan; Jiming Liu; Xuemei Chen; Manjuan Li; Yan Guo; Xuan Li; Pengyuan Leng; Guoyong Fan; Mengjiao Zheng; Kai Yu; Pingping Ma; et al. (Chemical Engineering Journal, 2025)

Functional molecule surface infiltration treatment for efficient all-inorganic perovskite light-emitting diodes - Shurui Chi; Yongjian Chen; Xiuling Li; Jiaqi Wang; Zixun Zhao; Zhuojian Li; Yanqin Miao; Xin Tong; Jinli Liu; Yuechuan Bi; Zongwen Liu; Zhiming Wang; et al. (Chemical Engineering Journal, 2025)

Stabilizing ultra-high Ni layered cathodes for high-voltage operation through Al doping with synergistic Sn modification - Yuhuan Wang; Chi Chen; Shuangjia Weng; Chunyu Li; Yang Xia; Xiaoxiao Lu (Chemical Engineering Journal, 2025)

Global Research and Emerging Trend of Superabsorbent Hydrogel Applied to Agriculture Based on Visual Analysis - Zhiwen Li; Yuankai Zhou; Tian Qin; Wei Liu; Xiaohao Guo; Yalan Zhang; Sunlin Chi; Jinying Xu; Zanxu Chen; Yongdong Zhang; Jiyi Kang; Xianchuan Xie; et al. (Water, Air, & Soil Pollution, 2025)

Anti-inflammatory effects of resveratrol in treating interstitial cystitis/bladder pain syndrome: a multi-faceted approach integrating network pharmacology, molecular docking, and experimental validation - Wenshuang Li; Ruixiang Luo; Zheng Liu; Xiaoyang Li; Chi Zhang; Junlong Huang; Ziqiao Wang; Jialiang Chen; Honglu Ding; Xiangfu Zhou; Bolong Liu (Molecular Diversity, 2025)

Upper limit of ice content at the lunar south pole as revealed by the Earth-based SYISR–FAST bistatic radar system - Mingyuan Li; Jinghai Sun; Xin’an Yue; Honglei Lin; Zhiqing Chen; Feng Ding; Baiqi Ning; Yong Wei; Chi Wang; Peng Jiang (Science Bulletin, 2025)

Zeolite amendment enhances grain yield and mitigates greenhouse gas emissions in an intensive aerobic rice system - Xuda Chen; Guangyan Liu; Boyang Liu; Taotao Chen; Yinghao Li; Wei Chen; Jiayin Pang; Kadambot H.M. Siddique; Daocai Chi (Field Crops Research, 2025)

Hydrophilic modification and synergistic interaction of phosphate-amidoxime adsorbent for enhanced uranium extraction from seawater - Lina Lv; Tingting Deng; Lu Wang; Hao Peng; He Chen; Xiaoyu Li; Fangting Chi (Desalination, 2025)

Comprehensive regulation of swelling, salt-shrinkage resistance and antibacterial abilities towards polyamidoxime fibers for efficient uranium extraction from seawater - Xiaoyu Li; Hao Peng; Tingting Deng; He Chen; Lu Wang; Lina Lv; Shuang Xie; Fangting Chi (Chemical Engineering Journal, 2025)

Vacancy engineering in transition metal selenides for long-lasting and fast-charging Na-ion batteries - Changsheng An; Jialing Liu; Chen Xu; Chi Zhang; Ruiting Li; Shumin Zhang; Shiying Zhang; Jinbo Li; Chao Cai; Xing Ou (Chemical Engineering Journal, 2025)

Ultra-high xylan content solid-state ionic conductors with mechanical excellence - Peng Ding; Kai Zhao; Chi Wang; Ren'ai Li; Guangxue Chen; Zheng Jia; Minghui He (Carbohydrate Polymers, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Overexpression of Heme Oxygenase 1 Enhances the Neuroprotective Effects of Exosomes in Subarachnoid Hemorrhage by Suppressing Oxidative Stress and Endoplasmic Reticulum Stress - Qiongqiong Gao; Zhumin Su; Xiangxiong Pang; Jinshuo Chen; Ruixiang Luo; Xiaoyang Li; Chi Zhang; Yun Zhao (Molecular Neurobiology, 2025)

Research advances in branched-chain amino acid metabolism in tumors - Zheng Li; Sainan Chen; Xuechao Wu; Fei Liu; Jing Zhu; Jiayi Chen; Xiaojie Lu; Rui Chi (Molecular and Cellular Biochemistry, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

First genome-wide association and genomic prediction of ammonia‑nitrogen tolerance in tiger pufferfish (Takifugu rubripes) - Yong Chi; Clémence Fraslin; Robert Mukiibi; Yuanri Hu; Weidong Li; Diego Robledo; Songlin Chen; Yangzhen Li (Aquaculture, 2025)

Nitrogen-doped carbon modified with boron atoms activating peroxydisulfate for sulfamethoxazole degradation: The electron transfer-dominated pathway - Yaoning Chen; Chen Zhao; Yuanping Li; Mengyang Zhao; Huayue Kang; Yihuan Liu; Hongjuan Jiang; Li Chen; Jun Wang; Wencheng Zhou; Nianping Chi (Journal of Environmental Chemical Engineering, 2025)

Effect of tertiary amine carbon quantum dots incorporation on oil/water separation performance of membranes - Gabriel V. Carballo; Hsin-Yi Lin; Pei-Chen Chen; Hong-Li Yang; Rhoda B. Leron; Chi-Lan Li; Hui-An Tsai; Kueir-Rarn Lee (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils” [Icarus 429 (2025) 116448] - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

An electrochemical immunosensing of electrochemically modified carbon cloth electrode based on functionalized gold nanoparticle-Prussian blue for the detection of aflatoxin B1 in vegetable oil industry - Hai Chi; Xuefei Wen; Huan Li; Jie Tang; Xingzhong Zhang; Hongrui Chen (Food Chemistry, 2025)

Comparative Analysis of the Complete Mitochondrial Genomes of Three Sisoridae (Osteichthyes, Siluriformes) and the Phylogenetic Relationships of Sisoridae - Yunpeng Wang; Shiyi Chen; Yifan Liu; Shufei Zhang; Xun Jin; Sixu Zheng; Jiasheng Li; Ying Peng; Kun Zhang; Chi Zhang; Bingjian Liu (Biochemical Genetics, 2025)

Environmental heterogeneity drives the spatial distribution of macrobenthos in the Yellow River Delta wetland - Qinglu Fu; Jiao Wang; Debin Sun; Jianyu Chi; Wenzheng Fan; Yu Li; Yilin Wang; Baoquan Li; Linlin Chen (Aquatic Sciences, 2025)

Low high-temperature tolerance of the hydrothermal vent crab Xenograpsus testudinatus: Thermal biochemistry, survival rate and histological analyses, and habitat investigations - Li-Chun Tseng; Hong-Miao Chen; Chi Chou; Wen-Hung Twan; Yan-Ying Zhou; Lan Wang; Jiang-Shiou Hwang (Science of The Total Environment, 2025)

Shortwave cloud warming effect observed over highly reflective Greenland - Haotian Zhang; Chuanfeng Zhao; Jing Li; Yan Yu; Annan Chen; Yikun Yang; Yan Xia; Jie Yang; Yue Sun; Yulei Chi; Xin Zhao; Yuan Wang; et al. (Science Bulletin, 2025)

Experimental and non-hydrostatic modelling of wave transformation and runup on a reef-fronted beach - Chi Zhang; Shubin Chen; Yuan Li; Gen Liu; Songgui Chen; Aijun Li; Hui Fang (Ocean Engineering, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Aeration strategies for microalgae in wastewater treatment: Enhancing pollutant removal and community dynamics - Pan Li; Yajun Luo; Fei Ming; Jingxian Zheng; Zhicheng Pan; Rui Wang; Yanqing He; Miao Zhou; Xin Xiong; Chi Zhang; Yu Lei; Zhaoqi Wang; et al. (Journal of Environmental Management, 2025)

Biomass moulding fuel for zero-emission agricultural waste management: A case study of tobacco curing in China - Tianbao Ren; Ding Yan; Youjian Zhang; Xiaolong Li; Jian Chen; Chuliang Wang; Chi Wang; Peiyan Li; Longfei Wang; Qiang Zeng; Xianjie Cai (Journal of Environmental Management, 2025)

Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Discovery of the dipicolinic acid synthase in the spoilage fungus Paecilomyces reveals its role in spore heat, salt, and alkaline pH resistance - Su-Yan Wang; Yun-Jiao Zhang; Li-Xiao Chen; Yi-Bo Pang; Daniela D. Herrera-Balandrano; Paul Daly; Feng-Quan Liu; Marta Filipa Simões; Xin-Chi Shi; Pedro Laborda (Food Research International, 2025)

High-pressure homogenization assisted pH-shifting modified soybean lipophilic protein interacting with chitosan hydrochloride: Double emulsion construction, physicochemical properties, stability, and in vitro digestion analysis - Yiting Gao; Le Chen; Lijia Li; Huiyue Chi; Fei Teng (Food Hydrocolloids, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Orchestrated immune responses to Mycobacterium marinum natural infection in tongue sole (Cynoglossus semilaevis) - Yangzhen Li; Limin Song; Xu Yan; Yong Chi; Yuanri Hu; Jialin Wang; Diego Robeldo; Robert Mukiibi; Songlin Chen (Fish & Shellfish Immunology, 2025)

Efficient and stable PEI@MSF adsorbents for CO2 removal in confined space: Insights into silica foam support with ultra-large pore structure - Junyang Lu; Feng Yan; Tong Chi; Bangqiang Li; Heijin Chen; Xuehua Shen; Zuotai Zhang (Chemical Engineering Journal, 2025)

Unveiling the role of heteroatom doping and strain in Core-Shell catalysts for CO2RR - Yiran Bai; Yunjian Wang; Yibing Yang; Chen Sun; Hsiao-Tsu Wang; Chi-Feng Lee; Cheng-You Li; Tingting Zheng; Kunpeng Jiang; Lili Han (Chemical Engineering Journal, 2025)

The biodegradable poly(3-hydroxypropionate) from acrylic acid via 3-hydroxypropionic acid: Studies on catalytic hydration and self-polycondensation - Zhen-Yang Lu; Zhao Chen; Zhuo Li; Zi-Yi Chi; Xue-Gang Li; Shuang-Yu Wei; Cheng-Wei Liu; Wen-De Xiao (Chemical Engineering Journal, 2025)

Orally administered metal–organic framework nanocubes for sequence-targeted quercetin delivery in colitis alleviation - Runan Zhao; Tao Chen; Shumeng Hu; Xuesong Chi; Songfeng Yu; Yanfei Li; Wenjun Wang; Beiwei Zhu; Donghong Liu; Jiangning Hu (Chemical Engineering Journal, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

AI integration into wavelength-based SPR biosensing: Advancements in spectroscopic analysis and detection - Ying-Feng Chang; Yu-Chung Wang; Tsung-Yu Huang; Meng-Chi Li; Sin-You Chen; Yu-Xen Lin; Li-Chen Su; Kwei-Jay Lin (Analytica Chimica Acta, 2025)

Retraction notice to “Investigation on the evolution of hydrothermal biochar”[Chemosphere 307 (2022) 135774] - Ming Li; Yang Wang; Zhangfeng Shen; Mingshu Chi; Chen Lv; Chenyang Li; Li Bai; Hamdy Khamees Thabet; Salah M. El-Bahy; Mohamed M. Ibrahim; Lai Fatt Chuah; Pau Loke Show; et al. (Chemosphere, 2025)

Growth characteristics based multi-class kiwifruit bud detection with overlap-partitioning algorithm for robotic thinning - Haojie Dang; Leilei He; Yufei Shi; Lamin L. Janneh; Xiaojuan Liu; Chi Chen; Rui Li; Hongbao Ye; Jinyong Chen; Yaqoob Majeed; Xiaoxi Kou; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Development of an oral vaccine delivery system for shrimp aquaculture using attenuated Listeria monocytogenes - Jeff Chia-Kai Hsu; Te-Ken Hsu; Shuh-Bing Guan; Po-Wei Chi; Chih-Ying Chiang; Colin William Pouton; Zi-Wey Wong; Po-Yu Huang; Li-Li Chen (Aquaculture, 2025)

A QTL associated with vibriosis resistance highlights the significant role of jam2a gene in tongue sole (Cynoglossus semilaevis) - Yangzhen Li; Yong Chi; Xu Yan; Yuanri Hu; Zhongming Li; Lei Jia; Songlin Chen (Aquaculture, 2025)

Diffusive gradients in thin-films (DGT) for in situ measurement of neonicotinoid insecticides (NNIs) in waters - Junwu Xiong; Chang Pu; Zhe Qian; Jiapei Yi; Kang Wang; Chi Zhang; Wei Liu; Wei Chen; Li Xu; Shihua Qi; Zulin Zhang; Hao Zhang; et al. (Water Research, 2025)

RF-DET: Refocusing on the small-scale objects using aggregated context for accurate power transmitting components detection on UAV oblique imagery - Zhengfei Yan; Chi Chen; Shaolong Wu; Zhiye Wang; Liuchun Li; Shangzhe Sun; Bisheng Yang; Jing Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Predicting the adsorption of ammonia nitrogen by biochar in water bodies using machine learning strategies: Model optimization and analysis of key characteristic variables - Guixian Xie; Chi Zhu; Chen Li; Zhiping Fan; Bo Wang (Environmental Research, 2025)

Regulation of chain conformation and synergistic effect of auxiliary groups towards polyamidoxime for highly efficient uranium extraction from seawater - Hao Peng; Xiaoyu Li; Lina Lv; Tingting Deng; He Chen; Lu Wang; Qiang He; Caiping Dang; Lianggui Bao; Yihao You; Fangting Chi (Chemical Engineering Journal, 2025)

Dual protonation reactions in biphasic absorbents facilitate efficient capture of low-concentration CO2 from gas-fired power plants - Hang Yu; Lijian Jin; Hangqi Yang; Wenrui Li; Shudan Chi; Fan Zhang; Heng Chen; Linjun Yang (Chemical Engineering Journal, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

α-Glucosidase inhibitory activities of aromatic compounds from the rhizomes of Alpinia galanga - Yueh-Hung Cheng; Po-Chun Chen; Zakhele M. Dlamini; Jia-Wei Li; Bongani S. Dlamini; Yu-Kuo Chen; Chi-I Chang (Medicinal Chemistry Research, 2025)

Influence of PGV and response spectra on human walking states in simulated earthquake scenarios - Li Tiefei; Chi Mingjie; Chen Xueliang; Liu Xinyu; Li Zongchao; Ji Zhiwei; Chu Jian (Journal of Seismology, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

A newly developed 20 K SNP array reveals QTLs for disease resistance to Cryptocaryon irritans in tiger pufferfish (Takifugu rubripes) - Yangzhen Li; Clémence Fraslin; Yong Chi; Robert Mukiibi; Yuanri Hu; Jialin Wang; Weiguo Li; Weidong Li; Ross D. Houston; Diego Robledo; Songlin Chen (Aquaculture, 2025)

Transcriptome and pathophysiological analysis during Bacillus cereus group infection in Pelodiscus sinensis uncovered the importance of iron and toll like receptor pathway - Li-Wu Cheng; Qiong-Yi Huang; Pei-Chi Wang; Ming-An Tsai; Shih-Chu Chen (Aquaculture, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

Electro-Fenton-assisted Camellia oleifera by-product composting for reduction of greenhouse gas emission and improvement of humification - Li Chen; Zhigang Yi; Yaoning Chen; Yuanping Li; Hongjuan Jiang; Jun Wang; Mengyang Zhao; Yanrong Chen; Wei Zhang; Nianping Chi; Guangming Zeng (Chemical Engineering Journal, 2025)

Cation W-doping motivated novel layered K0.45Rb0.05Mn0.85−xWxMg0.15O2 cathode for boosting potassium/sodium-ion storage - Yucong Chen; Xiaobo Chen; Jia Li; Hongjie Chen; Yixuan Su; Weitao Chen; Chengrun Yu; Francis Chi-Chun Ling; Qiang Ru (Chemical Engineering Journal, 2025)

Experimental investigation on cross-shore profile evolution of reef-fronted beach - Yuan Li; Chi Zhang; Shubin Chen; Hongshuai Qi; Weiqi Dai; Huimin Zhu; Titi Sui; Jinhai Zheng (Coastal Engineering, 2025)

Calibration of the Solar X-ray Detector on-board the Macao Science Satellite-1B for Soft X-ray Detection - Man-Hei Ng; Xiaoping Zhang; Jianwu Chen; Yongqiang Shi; Fuchang Zuo; Wenxi Peng; Weichun Fu; Liansheng Li; Pengwei Luo; Chi-Long Tang; Guozheng Zhang; Zhiwu Mei; et al. (Science China Earth Sciences, 2025)

The obesity-related mutation gene on nonalcoholic fatty liver disease - Yen-Yu Chen; Chi-Sheng Chen; Jee-Fu Huang; Wen-Hsiu Su; Chia-Yang Li; Wei-Shiun Chen; En-Sheng Lin; Wan-Long Chuang; Ming-Lung Yu; Shu-Chi Wang (Human Genetics, 2025)

Development of seismic risk models for low-rise masonry structures considering age and deterioration effects - Si-Qi Li; Peng-Fei Qin; Peng-Chi Chen; Lin-Lin Zheng; Can Zhang (Bulletin of Earthquake Engineering, 2025)

Suitability assessment of treated wastewater with various dilution levels for irrigation in a rain-fed area: implications for crop growth and element translocations in Sorghum bicolor (L.) Moench - Li-Chi Chiang; Ci-Jyun Liao; Chihhao Fan; Ya-Zhen Huang; Feng-Wen Chen (Paddy and Water Environment, 2025)

Lincomycin as a growth-promoting antibiotic induces metabolic and immune dysregulation in animals - Hongyuhang Ni; Haoze Wu; Jing Wang; Bill Kwan-wai Chan; Kaichao Chen; Edward Wai-Chi Chan; Fuyong Li; Sheng Chen (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Sustainable management strategy for phosphorus in large-scale watersheds based on the coupling model of substance flow analysis and machine learning - Wei Liu; Tian Qin; Yuejin Chen; Junbao Yin; Zhiwen Li; Hanzhi Wang; Guangwei Ruan; Jiaqi Zhu; Huoqing Xiao; Evgeny Abakumov; Yalan Zhang; Hu Du; et al. (Resources, Conservation and Recycling, 2024)

Identification of BpEXP family genes and functional characterization of the BpEXPA1 gene in the stems development of Betula platyphylla - Yao Chi; Zihan Wang; Shizhong Chen; Lin Feng; Meiqi Zhou; Yang Li; Ying Yu; Caiqiu Gao; Chao Wang (Journal of Plant Physiology, 2024)

Biodegradable and conventional mulches inhibit nitrogen fixation by peanut root nodules – potentially related to microplastics in the soil - Wei Guo; Jizhi Li; Zhengfeng Wu; Guangyu Chi; Caiyan Lu; Jian Ma; Yanyu Hu; Bin Zhu; Miaoyin Yang; Xin Chen; Huiying Liu (Journal of Hazardous Materials, 2024)

Efficient removal of chromium from electroplating sludge by a novel combined process of alkaline oxidizing roasting, water leaching and on-line adsorption - Chengbin Zhong; Junxia Yu; Jia Wang; Xiaodi Li; Li Guo; Ruan Chi; Yuchi Chen; Yue Chen (Journal of Environmental Chemical Engineering, 2024)

Effect of inoculation with different Eurotium cristatum strains on the microbial communities and volatile organic compounds of Fu brick tea - Yu Xiao; Hui Chen; Yulian Chen; Chi-Tang Ho; Yuanliang Wang; Ting Cai; Shi Li; Jinrong Ma; Tianyang Guo; Liang Zhang; Zhonghua Liu (Food Research International, 2024)

Volatilomics of Cabernet Sauvignon grapes and sensory perception of wines are affected by canopy side in vineyards with different row orientations - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Hui-Qing Li; Ming-Yu Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Andrea Schubert; Jun Wang (Food Chemistry, 2024)

The simultaneous addition of chitosan and peat enhanced the removals of antibiotics resistance genes during biogas residues composting - Jieqi Ye; Xinxin Liu; Muhammad Khalid; Xiaoxiao Li; Martin Romantschuk; Yucheng Bian; Chi Li; Junren Zhang; Chang Zhao; Jian Wu; Yinfeng Hua; Weihua Chen; et al. (Environmental Research, 2024)

Nature-inspired temperature-adaptive module: Achieving all-season passive thermal regulation for buildings - Lin Liang; Jianheng Chen; Kaixin Lin; Xueming Yang; Sai Liu; Chui Ting Kwok; Hao Pan; Ziai Liu; Aiqiang Pan; Siru Chen; Yihao Zhu; Wei Li; et al. (Energy and Buildings, 2024)

Investigation on the overall performance of hydrogel-based thermochromic windows with various structures - Chuyao Wang; Sai Liu; Xin Li; Qiuyi Shi; Wenqi Wang; Yang Fu; Jianheng Chen; Chi Yan Tso (Energy and Buildings, 2024)

Preparation and performance study of three-dimensional interconnected structured electrodes with lamellar connections - Bing Yang; Bo Wang; Peng Li; Jing Chen; Bo Li; Lushan Ma; Futian Zhang; Haitao Guo; Yunfeng Tian; Xuzhuo Sun; Bo Chi (Chemical Engineering Journal, 2024)

Crocin-1 laden thermosensitive chitosan-based hydrogel with smart anti-inflammatory performance for severe full-thickness burn wound therapeutics - Xiansen Lv; Hui Li; Ya Chen; Yanting Wang; Jinhua Chi; Shuo Wang; Yan Yang; Baoqin Han; Zhiwen Jiang (Carbohydrate Polymers, 2024)

Uncovering paleoenvironmental evolution in Xinghua Bay of Southern China during the mid-to-late Holocene, insights from studies of biogeochemical elements in sediments - Jinrong Wang; Xin Xu; Lianbao Chi; Xin Li; Yongchao Wang; Miaohua Jiang; Jianming Chen; Jing Li; Xin Fan (Journal of Paleolimnology, 2024)

Chang’E-7 Lunar Soil Water Molecule Analyzer (LSWMA) Prototype for High-Precision Measurement of Water Content and Hydrogen Isotope Ratio - Rui Chen; Wenzhen Lu; Xiang Li; Xingping Wang; Kan Chen; Chi Zhang; Nailiang Cao; Zhenyu Xu; Yi Xu; Ruifeng Kan; Renrui Liu; Qiquan Yang; et al. (Journal of Earth Science, 2024)

Investigating illicit drug hotspots and daily variations using sewer-network wastewater analysis - Hank Hui-Hsiang Lin; Ming-Chi Hsieh; Jennifer Ia Wen Wen Liu; Yu-Hsiang Wang; Shu-Jie Huang; En Lien; Li-Wei Huang; Pei-Te Chiueh; Hsin-Hsin Tung; Angela Yu-Chen Lin (Chemosphere, 2024)

Immune responses in giant groupers after vaccination with inactivated bivalent vaccine against betanodavirus and ranavirus - Yu-Hsuan Kai; Chun-Kuei Chang; Hong-Qi Li; Wei-Hsu Chen; Shau-Chi Chi; Yu-Chi Wu (Aquaculture, 2024)

Shallow groundwater table fluctuations weaken nitrogen accumulation in the thin layer vadose zone of cropland around plateau lakes, Southwest China - Qingfei Chen; Anqiang Chen; Jinheng Min; Lin Li; Wanli Hu; Chi Wang; Bin Fu; Shufang Guo; Dan Zhang (Science of The Total Environment, 2024)

Fluid evolution and genesis of the Shipenggou gold deposit in Central Jilin Province, China: Constraints from C–H–O and in–situ sulphur isotopes of pyrite and fluid inclusions - Jun-chi Chen; Ke-yong Wang; Xiang-jin Yan; Qing-ying Zhao; Li-Xue Sun (Geochemistry, 2024)

Natural restoration has more stable soil leucine aminopeptidase kinetic characteristics than plantations - Jinmei Bao; Falin Chen; Chi Zhang; Lizhi Wang; Bo Liu; Longchao Yang; Xinli Wang; Yuan Gao; Junxia He; Yinghong Chen; Yang Li; Yun Wang (Forest Ecology and Management, 2024)

Capture and in-situ conversion of low-concentration CO2 over robust poly(ionic liquid)@porous carbon nanocomposites under green, co-catalyst- and solvent-free conditions - Mengshuai Liu; Chi Ma; Qi Wang; Ranyue Li; Shengze Yu; Hui Chen; Fusheng Liu (Chemical Engineering Journal, 2024)

Defect passivation engineering for achieving 4.29% light utilization efficiency MA-free wide-bandgap semi-transparent perovskite solar cells - Hongxi Shi; Tianye Xie; Denggao Li; Ziyu Li; Zhijia Chen; Chenyu Wang; Shihua Huang; Zhangbo lu; Fan Zheng; Dan Chi (Chemical Engineering Journal, 2024)

Immune response and protection efficacy of formalin‐killed vaccines against Streptococcus iniae in four‐finger threadfin Eleutheronema tetradactylum - Yin‐Ze Shi; Andre Giovanni; Li‐Wu Cheng; Wen‐Rou Huang; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Four‐finger threadfin, Eleutheronema tetradactylum farming in southern Taiwan has been facing disease problems caused by Streptococcus iniae since 2018. The development of a vaccine against infectious S . iniae in the cultured threadfin industry is necessary. Thus, this study aimed to examine the efficacy of threadfin immunized formalin‐killed cells (FKC) from S . iniae GSI‐111 for 42 days post‐vaccination (dpv) using two doses of FKC alone (a booster at 14 dpv) as group A, and FKC mixed with ISA763A adjuvant using a single dose as group B or double doses as group C. Immunoglobulin (Ig)‐M was purified from threadfin, and rabbit anti‐threadfin IgM polyclonal antibodies were used to detect antibody level in immunized fish; the vaccinated group A displayed higher levels at 3 dpv and all vaccinated treatments demonstrated high antibody levels between 14 and 42 dpv. All vaccine groups showed significantly higher values of lysozyme activity at 42 dpv compared with the control group; the vaccinated A group peaked at 14 dpv. The expression profiles of pro‐inflammatory and immune‐related genes, TNF‐α , IL‐12A , and C2 were upregulated at 3 dpv, while CD8A and chemokine receptor CXCR4 were upregulated at 42 dpv. Finally, the threadfins were challenged with S . iniae at 42 dpv. The average relative percent survival was 96% for vaccination A and B treatments, and 100% for vaccination C treatment. In summary, this study demonstrated that FKC vaccines whether formulated with an adjuvant could stimulate immune response and effective protect threadfins against S . iniae infection.

Microplastics and arsenic speciation in edible bivalves from the coast of China: Distribution, bioavailability, and human health risk - Zhendong Lyu; Xiaohan Chen; Ting Wei; Difeng Wang; Puhui Zhao; Edmond Sanganyado; Duowen Chi; Zewei Sun; Tieyu Wang; Ping Li; Wenhua Liu; Ran Bi (Marine Pollution Bulletin, 2024)

Assessment of the seismic failure of reinforced concrete structures considering the directional effects of ground motions - Si-Qi Li; Ke Du; Yong-Sheng Chen; Peng-Fei Qin; Gabriele Milani; Antonio Formisano; Peng-Chi Chen; Lin-Lin Zheng; Can Zhang (Soil Dynamics and Earthquake Engineering, 2024)

Corrigendum to “Investigations on the shallow water wave attenuation over continuous porous oyster reef-like structure” [Ocean Eng. 287 Part 2 (November 2023)] - Yunhan Yang; Titi Sui; Guangsheng Wang; Chi Zhang; Peixiong Chen; Yuan Li; Jian Zeng; Richard Aidoo (Ocean Engineering, 2024)

Advancements and future prospects in in-situ catalytic technology for heavy oil reservoirs in China: A review - Li Wang; Jixiang Guo; Chi Li; Ruiying Xiong; Xiangwei Chen; Xiaojun Zhang (Fuel, 2024)

Sodium carboxymethyl cellulose hydrogels containing montmorillonite-NaClO2 for postharvest preservation of Chinese bayberries - Zhanpeng Chen; Yuting Wei; Ren Liu; Chi Hu; Yuqing Sun; Chunguang Yao; Zhaolong Wu; Bingzheng Li; Zisheng Luo; Chongxing Huang (Food Chemistry, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

High efficiency in blue TADF OLED using favorable horizontal oriented host - Yi-Zhen Li; Hsuan-Chi Liang; Chia-Hsun Chen; Ching-Huang Chiu; Lian-Chun Huang; Yi-Ting Lee; Yi-Chung Dzeng; Chi Chen; Bo-Yen Lin; Jiun-Haw Lee; Tien-Lung Chiu; Man-kit Leung (Chemical Engineering Journal, 2024)

High-efficiency blue hybridized local and charge-transfer fluorescent material affording OLEDs with external quantum efficiency exceeding 14 % - Guiming Wu; Xiangyu Ge; Zhan Yang; Yanyan Liu; Zhu Chen; Yuyuan Wang; Gaoyu Li; Danman Guo; Huangjun Deng; Juan Zhao; Zhenguo Chi (Chemical Engineering Journal, 2024)

The role of ALDH1A1 in glioblastoma proliferation and invasion - Yu-Kai Huang; Tzu-Ming Wang; Chi-Yu Chen; Chia-Yang Li; Shu-Chi Wang; Khushboo Irshad; Yuan Pan; Kun-Che Chang (Chemico-Biological Interactions, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Applications of multi-omics techniques to unravel the fermentation process and the flavor formation mechanism in fermented foods - Linfeng Wen; Lixin Yang; Cong Chen; Jun Li; Jiangyan Fu; Guo Liu; Qixin Kan; Chi-Tang Ho; Qingrong Huang; Yaqi Lan; Yong Cao (Critical Reviews in Food Science and Nutrition, 2024)

Spatiotemporal changes of ecosystem services value and cross regional ecological compensation in the Yangtze River Basin - Chen Chi; Juqin Shen; Xin Gao; Zhichao Li; Fuhua Sun (Environment, Development and Sustainability, 2024)

Deciphering the impact of organic loading rate and digestate recirculation on the occurrence patterns of antibiotics and antibiotic resistance genes in dry anaerobic digestion of kitchen waste - Yanzeng Li; Shenghua Zhang; Zhou Chen; Weizhao Huang; Qin Liu; Hongda Fang; Bin Chi; Ningbo Yang; Qian Zhang (Water Research, 2024)

The mother-offspring transfer of chlorothalonil through human breast milk: A multi-city cross-sectional study - Chi Zhang; Xuezhen Zhao; Xingqi Pan; Gerili Zaya; Bing Lyu; Shaohua Li; Jingguang Li; Yunfeng Zhao; Yongning Wu; Dawei Chen (Science of The Total Environment, 2024)

Paospora carinifang n. gen., n. sp. (Microsporidia: Spragueidae), a parasite of the ridgetail white prawn, Palaemon carinicauda - Yuan Wang; Ying Na; Yan-qing Huang; Jun-fang Zhou; Shou-hu Li; Quan-lin Liu; Le-tian Li; Yuan-ge Chen; Wei Tian; Hai Chi; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2024)

Wastewater-based epidemiology to monitor 68 NPS/conventional drug use in Taipei metropolitan area in Taiwan during and after COVID-19 pandemic - Te-Tien Ting; Pin-Chuan Chen; Ya-Chi Chang; Pin-Ju Chiang; Hsu-Cheng Li; Shih-Hsun Chen; Pei-Chieh Chen; Hai-Tien Chu; Ping-Yu Chuang; Yi-Hsin Liu; Pai-Shan Chen (Journal of Hazardous Materials, 2024)

Sustainable flood control strategies under extreme rainfall: Allocation of flood drainage rights in the middle and lower reaches of the yellow river based on a new decision-making framework - Xin Huang; Juqin Shen; Shuqin Li; Chen Chi; Ping Guo; Pei Hu (Journal of Environmental Management, 2024)

Meta-transcriptome-based molecular characterization of a novel fijivirus detected in a Sogatella furcifera population from Myanmar - Kuo Wu; Yongdui Chen; Lizhen Zhang; Qiannan Li; Zar Chi Htwe Yin; Yanqiong Yin; Jiahong Dong (Journal of Asia-Pacific Entomology, 2024)

Influence of Chinese herbal plants on greenhouse gas emissions from pig manure composting and fermentation - Ya-jun Duan; Hong-sheng Wu; Guang-yao Chen; Feng-yi Hu; Yan-hui Li; Zhen-wei Li; Jin-he Chi; Dong-ming Lu; Xiao-ming Gu; Ming-chun Di (International Biodeterioration & Biodegradation, 2024)

Effects and mechanisms of kitchen waste organic fertilizers application on soil nitrogen transformation, plant pathogenic virulence genes, and metabolites - Zhou Chen; Shenghua Zhang; Yanzeng Li; Bin Chi; Weizhao Huang; Jian Wu (Chemical Engineering Journal, 2024)

Enzyme induced polymer degradation as a pathway to create microbial habitats for biomanufacturing intensification - Wei Cheng; Huilin Wen; Haixia Shen; Chenwei Fu; Erkuang Miao; Dongbao Li; Xiaoqiang Chen; Chi Hu; Ziyi Yu (Chemical Engineering Journal, 2024)

Bimetallic porphyrin PET radiotracers for Low-Dose MRI contrast enhancement - Chen Xie; Xiong Li; Leilei Zhang; Ho-Fai Chau; Waygen Thor; Wing Sze Tam; Benjamin Woolley; Mingjun Jiang; Chi-Fai Ng; Mauro Botta; Tao Zhang; Nicholas J. Long; et al. (Chemical Engineering Journal, 2024)

Climate risk analysis of low-altitude tea gardens in central Taiwan using a Bayesian network - Yung-Chieh Wang; Chien-Teh Chen; Rui-Yu Li; Yu-Hsin Lu; Li-Chi Chiang (Environmental Monitoring and Assessment, 2024)

Comparative pathogenicity and histopathological analysis of Edwardsiella anguillarum intraperitoneal infection in milkfish ( Chanos chanos ), Nile tilapia ( Oreochromis niloticus ) and Asian seabass ( Lates calcarifer ) - Atiek Rahmawaty; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Edwardsiella anguillarum , a highly virulent species within the Edwardsiella genus, causes significant mortality in milkfish farms in Taiwan. This study aimed to investigate the comparison of milkfish susceptibility, a newly identified host species in Taiwanese aquaculture, with other species Nile tilapia ( Oreochromis niloticus ) and Asian seabass ( Lates calcarifer ), to E. anguillarum , elucidating its pathogenicity across both seawater and freshwater aquaculture environments. The results showed milkfish exhibited the highest mortality rate of 85% within 48 h of infection, whereas Nile tilapia exhibited a mortality rate of 70% between the second‐ and tenth‐day post challenge, and seabass exhibited a mortality rate of 25% between the second‐ and sixth‐day post challenge. Gross lesions observed in milkfish included splenomegaly and haemorrhage, whereas Nile tilapia exhibited signs of ascites, exophthalmia and brain haemorrhage. Seabass displayed spleen granulomas and haemorrhage at the injection site. Histopathological analysis revealed common features across all three species, including multifocal necrosis, bacterial presence in the necrotic areas, serositis and oedema. Asian seabass also exhibited chronic lesions in the form of splenic granulomas. This study highlights the high susceptibility of milkfish and Nile tilapia to E. anguillarum , emphasizing the urgent need for further investigation into targeted vaccine development for these fish species. These results not only deepen our understanding of the differing levels of pathogenicity among the three species but also offer valuable insights for improving disease prevention and management strategies in aquaculture, including those applied within polyculture systems and for the maintenance of aquaculture water environments.

Variability and driving effect of aquatic gross primary productivity across long-distance inter-basin water diversion project - Cheng Lai; Xizhi Nong; Lihua Chen; Chi Zhang; Luiza C. Campos; Kourosh Behzadian; Ronghui Li (Journal of Cleaner Production, 2024)

Evaluation and obstacle analysis of sustainable development in small towns based on multi-source big data: A case study of 782 top small towns in China - Mingman Chen; Chen Chen; Chi Jin; Bo Li; Yingqing Zhang; Ping Zhu (Journal of Environmental Management, 2024)

Shallow groundwater table fluctuations promote the accumulation and loss of phosphorus from surface soil to deeper soil in croplands around plateau lakes in Southwest China - Qingfei Chen; Wenchao Li; Anqiang Chen; Jinheng Min; Wanli Hu; Chi Wang; Bin Fu; Dan Zhang (Journal of Environmental Management, 2024)

Iron biogeochemical redox cycling dominantly controls cadmium availability in acidic paddy soils - Yang Yang; Tongxu Liu; Thomas Borch; Liping Fang; Shiwen Hu; Wenting Chi; Guojun Chen; Kuan Cheng; Qi Wang; Xiaomin Li; Xiu Yuan; Fangbai Li (Geochimica et Cosmochimica Acta, 2024)

Biocompatible hydrophobic cross-linked cyclodextrin-based metal-organic framework as quercetin nanocarrier for enhancing stability and controlled release - Runan Zhao; Tao Chen; Yanfei Li; Lihang Chen; Yu Xu; Xuesong Chi; Songfeng Yu; Wenjun Wang; Donghong Liu; Beiwei Zhu; Jiangning Hu (Food Chemistry, 2024)

MSC-Derived Extracellular Vesicles Alleviate NLRP3/GSDMD-Mediated Neuroinflammation in Mouse Model of Sporadic Alzheimer’s Disease - Lishan Lin; Longxin Huang; Sen Huang; Weineng Chen; Heng Huang; Li Chi; Fengjuan Su; Xiaoqing Liu; Kang Yuan; Qiuhong Jiang; Changu Li; Wanli W. Smith; et al. (Molecular Neurobiology, 2024)

IGFBP2 induces podocyte apoptosis promoted by mitochondrial damage via integrin α5/FAK in diabetic kidney disease - Xiaochen Wang; Yifan Zhang; Kun Chi; Yuwei Ji; Keying Zhang; Ping Li; Zhangning Fu; Xu Wang; Shaoyuan Cui; Wanjun Shen; Guangyan Cai; Xiangmei Chen; et al. (Apoptosis, 2024)

Evaluation of spatial and temporal changes in illicit drug use in the Taipei metropolitan area via wastewater-based epidemiology - Hank Hui-Hsiang Lin; Yu-Hsiang Wang; Jennifer Ia Wen Wen Liu; Ming-Chi Hsieh; Shu-Jie Huang; En Lien; Li-Wei Huang; Angela Yu-Chen Lin (Science of The Total Environment, 2024)

Toxicology assessment of deep-sea mining impacts on Gigantidas platifrons: A comparative in situ and laboratory metal exposure study - Li Zhou; Chao Lian; Yameng He; Xupeng Chi; Hao Chen; Zhaoshan Zhong; Minxiao Wang; Lei Cao; Hao Wang; Huan Zhang; Chaolun Li (Science of The Total Environment, 2024)

Functional identification of specialized diterpene synthases from Chamaecyparis obtusa and C. obtusa var. formosana to illustrate the putative evolution of diterpene synthases in Cupressaceae - Tsai-Jung Wu; Chi-Chun Lin; Li-Ting Ma; Chih-Kai Yang; Chen-Lung Ho; Sheng-Yang Wang; Fang-Hua Chu (Plant Science, 2024)

Global daily mask use estimation in the pandemic and its post environmental health risks: Analysis based on a validated dynamic mathematical model - Ying Zhang; Fei Jiang; Fengmin Li; Shaoyong Lu; Zihao Liu; Yuwen Wang; Yiming Chi; Chenchen Jiang; Ling Zhang; Qingfeng Chen; Zhipeng He; Xiaoli Zhao; et al. (Journal of Hazardous Materials, 2024)

Functionalized ligands mediated microenvironment of Pd@UiO-66-X catalysts for ethanol upgrading to n-butanol - Yaohui He; Huanqi Gou; Danfeng Zhou; Peng Wang; Shaowen Hou; Xinhui Chen; Yixing Wang; Fenghao Guo; Mengchuan Wang; Chi Wang; Jinshu Tian; Xiaonian Li; et al. (Fuel, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Exposure and health risk assessment of volatile organic compounds among drivers and passengers in long-distance buses - Jing-Jie Chen; Tiffany B. Wang; Li-Te Chang; Kai-Jen Chuang; Hsiao-Chi Chuang; Ta-Yuan Chang (Environmental Research, 2024)

Prenatal exposure to fenvalerate causes depressive-like behavior in adulthood by inhibiting brain-derived 5-HT synthesis - Hui-Min Zhu; Bo Wang; Tao Wang; Jing Shao; Hui-Ru Chen; Chi Zhang; Li-Hua Xu; Jing-Jing Li; Min Wang; De-Xiang Xu; Xiu-Hong Meng (Environmental Pollution, 2024)

A NIR-II quantum dot-assisted dual-color imaging strategy enables simultaneous tracking of two subtypes of extracellular vesicles in vivo - Xing-Chi Liu; He-Jing Zhang; Rui Xu; Jing Liu; Hou-Fu Xia; Qi-Hui Xie; Zhi-Quan Tian; Zi-Li Yu; Gang Chen (Chemical Engineering Journal, 2024)

Comparative pathogenicity of Nocardia seriolae in Nile tilapia ( Oreochromis niloticus ), milkfish ( Chanos chanos ) and Asian seabass ( Lates calcarifer ) - Sandra Celenia Nazareth; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Nocardiosis, caused by Nocardia seriolae , has been a prominent disease in Southeast Asian aquaculture in the last three decades. This granulomatous disease reported in various fish species is responsible for significant economic losses. This study investigated the pathogenicity of N. seriolae in three cultured species in Taiwan: Nile tilapia (omnivore), milkfish (herbivore) and Asian seabass (carnivore). Administration of an infective dose of 1 × 10 6 CFU/ fish in tilapia, seabass and milkfish demonstrated mortalities of 100%, 90% and 75%, respectively. Additionally, clinical signs namely, granuloma and lesions displayed varying intensities between the groups and pathological scores. Polymerase chain reaction (PCR) amplification specific for N. seriolae was confirmed to be positive (432 bp) using NS1/NG1 primers. Post‐mortem lesions revealed the absence of granulomas in tilapia and milkfish and their presence in the seabass. Interestingly, the gut in tilapia showed an influx of eosinophils suggesting its role during the acute stages of infection. However, post‐challenge, surviving milkfish exhibited granulomatous formations, while surviving seabass progressed toward healing and tissue repair within sampled tissues. Overall, in conclusion, these results demonstrate the versatility in the immunological ability of individual Perciformes to contain this pathogen as a crucial factor that influences its degree of susceptibility.

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

Ergosterols with rare peroxide, oxetane ring moiety, and a lactone ring from Aspergillus spectabilis and their immunosuppressive activities - Mengsha Wei; Hong Liao; Qin Li; Xueying Deng; Chi Gao; Nanjin Ding; Weiguang Sun; Hucheng Zhu; Jieru Guo; Chunmei Chen; Yonghui Zhang (Phytochemistry, 2024)

Identification of the cytochrome P450 gene AccCYP6A13 in Apis cerana cerana and its response to environmental stress - Li Lei; Zihan Gao; Qinglong Zhao; Chen Wang; Ying Wang; Hongfang Wang; Xuepeng Chi; Baohua Xu (Pesticide Biochemistry and Physiology, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

Cellulose nonwoven with fast liquid-discharging and anti-return properties: A microplastic-free surface layer for disposable absorbent hygiene products - Mei Liu; Chi Ma; Yong Chen; Yaning Wang; Jielin Xu; Zhenguang Li; Lili Deng; Liming Zou; Jing Wu; Huaping Wang (Chemical Engineering Journal, 2024)

Algae-leached DOM inhibits the Hg(II) reduction and uptake by lettuce in aquatic environments under light conditions - Xu Yang; Ruihong Yu; Tantan Wang; Xin Wen; Yubo He; Zihao Li; Chi Ma; Wenhao Chen; Chang Zhang (Aquatic Toxicology, 2024)

Losing Tidal Flats at the Midpoint of the East Asian-Australasian Flyway over the past 100 Years - Wan-Jyun Chen; An-Yu Chang; Chia-Chi Lin; Ruey-Shing Lin; Da-Li Lin; Pei-Fen Lee (Wetlands, 2024)
The ecosystem services and functions of tidal flats have been overlooked for many decades, and tidal flat loss has been identified as a serious threat to many taxa in recent years, especially for migratory waterbirds. Despite the understanding of tidal flats change on the global scale, there are still a lot of unknowns on the small scale, including tidal flats in Taiwan, which are important stopover sites for migratory waterbirds along the East Asian–Australasian Flyway. Therefore, we collated historic topographic maps, Landsat Archive images between the 1920s and the 2020s to determine the trajectories of tidal flat change along the coastline of Taiwan. Our results show that tidal flat coverage expanded between the 1920s and the 1950s, but lost approximately 266 km 2 (58%) between the 1950s and the 2010s. The status of the tidal flats along the western coastline of Taiwan has been identified as “Endangered” based on the criteria of the IUCN Red List of Ecosystems. According to the aims of the Global Biodiversity Framework, we suggest rethinking the land use plans along the coastline to mitigate the tidal flat loss, especially the controversial issues concerning the expansion of green energy infrastructure. To realize the Nature Positive goals by 2030, recovering and restoring the tidal flat ecosystem could be one of the key strategies.

Differences of Escherichia coli isolated from different organs of the individual sheep: molecular typing, antibiotics resistance, and biofilm formation - Zihao Wu; Haoming Chi; Tingting Han; Guangxi Li; Jixue Wang; Wei Chen (Folia Microbiologica, 2024)

Natural and engineered enzymes for polyester degradation: a review - Rey-Ting Guo; Xian Li; Yu Yang; Jian-Wen Huang; Panpan Shen; Rock Keey Liew; Chun-Chi Chen (Environmental Chemistry Letters, 2024)
Plastic pollution is becoming a major health issue due to the recent discovery of microplastics and nanoplastics in living organisms and the environment, calling for advanced technologies to remove plastic waste. Here we review enzymes that degrade plastics with focus on plastic properties, protein engineering and polymers such as poly(ethylene terephthalate), poly(butylene adipate-co-terephthalate), poly(lactic acid), polyamide and polyurethane. The mechanism of action of natural and engineered enzymes has been probed by experimental and computation approaches. The performance of polyester-degrading enzymes has been improved via directed evolution, structure-guided rational design and machine learning-aided strategies. The improved enzymes display higher stability at elevated temperatures, and tailored substrate-binding sites.

Tannic Acid Impedes the Proliferation of Bladder Cancer Cells by Elevating Mitochondrial Pathways of Apoptosis - Chi-Cheng Li; Bruce Chi-Kang Tsai; Selvaraj Annseles Rajula; Chiung-Hung Hsu; Ming-Cheng Chen; Chia-Hua Kuo; Chung-Min Yeh; Dennis Jine-Yuan Hsieh; Wei-Wen Kuo; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2024)

An emerging pathogen found in farm-cultured fourfinger threadfin (Eleutheronema tetradactylum), Edwardsiella piscicida, its genetic profile, virulent genes, and pathogenicity - Li-Wu Cheng; Hsien-Chung Lee; Qiong-Yi Huang; Wen-Rou Huang; Pei-Chi Wang; Shih-Chu Chen (Aquaculture, 2024)

Integrating metagenomic and isolation strategies revealed high contamination of pathogenies and resistome in market shrimps - Lianwei Ye; Zhiwei Zheng; Yaling Wang; Qiao Hu; Liang Zhong; Heng Heng; Zhihao Guo; Runsheng Li; Edward Wai Chi Chan; Sheng Chen (Science of The Total Environment, 2024)

Polyphenol nanoparticles based on bioresponse for the delivery of anthocyanins - Zhihuan Zang; Yuan Li; Shurui Chou; Jinlong Tian; Xu Si; Yuehua Wang; Hui Tan; Ningxuan Gao; Chi Shu; Dongnan Li; Wei Chen; Yi Chen; et al. (Food Research International, 2024)

Wave-induced residual response and liquefaction of a nonhomogeneous layered seabed - Titi Sui; Musheng Yang; Li Peng; Jiandong Chen; Chi Zhang; Jinhai Zheng (Frontiers in Marine Science, 2024)
Numerical studies were conducted on the wave-induced residual liquefaction of a silt–coarse sand layered seabed. Fully dynamic soil equations and residual seabed response equations were incorporated into the development of a numerical model. The numerical results were compared with theoretical solutions and experimental data from previous studies. Relatively good agreement was found in this comparison, validating the reliability of the proposed numerical model. The present model was applied to systematically investigate the wave-induced residual response with a silt–coarse sand layered seabed. The effects of coverage thickness, permeability, Young’s modulus in the upper silt layer on the residual response of the seabed were carefully examined. Numerical simulations indicate that the potential liquefaction is prone to occur with low permeability of the upper silt layer and shallower water depth, and the effect of coverage thickness of the silt layer on pore pressure and liquefaction potential is determined by shear stress ratio ( χ ) and effective normalized spreading parameter ( S e ) which represent the “generation power” and “dissipation potential” for residual pore pressure. The performance of the pore pressure and liquefaction in the layered seabed is the result of a trade-off between two non-dimensional parameters.

Automated segmentation of individual leafy potato stems after canopy consolidation using YOLOv8x with spatial and spectral features for UAV-based dense crop identification - Hanhui Jiang; Bryan Gilbert Murengami; Liguo Jiang; Chi Chen; Ciaran Johnson; Fernando Auat Cheein; Spyros Fountas; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

Silica from rice husk for sludge-based biochar modification: As a novel adsorbent for lead - Yuanping Li; Mengyang Zhao; Haoqin Yan; Yaoning Chen; Yihuan Liu; Hongjuan Jiang; Li Chen; Suzhen Hou; Nianping Chi; Shunyao Jia (Journal of Water Process Engineering, 2024)

Treatment of mature landfill leachate using chemical and electrical Fenton with novel Fe-loaded GAC heterogeneous catalysts - Yuting Guo; Shuangyu Wang; Chen Chi; Yanqiu Wang; Xinyu Gao; Peipei Li; Yixian Wang; Chuncheng Wan; Shiyong Wu (Journal of Water Process Engineering, 2024)

Enhanced fluid mixing using a novel multi-stage static pipeline mixer: Numerical simulation and mechanism analysis - Jiaheng Zhao; Xing Li; Zedong Lu; Wenjun Chi; Zhibin Wang; Yawei Chen (Journal of Water Process Engineering, 2024)

Treatment of membrane-concentrated landfill leachate by heterogeneous chemical and electrical Fenton processes with Iron-loaded granular activated carbon catalysts - Peipei Li; Zishan Yin; Chen Chi; Yanqiu Wang; Yixian Wang; Hong Liu; Yanli Lv; Nan Jiang; Shiyong Wu (Journal of Environmental Chemical Engineering, 2024)

Effects of zero-valent iron added in the flooding or drainage process on cadmium immobilization in an acid paddy soil - Hanbing Meng; Shiwen Hu; Zebin Hong; Wenting Chi; Guojun Chen; Kuan Cheng; Qi Wang; Tongxu Liu; Fangbai Li; Kexue Liu; Yang Yang (Journal of Environmental Sciences, 2024)

Metagenomics and untargeted metabolomics analyses to unravel the formation mechanism of characteristic metabolites in Cantonese soy sauce during different fermentation stages - Linfeng Wen; Jianping Lei; Lixin Yang; Qixin Kan; Peipei Wang; Jun Li; Cong Chen; Liping He; Jiangyan Fu; Chi-Tang Ho; Qingrong Huang; Yong Cao. (Food Research International, 2024)

Effect of sowing date on radiation and temperature use efficiencies of rice in the low-light region of China - Xiaofan Huang; Fei Deng; Chi Zhang; Qiuping Li; Yuxin He; Chenyan He; Xiaofeng Ai; Yujie Yuan; Li Wang; Hong Cheng; Tao Wang; Youfeng Tao; et al. (Field Crops Research, 2024)

Single-cell transcriptomic analysis reveals genome evolution in predatory litostomatean ciliates - Zhaorui Zhou; Chao Li; Qingxiang Yuan; Yong Chi; Yuqing Li; Ying Yan; Saleh A. Al-Farraj; Naomi A. Stover; Zigui Chen; Xiao Chen (European Journal of Protistology, 2024)

Histone H3K36me3 mediates the genomic instability of Benzo[a]pyrene in human bronchial epithelial cells - Shen Chen; Zhengbao Zhang; Honghao Peng; Shuyun Jiang; Chi Xu; Xingyu Ma; Liying Zhang; Hao Zhou; Xiumei Xing; Liping Chen; Qing Wang; Wen Chen; et al. (Environmental Pollution, 2024)

The angiogenesis-modulating effects of coumarin-derivatives - Han-Ting Huang; Ching-Yuan Huang; Chih-Jou Lee; Bo-Jie Sun; Zong-Wei Jhang; Chi-Chung Wen; Yun-Hsin Wang; Tao-Sheng Li; Ching-Yuh Chern; Yau-Hung Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Improving impact of heparan sulfate on the endothelial glycocalyx abnormalities in atherosclerosis as revealed by glycan-protein interactome - Qingqing Chen; Xiaohui Xu; Shaoshuai Xie; Anran Sheng; Naihan Han; Zhenyu Tian; Xiaowei Wang; Fuchuan Li; Robert J. Linhardt; Fuming Zhang; Lan Jin; Qunye Zhang; et al. (Carbohydrate Polymers, 2024)

Accelerating flow simulations in the built environment by using the fast fluid dynamics initializer - Chi Zhang; Chih-Yung Wen; Yu-Hsuan Juan; Yee-Ting Lee; Zhengwei Chen; An-Shik Yang; Zhengtong Li (Building and Environment, 2024)

Investigation on the budget of peroxyacetyl nitrate (PAN) in the Yangtze River Delta: Unravelling local photochemistry and regional impact - Tao Xu; Wei Nie; Zheng Xu; Chao Yan; Yuliang Liu; Qiaozhi Zha; Ruoxian Wang; Yuanyuan Li; Lei Wang; Dafeng Ge; Liangduo Chen; Ximeng Qi; et al. (Science of The Total Environment, 2024)

Predicting air pollutant emissions of the foundry industry: Based on the electricity big data - Xiangyu Chi; Zheng Li; Hanqing Liu; Jianhua Chen; Jian Gao (Science of The Total Environment, 2024)

Ecotoxicity of tire wear particles to antioxidant enzyme system and metabolic functional activity of river biofilms: The strengthening role after incubation-aging in migrating water phases - Kun Li; Wanqi Hao; Chi Liu; Zhangle Chen; Zidong Ye (Science of The Total Environment, 2024)

Experimental investigation of the impacts of supercritical carbon dioxide on acid-etching fracture morphology and conductivity in tight carbonate reservoir - Bo Gou; Xiao Li; Jianchun Guo; Chao Liu; Chi Chen; Chencheng Guan (Fuel, 2024)

Individual and combined effects of earthworms and Sphingobacterium sp. on soil organic C, N forms and enzyme activities in non-contaminated and Cd-contaminated soil - Li Jia; Qing Liu; Siyi Chen; Kexue Liu; Yiqing Chen; Mikael Motelica-Heino; Hesen Zhong; Menghao Zhang; Cevin Tibihenda; Patrick Lavelle; Jun Dai; Chi Zhang (European Journal of Soil Biology, 2024)

Ecotoxicity of three typical tire wear particles to periphytic biofilms: The potentiating role after natural water-incubation-aging - Kun Li; Wanqi Hao; Han Su; Chi Liu; Zhangle Chen; Zidong Ye (Environmental Pollution, 2024)

Hydrodynamic modeling study of nature-based hybrid coastal defense strategy applied in salt marsh restoration - Zhipeng Chen; Feng Luo; Guanghuai Zhou; Fei Zhu; Hongbo Wu; Ruijie Li; Chi Zhang (Estuarine, Coastal and Shelf Science, 2024)

Oxidation state of copper species rather than ammonium nitrate decomposition determines the N2O generation during NO reduction with NH3 on Cu-AEI catalyst - Qin Wu; Jianjun Chen; Chi Fan; Jinxing Mi; Xiangyou Kong; Guimin Wang; Li Cai; Junhua Li; Tao Li (Chemical Engineering Journal, 2024)

Nocardiosis and other common diseases of cultured golden pompano ( Trachinotus blochii ) in Taiwan - Wei‐Xiao Yan; Yu‐Han Tseng; Wen‐Rou Huang; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Golden pompano ( Trachinotus blochii ) is a carnivorous teleost cultured in the Asia‐Pacific region. Fish culture in high densities and numbers results in disease outbreaks, causing huge economic losses. Here, we collected cultured golden pompanos from 2021 to 2022 and identified the pathogens isolated from the diseased fish. Out of a total of 64 clinical cases observed in both sea cages and fish ponds, it was found that Nocardia seriolae was the predominant pathogen (26%), followed by Lactococcus garvieae (13%). Trichodina spp. was the most prevalent parasite in sea cages and earthen ponds (21%), while Neobenedenia spp. was the primary parasitic pathogen (16%) in sea cages. Given these findings, further investigations were conducted, including antibiotic susceptibility and pathogenicity tests specific to N. seriolae in golden pompanos. Antibiotic susceptibility tests of N. seriolae revealed that all strains were susceptible to doxycycline, oxytetracycline, florfenicol and erythromycin but resistant to amoxicillin and ampicillin. Additionally, a pathogenicity assessment was carried out by administering an intraperitoneal injection of 0.1 mL containing 10 7 CFU of N. seriolae per fish. The mortality rates observed varied between 40% and 90%, with the P2 strain exhibiting the highest level of virulence, resulting in a cumulative mortality of 90%. Therefore, disease outbreaks in fish can be minimized by developing effective treatments and prevention methods.

Genetic improvement of oysters: Current status, challenges, and prospects - Kunyin Jiang; Chen Chen; Gaowei Jiang; Yong Chi; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Reviews in Aquaculture, 2024)
Oysters are one of the most commercially important shellfish species and have been cultured for thousands of years. Oyster aquaculture supports the major aquaculture industries in many countries. Over the last few decades, the oyster breeding and aquaculture industries have developed rapidly to meet the continually growing demand. Many researchers have made significant efforts toward the genetic improvement of commercially important traits in oysters. Some strains with fast‐growing, disease‐resistant, and stable shell‐colours have been developed through selective breeding. Some hybrid varieties have been developed by crossing different geographical populations or cultivated strains. Several hybrids exhibit considerable genetic variation and improved productive performance. Additionally, polyploid induction technologies have been applied in the oyster aquaculture industry, which provides a useful tool for performance improvement and genetic containment of cultured stocks. At present, the development of molecular breeding also provides a great opportunity for oyster genetic improvement. These advances in oyster breeding have improved the quality of oysters, brought great economic benefits, and been conducive to the sustainability of oyster production. Nonetheless, there are still some limitations and obstacles in oyster breeding, such as infectious diseases, summer mortality, conservation of germplasm resources, environmental contamination, and climate change. The present review provides an overview of the current status, challenges, and prospects in oyster breeding.

Rapid start-up of an innovative pilot-scale staged PN/A continuous process for enhanced nitrogen removal from mature landfill leachate via robust NOB elimination and efficient biomass retention - Cancan Jiang; Liang Zhang; Yongzhi Chi; Shengjun Xu; Yawen Xie; Dongmin Yang; Yunzhi Qian; Fuqiang Chen; Weijun Zhang; Dongsheng Wang; Zhe Tian; Shujun Zhang; et al. (Water Research, 2024)

Toxic effects of the heavy metal Cd on Apis cerana cerana (Hymenoptera: Apidae): Oxidative stress, immune disorders and disturbance of gut microbiota - Zhongyu Li; Dezheng Guo; Chen Wang; Xuepeng Chi; Zhenguo Liu; Ying Wang; Hongfang Wang; Xingqi Guo; Ningxin Wang; Baohua Xu; Zheng Gao (Science of The Total Environment, 2024)

Rational design of a cross-type HPV vaccine through immunodominance shift guided by a cross-neutralizing antibody - Zhiping Wang; Daning Wang; Jie Chen; Fei Gao; Yanan Jiang; Chengyu Yang; Ciying Qian; Xin Chi; Shuyue Zhang; Yujie Xu; Yihan Lu; Jingjia Shen; et al. (Science Bulletin, 2024)

Mussel-inspired modification of 2D MoS2 to construct a hybrid nanocomposite membrane with enhanced pervaporation dehydration of isopropanol - Marwin R. Gallardo; Jyun-Xiang Ciou; Chen-Hsiu Wang; Micah Belle Marie Yap Ang; Jeremiah C. Millare; Chi-Lan Li; Hui-An Tsai; Shu-Hsien Huang; Kueir-Rarn Lee (Journal of Environmental Chemical Engineering, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Zwitterion grafted polyimide separator for improving lithium-ion transport and its application in LiCoO2 batteries - Haitao Huang; Kaijin Chen; Chuying Li; Zhuxin Zhou; Wenhui Wang; Bo Deng; Siwei Liu; Chao Qian; Min Yue; Zhenguo Chi; Jiarui Xu; Yi Zhang (Chemical Engineering Journal, 2024)

Complete decomposition of poly(ethylene terephthalate) by crude PET hydrolytic enzyme produced in Pichia pastoris - Chun-Chi Chen; Xian Li; Jian Min; Ziyin Zeng; Zhiyuan Ning; Hailin He; Xin Long; Du Niu; Rouming Peng; Xin Liu; Yu Yang; Jian-Wen Huang; et al. (Chemical Engineering Journal, 2024)

Unravelling molecular fractionation of dissolved organic matter on ferrihydrite-phosphate complexes - Yanan Ou; Jialin Chi; Fangbai Li; Qing Chen; Liping Fang (Chemical Geology, 2024)

A proposed framework for a social-ecological traits database for studying and managing urban plants and assessing the potential of database development using Floras - Chi-Ru Chang; Mong-Huai Su; Yi-Hsuan Li; Ming-Chun Chen (Urban Forestry & Urban Greening, 2024)

Cooperative roles of phosphate and dissolved organic matter in inhibiting ferrihydrite transformation and their distinct fates - Jialin Chi; Yanan Ou; Fangbai Li; Wenjun Zhang; Hang Zhai; Tongxu Liu; Qing Chen; Xiaoxia Zhou; Liping Fang (Science of The Total Environment, 2024)

Conjugative plasmids facilitate the transmission of tmexCD2-toprJ2 among carbapenem-resistant Klebsiella pneumoniae - Hong Yao; Tingting Zhang; Kai Peng; Junke Peng; Xu Liu; Ziwei Xia; Leizi Chi; Xiaoyu Zhao; Shihong Li; Sheng Chen; Shangshang Qin; Ruichao Li (Science of The Total Environment, 2024)

Identification and analysis of microplastics in human lower limb joints - Zhuo Li; Yifan Zheng; Zulipikaer Maimaiti; Jun Fu; Fan Yang; Zhi-Yuan Li; Yanli Shi; Li-Bo Hao; Ji-Ying Chen; Chi Xu (Journal of Hazardous Materials, 2024)

The spatiotemporal patterns and climate impacts of the carbon dynamics in economically developed areas of China during the past 40 years: A case of Jiangsu Province - Shihua Zhu; Chi Zhang; Xia Fang; Yan Yan; Xin Hang; Yan Chen; Liangxiao Sun; Xiaoping Xie; Yachun Li (Journal of Cleaner Production, 2024)

Adaptation behaviors modify the effects of body fat on heat-related symptoms among Taiwanese elderly - Chi-Hsien Chen; Wen-Yi Lin; Kang-Yun Lee; Wen-Jung Sun; Li-Ying Huang; Yue-Liang Leon Guo (International Journal of Hygiene and Environmental Health, 2024)

Ammonium intercalation engineering regulated structural stability of V6O13 cathodes for durable zinc ion batteries - Ziang Wu; Jia Yao; Chi Chen; Xiang Chen; Xiaoxin Pan; Junjie Zheng; Yi Gan; Jingying Li; Xingtai Liu; Chao Xia; Lin Lv; Hao Wang; et al. (Chemical Engineering Journal, 2024)

In situ self-reconstructed nanoparticle-coated cathode and anode by nitric acid etching for symmetric solid oxide fuel cells - Xuzhuo Sun; Yunyun Xia; Bo Wang; Bo Li; Lushan Ma; Jing Chen; Bo Chi (Chemical Engineering Journal, 2024)

Blue polyimides for high-performance solution-processable organic light-emitting diodes - Wenhui Wang; Kaijin Chen; Chuying Li; Faxu Lin; Yuxuan Li; Yubo Long; Juan Zhao; Siwei Liu; Zhenguo Chi; Jiarui Xu; Yi Zhang; Yuguang Ma (Chemical Engineering Journal, 2024)

Combined metabolome and transcriptome analysis reveals a critical role of lignin biosynthesis and lignification in stem-like pneumatophore development of the mangrove Avicennia marina - Yu-Chen Zhang; Li-Han Zhuang; Jia-Jie Zhou; Shi-Wei Song; Jing Li; He-Zi Huang; Bing-Jie Chi; You-Hui Zhong; Jing-Wen Liu; Hai-Lei Zheng; Xue-Yi Zhu (Planta, 2024)

The responses of soil Cd fractions to disinfestation regimes associated with microbial communities - Xin Li; Yu Tao; Fang Chen; Fangjun Tan; Chi Zhou; Jie Chen; Tao Xue; Yunhe Xie (Applied Soil Ecology, 2024)

Co-metabolic biodegradation of chlorinated ethene in an oxygen- and ethane-based membrane biofilm reactor - Zifang Chi; Xinyang Liu; Huai Li; Shen Liang; Yi-Hao Luo; Chen Zhou; Bruce E. Rittmann (Science of The Total Environment, 2023)

Ingestion and biodegradation of disposable surgical masks by yellow mealworms Tenebrio molitor larvae: Differences in mask layers and effects on the larval gut microbiome - Jiaming Wang; Chi Zhang; Xin Zhao; Yue Weng; Xinrui Nan; Xiaoyu Han; Chen Li; Baoqin Liu (Science of The Total Environment, 2023)

Vertical distribution and characteristics of soil microplastics under different land use patterns: A case study of Shouguang City, China - Jizhi Li; Bin Zhu; Bin Huang; Jian Ma; Caiyan Lu; Guangyu Chi; Wei Guo; Xin Chen (Science of The Total Environment, 2023)

Prevalence and genetic basis of tetracycline resistance in Vibrio parahaemolyticus isolates recovered from food products in Shenzhen, China during 2013 to 2021 - Lianwei Ye; Zhiwei Zheng; Yating Xu; Chen Yang; Heng Heng; Fuyong Li; Edward Wai Chi Chan; Sheng Chen (Science of The Total Environment, 2023)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Vineyard soil heterogeneity and harvest date affect volatolomics and sensory attributes of Cabernet Sauvignon wines on a meso-terroir scale - Hao-Cheng Lu; Meng-Bo Tian; Xiao Han; Ning Shi; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Research International, 2023)

Molecular characterization of spoilage microbiota in high CO2 refrigerated large yellow croaker (Larimichthys crocea) fillets using metagenomic and metabolomic approaches - Qi Yan; Meijie Guo; Bohan Chen; Chi Zhang; Dapeng Li; Jing Xie (Food Bioscience, 2023)

Lactobacillus gasseri relieves diarrhea caused by enterotoxin-producing Escherichia coli through inflammation modulation and gut microbiota regulation - Chi Chen; Yue Yue; Zhujun He; Bowen Li; Jianxin Zhao; Wei Chen; Bo Yang (Food Bioscience, 2023)

Dysregulation of immunity by cigarette smoking promotes inflammation and cancer: A review - Yubin Liu; Lan Lu; Huan Yang; Xu Wu; Xinyue Luo; Jing Shen; Zhangang Xiao; Yueshui Zhao; Fukuan Du; Yu Chen; Shuai Deng; Chi Hin Cho; et al. (Environmental Pollution, 2023)

Compositionally complex doping for low-V Ti-Cr-V hydrogen storage alloys - Yongyang Zhu; Xubo Li; Xu-Sheng Yang; Pengyun Chen; Gary Chi-Pong Tsui; Zheng-Long Xu; Renheng Tang; Fangming Xiao; Kangcheung Chan (Chemical Engineering Journal, 2023)

Preparation of porous chitin beads from waste crayfish shell and application in the co-immobilization of PLP and its dependent enzyme - Guoguang Wei; Chi Zhang; Ning Zhou; Bin Wu; Hui Li; Alei Zhang; Pingkai Ouyang; Kequan Chen (Carbohydrate Polymers, 2023)

Improving extraction phenology accuracy using SIF coupled with the vegetation index and mapping the spatiotemporal pattern of bamboo forest phenology - Yanxin Xu; Xuejian Li; Huaqiang Du; Fangjie Mao; Guomo Zhou; Zihao Huang; Weiliang Fan; Qi Chen; Chi Ni; Keruo Guo (Remote Sensing of Environment, 2023)

Investigations on the shallow water wave attenuation over continuous porous oyster reef-like structure - Yunhan Yang; Titi Sui; Guangsheng Wang; Chi Zhang; Peixiong Chen; Yuan Li; Jian Zeng; Richard Aidoo (Ocean Engineering, 2023)

Strategies analysis for improving SWAT model accuracy and representativeness of calibrated parameters in sediment simulation for various land use and climate conditions - Li-Chi Chiang; Pin-Chih Shih; Chih-Mei Lu; Bing-Chen Jhong (Journal of Hydrology, 2023)

The effectiveness of sewage sludge biochar amendment with Boehmeria nivea L. in improving physicochemical properties and rehabilitating microbial communities in mine tailings - Mengyao Li; Xiaoting Chen; Chiyu Chen; Lige Huang; Haochun Chi; Nan Zhao; Bofang Yan; Yuanqing Chao; Yetao Tang; Rongliang Qiu; Shizhong Wang (Journal of Environmental Management, 2023)

Dose-response formation of N7-(3-benzo[1,3]dioxol-5-yl-2-hydroxypropyl)guanine in liver and urine correlates with micronucleated reticulocyte frequencies in mice administered safrole oxide - Kuen-Yuh Wu; Yu-Tzu Wei; Yu-Syuan Luo; Li-Chin Shen; Bao-Suei Chang; Ya-Yin Chen; Yan-Chi Huang; Hui-Fen Huang; Wen-Sheng Chung; Su-Yin Chiang (Food and Chemical Toxicology, 2023)

High-performance nitrogen-doped porous carbon electrode materials for capacitive deionization of Industrial salt-contaminated wastewater - Chunyu Chen; An Liu; Chi Fei; Bin Hui; Yingying Li; Deng Guan; Dianchun Ju (Desalination, 2023)

Primary open-angle glaucoma risk prediction with ABCA1 and LOC102723944 variants and their genotype–phenotype correlations in southern Chinese population - Zhenggen Wu; Chukai Huang; Yuqian Zheng; Xiang-Ling Yuan; Shaowan Chen; Yanxuan Xu; Li Jia Chen; Chi Pui Pang; Mingzhi Zhang; Tsz Kin Ng (Molecular Genetics and Genomics, 2023)

Pathogenicity characterization of nocardiosis in orange‐spotted grouper ( Epinephelus coioides ) via exposure to nine distinct isolates of Nocardia seriolae and four administrative routes - Phuong Nguyen; Andre Giovanni; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2023)
Nocardia seriolae causes chronic nocardiosis in various marine and freshwater aquatic animals; however, grouper species have rarely been investigated. This study evaluated the pathogenicity of nocardiosis following N. seriolae infection in the orange‐spotted grouper Epinephelus coioides . Nine identified genetic isolates of N. seriolae were tested in vivo using the intraperitoneal method and observed daily for 35 days. The most virulent isolate was then used to evaluate transmission through different routes (intraperitoneal IP, intramuscular IM, oral OR, and immersion IS) in the same fish model and was observed daily for 42 days. The results showed mild variation in virulence among N. seriolae isolates. AOD107132‐2 K and OT103003‐N11 strains displayed the highest and lowest risk virulence, respectively, based on the accumulation and kinetics of mortality. IM and IP administrations showed an early phase response with early mortality by 5 dpc (30%–100%), while slower kinetics of nocardiosis occurred in the OR and IS routes with slow mortality at 35 dpc (4%–8%). Histopathology revealed typical granulomas, confirming the progression of nocardiosis in the diseased fish. These results provide the basis for further studies on the virulence profile of N. seriolae in Taiwan and a well‐suited route of administration in orange‐spotted groupers for further prevention development.

Aging rice straw reduces the bioavailability of mercury and methylmercury in paddy soil - Yubo He; Xu Yang; Zihao Li; Tantan Wang; Chi Ma; Xin Wen; Wenhao Chen; Chang Zhang (Chemosphere, 2023)

A novel design for a dust-induced closed return mars wind tunnel - Lifang Li; Yun Chen; Songmei Hu; Congbin Chen; Guanxin Chi; Guopeng Sun; Pengzhen Guo (Planetary and Space Science, 2023)

Intelligent marine area supervision based on AIS and radar fusion - Wang Chi Ming; Li Yanan; Min Lanxi; Chen Jiuhu; Lin Zhong; Su Sunxin; Zhang Yuanchao; Chen Qianying; Chen Yugui; Duan Xiaoxue; Wei Jiayi; Zhu shunzhi (Ocean Engineering, 2023)

Hydroxyl modified nano calcium phosphate, a novel adsorbent for denitrogenation of fuel: Synthesis, characterization and adsorptive performance for quinoline - Peiji Yin; Yixuan Chen; Yu Wang; Yujing Chi; Bokai Li; Mingwei Xu; Haiyan Song; Chunxia Chen (Journal of Environmental Chemical Engineering, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

A pervasive phosphorylation cascade modulation of plant transcription factors in response to abiotic stress - Wang Baoxiang; Sun Zhiguang; Liu Yan; Xu Bo; Li Jingfang; Chi Ming; Xing Yungao; Yang Bo; Li Jian; Liu Jinbo; Chen Tingmu; Fang Zhaowei; et al. (Planta, 2023)

Accumulation, root-shoot translocation and phytotoxicity of substituted polycyclic aromatic hydrocarbons in wheat - Huiqiang Yang; Zhirui Zhu; Jian Zhou; Jinbo Liu; Jiping Chen; Aorui Li; Chi Wang; Chi Zhang; Yunchao Dai; Hanzhong Jia (Environmental Chemistry Letters, 2023)

Biological carbon pump responses to multiscale physical processes: a review of sediment trap studies in the South China Sea - Jingjing Zhang; Hongliang Li; Martin G. Wiesner; Lihua Ran; Xingju He; Guangxi Chi; Xinyang Wang; Jinping Yu; Jianfang Chen (Frontiers in Marine Science, 2023)
Accurately assessing the capacity of the modern ocean to photosynthetically fix and sequester atmospheric CO 2 , termed the biological carbon pump (BCP), is a key component in studies on the marine carbon cycle and the global climate system. Particulate organic carbon (POC) flux into the ocean interior is an important indicator of the BCP strength, and it can be directly measured by sediment traps on time scales from days to years. This study has been conducted in the South China Sea (SCS) for over three decades. The SCS is one of the largest tropical marginal seas, located in the Asian monsoon region with frequent occurrence of dynamic physical processes and anthropogenic perturbations. It hosts an ideal natural laboratory to investigate the response of the BCP to multiscale physical processes. In this mini review, we briefly introduce the study history of mooring sediment traps in the SCS, synthesize the processes that regulate the temporal variability in mesopelagic POC flux, and how it is sensitive to climate changes. The time-series characteristics of the POC flux are clearly linked to primary production, as well as the key physical processes in the upper layer. The seasonal East Asian monsoon, intraseasonal eddies, aerosol deposition and interannual El Niño Southern Oscillation (ENSO) events are the main controlling factors over weekly to yearly timescales. Together, they suggest that the multiscale physical forcing in the upper layer regulates the mesopelagic POC export flux by controlling nutrient supplementation and subsequent POC production.

Course-, dose-, and stage-dependent toxic effects of prenatal acetaminophen exposure on fetal long bone development - Chi Ma; Xufeng Li; Hao Xiao; Bin Li; Hanwen Gu; Yu Guo; Hui Wang; Yinxian Wen; Liaobin Chen (Toxicology Letters, 2023)

The fate of photoreduction of Hg(II) in aqueous solution by aged microplastic particles and their leached DOM - Xu Yang; Chi Ma; Zihao Li; Tantan Wang; Xin Wen; Yubo He; Wenhao Chen; Xiaohong Shi; Chang Zhang (Science of The Total Environment, 2023)

Duplicated paralog of sulfide: quinone oxidoreductase contributes to the adaptation to hydrogen sulfide-rich environment in the hydrothermal vent crab, Xenograpsus testudinatus - Chi Chen; Guan-Chung Wu; Yao-Tse Chung; Hau-Wen Li; Pei-Hsuan Chou; Yung-Che Tseng; Chieh-Jhen Chen; Sylvie Dufour; Ching-Fong Chang (Science of The Total Environment, 2023)

A small extent of seawater intrusion significantly enhanced Cd uptake by rice in coastal paddy fields - Wenting Chi; Guojun Chen; Shiwen Hu; Xiaomin Li; Kuan Cheng; Qi Wang; Bingqing Xia; Yang Yang; Yibing Ma; Tongxu Liu (Journal of Hazardous Materials, 2023)

Cryo-EM structure and rational engineering of a superefficient ochratoxin A-detoxifying amidohydrolase - Longhai Dai; Du Niu; Jian-Wen Huang; Xian Li; Panpan Shen; Hao Li; Zhenzhen Xie; Jian Min; Yumei Hu; Yu Yang; Rey-Ting Guo; Chun-Chi Chen (Journal of Hazardous Materials, 2023)

MeHg production in eutrophic lakes: Focusing on the roles of algal organic matter and iron-sulfur-phosphorus dynamics - Tantan Wang; Xu Yang; Zihao Li; Wenhao Chen; Xin Wen; Yubo He; Chi Ma; Zhongzhu Yang; Chang Zhang (Journal of Hazardous Materials, 2023)

Phosphorylation and acetylation responses of glycolytic enzymes in meat to different chilling rates - Yuqiang Bai; Chi Ren; Chengli Hou; Li Chen; Zhenyu Wang; Xin Li; Dequan Zhang (Food Chemistry, 2023)

Molecular design strategy for through-space charge transfer blue polyimides with rigid non-conjugated backbone and the role of alicyclic imide linker - Yubo Long; Kaijin Chen; Chuying Li; Wenhui Wang; Jinkun Bian; Yuxuan Li; Siwei Liu; Zhenguo Chi; Jiarui Xu; Yi Zhang (Chemical Engineering Journal, 2023)

Understanding spontaneous biodiversity in informal urban green spaces: A local-landscape filtering framework with a test on wall plants - Xinyu Miao; Yuhan Pan; Hanxu Chen; Ming-Juan Zhang; Wensi Hu; Yuxiang Li; Ruoyu Wu; Peiyao Wang; Shubo Fang; Kechang Niu; Chi Xu; Shuqing N. Teng (Urban Forestry & Urban Greening, 2023)

Effects of currents on nonlinear wave transformation in a reef-lagoon-channel system - Shubin Chen; Yuan Li; Chi Zhang; Huimin Zhu; Qinyi Li; Jian Shi (Ocean Engineering, 2023)

Flavonoids mitigation of typical food thermal processing contaminants: Potential mechanisms and analytical strategies - Bin Li; Jiaxin Wang; Zhen Cheng; Baoge Song; Chi Shu; Yi Chen; Wei Chen; Shufang Yang; Yiyun Yang; Jinlong Tian (Food Chemistry, 2023)

The future for biochemical recycling of poly(ethylene terephthalate): From lab to process - Chun-Chi Chen; Xian Li; Panpan Shen; Yunyun Yang; Jian Min; Qi Zhang; Yingle Liu; Jian-Wen Huang; Rey-Ting Guo (Current Opinion in Green and Sustainable Chemistry, 2023)

Collaborative interfacial modification and surficial passivation for high-efficiency MA-free wide-bandgap perovskite solar cells - Yali Ou; Hao Huang; Hongxi Shi; Ziyu Li; Zhijia Chen; Muhammad Mateen; Zhangbo Lu; Dan Chi; Shihua Huang (Chemical Engineering Journal, 2023)

Rat Hair Metabolomics Analysis Reveals Perturbations of Unsaturated Fatty Acid Biosynthesis, Phenylalanine, and Arachidonic Acid Metabolism Pathways Are Associated with Amyloid-β-Induced Cognitive Deficits - Tian-Hoe Tan; Shih-Wen Li; Chih-Wei Chang; Yuan-Chih Chen; Yu-Hsuan Liu; Jui-Ti Ma; Ching-Ping Chang; Pao-Chi Liao (Molecular Neurobiology, 2023)
Hair is a noninvasive valuable biospecimen for the long-term assessment of endogenous metabolic disturbance. Whether the hair is suitable for identifying biomarkers of the Alzheimer’s disease (AD) process remains unknown. We aim to investigate the metabolism changes in hair after β-amyloid (Aβ 1-42 ) exposure in rats using ultra-high-performance liquid chromatography-high-resolution mass spectrometry–based untargeted and targeted methods. Thirty-five days after Aβ 1-42 induction, rats displayed significant cognitive deficits, and forty metabolites were changed, of which twenty belonged to three perturbed pathways: (1) phenylalanine metabolism and phenylalanine, tyrosine, and tryptophan biosynthesis— l -phenylalanine, phenylpyruvate, ortho-hydroxyphenylacetic acid, and phenyllactic acid are up-regulated; (2) arachidonic acid (ARA) metabolism—leukotriene B4 (LTB4), arachidonyl carnitine, and 5(S)-HPETE are upregulation, but ARA, 14,15-DiHETrE, 5(S)-HETE, and PGB2 are opposite; and (3) unsaturated fatty acid biosynthesis— eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), FA 18:3 + 1O, and FA 18:3 + 2O are downregulated. Linoleic acid metabolism belonging to the biosynthesis of unsaturated fatty acid includes the upregulation of 8-hydroxy-9,10-epoxystearic acid, 13-oxoODE, and FA 18:2 + 4O, and downregulation of 9(S)-HPODE and dihomo-γ-linolenic acid. In addition, cortisone and dehydroepiandrosterone belonging to steroid hormone biosynthesis are upregulated. These three perturbed metabolic pathways also correlate with cognitive impairment after Aβ 1-42 stimulation. Furthermore, ARA, DHA, EPA, l -phenylalanine, and cortisone have been previously implicated in the cerebrospinal fluid of AD patients and show a similar changing trend in Aβ 1-42 rats’ hair. These data suggest hair can be a useful biospecimen that well reflects the expression of non-polar molecules under Aβ 1-42 stimulation, and the five metabolites have the potential to serve as novel AD biomarkers.

Spawning characteristics of blue sprat (Spratelloides gracilis) in the waters of Penghu, central Taiwan Strait - Li Chi Cheng; Yang Chi Lan; Kuo Wei Lan; Jinn Shing Weng; Yu Kai Chen; Sheng Tai Hsiao; Yi Sui Wu; Jia Shin He; Hsing Han Huang; Yu Cih Huang; Hung An Cheng (Frontiers in Marine Science, 2023)
Blue sprat ( Spratelloides gracilis ) is an economically valuable species that inhabits the central Taiwan Strait. However, despite the implementation of a local management scheme involving a closed season between 1 May and 1 June, the annual catch has rapidly decreased over the decades. Thus, the efficacy of the implemented regulations must be investigated. This study sought to clarify the reproductive biology, spawning ground, and behavior of this species in the waters of Penghu. In total, 6,549 specimens were collected between March 2021 and September 2022. Considering gonadosomatic index, group maturity, and oocyte diameter, we found that the spawning season (March–September) peaked in April; new cohorts were distinctly recruited after the spawning peak. The distribution of the spawning ground (latitude, 23°41′N to 23°43′N; longitude, 119°32′E to 119°39′E) was determined by considering the fishing area of mature females and DNA analysis of adhered eggs. We further noted shoals of fish darting in the bottom water without clear schooling movement, females’ abdomen frequently contacting substrata for eggs able to attach on during oviposition, and males releasing sperms making water milky white; these indicate that S. gracilis exhibits promiscuous spawning behavior. Our findings may facilitate the management and conservation of S. gracilis in this region.

Therapeutic effects of green tea on endometriosis - Xiaoyan Chen; Gene Chi Wai Man; Sze Wan Hung; Tao Zhang; Linda Wen Ying Fung; Chun Wai Cheung; Jacqueline Pui Wah Chung; Tin Chiu Li; Chi Chiu Wang (Critical Reviews in Food Science and Nutrition, 2023)

Advanced porous nanomaterials as superior adsorbents for environmental pollutants removal from aqueous solutions - Xiaolu Liu; Yang Li; Zhongshan Chen; Hui Yang; Yawen Cai; Suhua Wang; Jianrong Chen; Baowei Hu; Qifei Huang; Chi Shen; Xiangke Wang (Critical Reviews in Environmental Science and Technology, 2023)

α-amanitin induces autophagy through AMPK-mTOR-ULK1 signaling pathway in hepatocytes - Yue Xu; Shangwen Wang; Chi-Kwan Leung; Hao Chen; Chan Wang; Huijie Zhang; Shuwei Zhang; Yi Tan; Haowei Wang; Lin Miao; Yi Li; Yizhen Huang; et al. (Toxicology Letters, 2023)

Biodegradable, transparent, and antibacterial alginate-based triboelectric nanogenerator for energy harvesting and tactile sensing - Yunmeng Li; Shoue Chen; Hao Yan; Haowen Jiang; Jianjun Luo; Chi Zhang; Yaokun Pang; Yeqiang Tan (Chemical Engineering Journal, 2023)

Plasmon driven super-high HER activity of electronic structure and lattice strain engineered single atomic layer Pd@Au nanorods - Yi-Bai Sun; Miao Ni; Chen Chi; Dong-Rui Yang; Xue-Lu Chen; Qi Qi; Jian Li; Xing-Hua Xia (Chemical Engineering Journal, 2023)

Physical dual-network photothermal antibacterial multifunctional hydrogel adhesive for wound healing of drug-resistant bacterial infections synthesized from natural polysaccharides - Xuan Yue; Shiyi Zhao; Mengyu Qiu; Junbo Zhang; Guofeng Zhong; Chi Huang; Xuebo Li; Chen Zhang; Yan Qu (Carbohydrate Polymers, 2023)

Contribution of the Chinese Meridian Project to space environment research: Highlights and perspectives - Chi Wang; Jiyao Xu; Libo Liu; Xianghui Xue; Qinghe Zhang; Yongqiang Hao; Gang Chen; Hui Li; Guozhu Li; Bingxian Luo; Yajun Zhu; Jiangyan Wang (Science China Earth Sciences, 2023)
The Chinese Meridian Project (CMP) is devoted to establishing a comprehensive ground-based monitoring network for China’s space weather research. CMP is a major national science and technology infrastructure project with the participation of more than 10 research institutions and universities led by the National Space Science Center of the Chinese Academy of Sciences. CMP is planned to be constructed in two phases: CMP phases I and II. The first phase (CMP-I) started construction in 2008 and completed in 2012, after which it entered the operation stage. The 10-year observation of CMP-I has made significant scientific discoveries and achievements in the research fields of the middle and upper atmospheric fluctuations, metal layers in the mesosphere and lower thermosphere, ionospheric disturbances and irregularities, geomagnetic disturbances, and influences of solar activity. The review summarizes the main observations and research achievements, space weather forecast modeling and methods based on CMP-I over the past 10 years, and presents a future extension perspective along with the construction of CMP-II.

Analysis of wave shoaling and shore-breakers on a low tide terrace beach based on in-situ measurements at Xisha Bay on South China coast - Yuan Li; Chi Zhang; Hongshuai Qi; Jiacheng Song; Weiqi Dai; Shanhang Chi; Jian Shi; Dake Chen (Acta Oceanologica Sinica, 2023)

Quality of life and cost-effectiveness of different breast cancer surgery procedures: a Markov decision tree-based approach in the framework of Predictive, Preventive, and Personalized Medicine - Hon-Yi Shi; Chiu-Hui Li; Yen-Chen Chen; Chong-Chi Chiu; Hao-Hsien Lee; Ming-Feng Hou (EPMA Journal, 2023)

Photoreduction of Hg(II) by typical dissolved organic matter in paddy environments - Xin Wen; Xu Yang; Tantan Wang; Zihao Li; Chi Ma; Wenhao Chen; Yubo He; Chang Zhang (Chemosphere, 2023)

Embryonic thermosensitivity and hatchling morphology differ among three species of crocodilians farm-raised in China - Dan Liu; Jia-Tian Chen; Jung-Chien Tsai; Cheng-Wang Li; Chi-Xian Lin; Yan-Fu Qu; Yu Du; Xiang Ji (Aquaculture, 2023)

Meta-analysis reveals cyanotoxins risk across African inland waters - Xu Zhao; Ying Liu; Yu-Ming Guo; Chi Xu; Liang Chen; Geoffrey A. Codd; Jun Chen; Ying Wang; Pu-Ze Wang; Li-Wei Yang; Long Zhou; Yan Li; et al. (Journal of Hazardous Materials, 2023)

Constructing γ-MnO2 with abundant oxygen vacancies by a chelating agent-assistant strategy to achieve high-efficient conversion of NO to NO2 - Lei Chen; Xiaoke Hou; Jinping Zhang; Chen Zhang; Chao Li; Zaoxiao Zhang; Li Tian; Guowei Guan; Zhenyu Zhang; Renyi Shi; Chi He (Chemical Engineering Journal, 2023)

Recent development of sustainable self-healable electronic skin applications, a review with insight - Jean-Sébastien Benas; Fang-Cheng Liang; Manikandan Venkatesan; Zhen-Li Yan; Wei-Cheng Chen; Su-Ting Han; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2023)

Identification of Rhodosorus marinus isolated in Taiwan and study on its optimum culture conditions - Wei Qing Chloe Lung; Jane Wungen-Sani; Chi-Cheng Huang; Chien-Li Chen; Hung-Chih Lai; Yeh-Fang Hu; Po-Tsang Lee; Fan-Hua Nan; Han-Yang Yeh; Meng-Chou Lee (Journal of Applied Phycology, 2023)

Dynamic risk analysis of oil depot storage tank failure using a fuzzy Bayesian network model - Qing-Yun Zhou; Bei Li; Yi Lu; Jie Chen; Chi-Min Shu; Ming-shu Bi (Process Safety and Environmental Protection, 2023)

Analytical method for modal analysis of submerged electric motor stator - Xudong Li; Shihao Zhao; Yunpeng Gao; Jinhua Chen; Chi Zhang; Yilin Qu (Ocean Engineering, 2023)

Evolutionary and biogeographic implications of an Erycine snake (Serpentes, Erycidae, Eryx) from the Upper Miocene of the Linxia Basin, Gansu Province, China - Jingsong Shi; Qiang Li; Thomas A. Stidham; Chi Zhang; Qigao Jiangzuo; Mo Chen; Xijun Ni (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Long-term effects of phosphorus deficiency on one-stage partial nitrification-anammox system and recovery strategies - Liang Zhang; Zhe Tian; Yunzhi Qian; Fuqiang Chen; Yu-You Li; Xueke Wang; Cuilian Fu; Yongzhi Chi (Journal of Cleaner Production, 2023)

AFLI-Calib: Robust LiDAR-IMU extrinsic self-calibration based on adaptive frame length LiDAR odometry - Weitong Wu; Jianping Li; Chi Chen; Bisheng Yang; Xianghong Zou; Yandi Yang; Yuhang Xu; Ruofei Zhong; Ruibo Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Deficiency of RAB39B Activates ER Stress-Induced Pro-apoptotic Pathway and Causes Mitochondrial Dysfunction and Oxidative Stress in Dopaminergic Neurons by Impairing Autophagy and Upregulating α-Synuclein - Ching-Chi Chiu; Yi-Hsin Weng; Tu-Hsueh Yeh; Juu-Chin Lu; Wan-Shia Chen; Allen Han-Ren Li; Ying-Ling Chen; Kuo-Chen Wei; Hung-Li Wang (Molecular Neurobiology, 2023)

Degree of ontogenetic diet shift and trophic niche partitioning of Euphausia superba and Thysanoessa macrura are influenced by food availability - Zhipeng Pang; Xupeng Chi; Zhihui Song; Haibo Li; Yunyan Chen; Guang Yang (Journal of Oceanology and Limnology, 2023)

Cyanidin-3- O -glucoside and its phenolic metabolites ameliorate intestinal diseases via modulating intestinal mucosal immune system: potential mechanisms and therapeutic strategies - Zhen Cheng; Xu Si; Hui Tan; Zhihuan Zang; Jinlong Tian; Chi Shu; Xiyun Sun; Zhiying Li; Qiao Jiang; Xianjun Meng; Yi Chen; Bin Li; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Physicochemical and pozzolanic properties of municipal solid waste incineration fly ash with different pretreatments - Zhen Chen; Jiang-Shan Li; Chi-Sun Poon; Wen-Hao Jiang; Zi-Han Ma; Xin Chen; Jian-Xin Lu; Hao-Xin Dong (Waste Management, 2023)

An empirical analysis of electric vehicles ’ charging patterns - Zhi Li; Zhengtian Xu; Zhibin Chen; Chi Xie; Guodong Chen; Minghui Zhong (Transportation Research Part D: Transport and Environment, 2023)

Severe shoot topping slows down berry sugar accumulation rate, alters the vine growth and photosynthetic capacity, and influences the flavoromics of Cabernet Sauvignon grapes in a semi-arid region - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Xiao Han; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (European Journal of Agronomy, 2023)

Confinement effect and Hetero-interface enable High-Performing MnOx/CeO2 oxidation catalysts with exceptional sintering resistance:Morphology effect of ceria support - Yijia Cao; Chi Zhang; Li Lv; Tao Zhang; Yunfa Chen; Shengwei Tang; Ye Wang; Wenxiang Tang (Chemical Engineering Journal, 2023)

Visible-light-driven selective cleavage of C C bonds in lignin model substrates using carbon nitride-supported ruthenium single-atom catalyst - Jun Deng; Chi Zhou; Yue Yang; Bing Nan; Lin Dong; Lingchao Cai; Lina Li; Zhu-Jun Wang; Xiaofei Yang; Zupeng Chen (Chemical Engineering Journal, 2023)

Large-scale mapping of new mixed rice cropping patterns in southern China with phenology-based algorithm and MODIS dataset - Qihui Shao; Rendong Li; Juan Qiu; Yifei Han; Dongfeng Han; MiaoMiao Chen; Hong Chi (Paddy and Water Environment, 2023)

Nocardia seriolae cell wall lipids: An effective protective mechanism in resistance and virulence - Sandra Celenia Nazareth; Shreesha Rao; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2023)
Piscine nocardiosis, caused by Nocardia seriolae , is a refractory granulomatous disease in South‐East Asian aquaculture. This study investigates the virulence of nocardial lipids essential for pathogenesis among Actinomycetes. Petroleum ether (PE) was used to selectively delipidate two groups of N. seriolae , namely, live cell (LC) and killed cell (KC); resulting in delipidated live cell (DLC) and delipidated killed cell (DKC), respectively. Changes post‐delipidation on genus characteristics, such as loss in acid‐fast nature and resistance to lysozyme were observed. Transmission electron microscopy revealed notable changes in the lipid layer. Additionally, Lates calcarifer , Asian seabass intraperitoneally injected with LC and DLC had mortality rates of 90% and 50%, respectively, with the latter exhibiting a delay in mortality. Reverse‐transcription quantitative PCR (RT‐qPCR) analysis of host cytokines from the spleen and head kidney showed delipidation contributed to the induction of an immune response with increased transcriptional levels of interferon‐γ ( ifn‐γ ). Histopathological samples collected on day 7 post‐inoculation displayed a varied granulomatous response between the treatment groups and scored for pathological changes. These findings affirm that the virulence of the lipids remains independent of the living state of the cell, significantly altering the immune and granulomatous responses in L. calcarifer to N. seriolae.

Effect of Tip Rake Distribution on the Hydrodynamic Performance of Non-Planar Kappel Propeller - Chen-Wei Chen; Xu-Peng Chen; Zhao-Ye Zhou; Li-Wan Chen; Chi Zhang; Tian-Jiang Zheng; Hua-Min Li (Journal of Marine Science and Engineering, 2023)
Taking advantage of end-plate effects to enhance propeller efficiency is engaging. This paper applied a 4-order B-spline curve to design the rake distribution of Kappel propellers using five types of Kappel propellers that each possesses different tip rakes, and one type has no constructed end-plate. The RANS method coupled with the γ transition model was utilized to analyze the open-water performance of the six propellers, considering cavitating flow. It was found that the tip rake is conducive to the thrust capacity of the Kappel propellers, mostly improving the propulsion efficiency by 2.5% at a designed advance speed with the appropriate tip rake. The increase in the tip rake will magnify the low-pressure value and area on the suction side blade surface, together with the phenomenon of the stretching tip vortex and the inhibition of wake vortex contraction, which are both beneficial to the elevation of propulsion efficiency. However, the sheet cavitation behavior of the six propellers aggravates as the tip rake rises. Accordingly, the reasonable range of a tip rake for the design of a Kappel propeller in favor of the propulsion performance is suggested in this paper, exhibiting the promising potential of energy savings for the application to marine vehicles.

Associations between trace level thallium and multiple health effects in rural areas: Chinese Exposure and Response Mapping Program (CERMP) - Yun-Jiang Yu; Zhen-Chi Li; Yang Zhou; Chen-Yin Dong; Hong-Xuan Kuang; Tong Zheng; Ming-Deng Xiang; Xi-Chao Chen; Hong-Yan Li; Xiao-Wen Zeng; Shu-Li Xu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Distinguishing the contributions of hot holes from interband and intraband transitions to the photoenhanced electrocatalytic oxidation reaction of ethanol - Chen Chi; Miao Ni; Xin-Lei Ding; Dong-Rui Yang; Jian Li; Xing-Hua Xia (Science Bulletin, 2023)

Theoretical study on the free radical scavenging potency and mechanism of natural coumestans: Roles of substituent, noncovalent interaction and solvent - Mohan Chen; Zheng Li; Gang Sun; Shuang Jin; Xiyue Hao; Chi Zhang; Ling Liu; Ling Zhang; Hongli Liu; Yunsheng Xue (Phytochemistry, 2023)

Chromium transformation driven by iron redox cycling in basalt-derived paddy soil with high geological background values - Ke Zhang; Yang Yang; Wenting Chi; Guojun Chen; Yanhong Du; Shiwen Hu; Fangbai Li; Tongxu Liu (Journal of Environmental Sciences, 2023)

Manipulating the severe shoot topping delays the harvest date and modifies the flavor composition of Cabernet Sauvignon wines in a semi-arid climate - Hao-Cheng Lu; Li Hu; Yao Liu; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Chemistry, 2023)

Volatomics of ‘Cabernet Sauvignon’ grapes and wines under the fan training system revealed the nexus of microclimate and volatile compounds - Meng-Bo Tian; Yao Liu; Hao-Cheng Lu; Li Hu; Yu Wang; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Chemistry, 2023)

Reductive dehalogenation pathways and inhibition mechanisms of 2,5-dichloronitrobenzene in UV/sulfite advanced reduction process - Hang Ren; Ranyun Xu; Tongtong Chi; Feifei Li; Yuhan Zheng; Jinping Tian; Lyujun Chen (Chemical Engineering Journal, 2023)

In silico analysis of NAC gene family in the mangrove plant Avicennia marina provides clues for adaptation to intertidal habitats - Shiwei Song; Dongna Ma; Chaoqun Xu; Zejun Guo; Jing Li; Lingyu Song; Mingyue Wei; Ludan Zhang; You-Hui Zhong; Yu-Chen Zhang; Jing-Wen Liu; Bingjie Chi; et al. (Plant Molecular Biology, 2023)

The NH2-UiO-66/3,4,9,10-perylenetetracarboxylicdiimide for Cr(VI) reduction: DFT calculation, performance, and mechanism - Yang Li; Yu-Hang Li; Peng Wang; Chen Zhao; Chi-Yao Tang; Shi-Jie Gao; Chong-Chen Wang (Journal of Environmental Chemical Engineering, 2023)

Typhoon-induced destruction and reconstruction of the coastal current system on the inner shelf of East China Sea - Wenqi Chi; Fangfang Shu; Yuting Lin; Yunhai Li; Fusheng Luo; Jia He; Zhijie Chen; Xiaochun Zou; Binxin Zheng (Continental Shelf Research, 2023)

CRISPR-based DNA methylation editing of NNT rescues the cisplatin resistance of lung cancer cells by reducing autophagy - Chi Xu; Shuyun Jiang; Xingyu Ma; Zeyong Jiang; Youguang Pan; Xiang Li; Liying Zhang; Hao Zhou; Shen Chen; Xiumei Xing; Liping Chen; Wenfan Fu; et al. (Archives of Toxicology, 2023)

Earthquake-induced persistent and instantaneous groundwater variations caused by volumetric strain of soil in Taiwan from 1999 to 2020 - Chi-Chin Tsai; Li-Ya Huang; Chia-Jeng Chen (Soil Dynamics and Earthquake Engineering, 2023)

Typical layered structure bismuth-based photocatalysts for photocatalytic nitrogen oxides oxidation - Chi Ma; Jingjing Wei; Kainian Jiang; Jiaqi Chen; Zhongzhu Yang; Xu Yang; Guanlong Yu; Chang Zhang; Xin Li (Science of The Total Environment, 2023)

Paddy rice methane emissions across Monsoon Asia - Zutao Ouyang; Robert B. Jackson; Gavin McNicol; Etienne Fluet-Chouinard; Benjamin R.K. Runkle; Dario Papale; Sara H. Knox; Sarah Cooley; Kyle B. Delwiche; Sarah Feron; Jeremy Andrew Irvin; Avni Malhotra; et al. (Remote Sensing of Environment, 2023)

Insight into photo-fenton catalytic degradation of tetracycline by environmental friendly nanocomposite 1T-2H hybrid phases MoS2/Fe3O4/g-C3N4 - Rongchao Yang; Guangzhu Zhou; Cuizhen Wang; Yin Liu; Yanyun Zhao; Yinming Li; Xiaoning Fu; Jingyi Chi; Xi Chen; Hui Fang; Zheng Qin (Journal of Cleaner Production, 2023)

Advanced exergy analysis of NH3/CO2 cascade refrigeration system with ejector - Weikai Chi; Qichao Yang; Xiaonan Chen; Liansheng Li; Guangbin Liu; Yuanyang Zhao (International Journal of Refrigeration, 2023)

Accumulated temperature and allocation of photo-thermal resources are key meteorological factors affecting rice cadmium content - Wei Zhou; Fengjun Yan; Yu Fan; Chi Zhang; Fan Yang; Qi Liu; Tao Wang; Bo Li; Yong Chen; Fei Deng; Jianfeng Hu; Xiaolong Lei; et al. (European Journal of Agronomy, 2023)

Recyclable nanocomposites for carbon dioxide fixation and membrane separation using waste polycarbonate - Ying-Chi Huang; Li-Fan Chen; Yu-Hsiang Huang; Chien-Chieh Hu; Chien-Hsin Wu; Ru-Jong Jeng (Chemical Engineering Journal, 2023)

Investigations on Cutting Force and Temperature Field of Pick Cutter Based on Single Factor and Orthogonal Test Methods - Long-Chuan Deng; Xiao-Zhao Li; Yi-Wei Chen; Qian-Wei Zhuang; Long-Hai Zhu; Chi Zhang (Rock Mechanics and Rock Engineering, 2023)

The complete mitochondrial genome of Parachiloglanis hodgarti and its phylogenetic position within Sisoridae - Jiasheng Li; Ying Peng; Shufei Zhang; Yifan Liu; Kun Zhang; Jian Chen; Hua Zhang; Chi Zhang; Bingjian Liu (Journal of Oceanology and Limnology, 2023)

Effect of alkaline washing treatment on leaching behavior of municipal solid waste incineration bottom ash - Zhen Chen; Jiang-Shan Li; Dongxing Xuan; Chi Sun Poon; Xiao Huang (Environmental Science and Pollution Research, 2023)

Isochrysis sp. cultivation in pilot-scale to concurrently produce sustainable triacylglycerols for human milk fat substitutes and fucoxanthin - Daogui Li; Na Chen; Zhihua Zhou; Cairong Zhong; Jingping Fang; Luqiang Huang; Han Sun; Chengdeng Chi; Youcai Zhou; Yongjin He (Algal Research, 2023)

Tannic acid attenuate AKT phosphorylation to inhibit UMUC3 bladder cancer cell proliferation - Ming-Cheng Chen; Selvaraj Annseles Rajula; V. Bharath Kumar; Chiung-Hung Hsu; Cecilia Hsuan Day; Ray-Jade Chen; Tso-Fu Wang; Vijaya Padma Viswanadha; Chi-Cheng Li; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2022)

Complete Mitochondrial Genome Analysis of Daphniopsis tibetana (Branchiopoda: Diplostraca): New Insights into the Taxonomy of the Genus and Its Phylogenetic Implications for Branchiopoda - Bingjian Liu; Ying Peng; Yifan Liu; Jiasheng Li; Kun Zhang; Jian Chen; Li Gong; Liqin Liu; Zhenming Lü; Chi Zhang (Journal of Ocean University of China, 2022)

7,8-Dihydroxyflavone attenuates the virulence of Staphylococcus aureus by inhibiting alpha-hemolysin - Nan Bian; Xiangqian Chen; Xinran Ren; Zishu Yu; Mengli Jin; Xiaoyu Chen; Chang Liu; Yanhe Luan; Lin Wei; Ying Chen; Wu Song; Yicheng Zhao; et al. (World Journal of Microbiology and Biotechnology, 2022)

Distribution of ultrafine aerosols and volatile organic compounds from surgical smoke during electrocauterization - Chi-Tsung Chen; Shiang-Fu Huang; Cheng-Jung Li; Jou-Mien Huang; Kai-Ping Chang; Gwo-Hwa Wan (Air Quality, Atmosphere & Health, 2022)

Unlabeled Sample Selection for Mineral Prospectivity Mapping by Semi-supervised Support Vector Machine - Jintao Tao; Nannan Zhang; Jinyu Chang; Li Chen; Hao Zhang; Yujin Chi (Natural Resources Research, 2022)

Threshold of surface erosion of cohesive sediments - Dake Chen; Jinhai Zheng; Chi Zhang; Dawei Guan; Yuan Li; Huiming Huang (Frontiers in Marine Science, 2022)
Cohesive sediment is ubiquitous in aquatic systems, which often forms fractal aggregates due to cohesive and adhesive forces between particles and is generally eroded as aggregates at low bed shear stresses. The erosion of aggregates plays a significant role in cohesive sediment dynamics. However, the effects of fractal bed aggregation on the erosion threshold of sediment have not been well understood. The incipient motion condition of cohesive sediment is investigated, in which particle aggregation is taken into account by employing the fractal theory and the van der Waals force between particles. A formula for the critical shear stress for surface erosion of cohesive sediments composed of fractal aggregates is developed based on the balance analysis of momentums acting on an aggregate in the bed surface. The developed formula has been successfully applied to different kinds of cohesive sediment. The fractal dimension is found as a function of the solid volume fraction and the diameter of primary particles. The contribution rate of the effective weight of aggregate to the erosion threshold of cohesive sediment is quantified.

Design, synthesis, antiproliferative and antimicrobial evaluation of a new class of disulfides containing 1,3,4-thiadiazole units - Ruilian Zhang; Bo Li; Chunlan Chi; Yang Liu; Xuguang Liu; Junjie Li; Wei Li; Baoquan Chen (Medicinal Chemistry Research, 2022)

The Effect of Co-Exposure to Glyphosate, Cadmium, and Arsenic on Chronic Kidney Disease - Junne-Ming Sung; Wei-Hsiang Chang; Kuan-Hung Liu; Chung Yu Chen; Trias Mahmudiono; Wan-Ru Wang; Ho-Chi Hsu; Zhen-Yi Li; Hsiu-Ling Chen (Exposure and Health, 2022)

Groundwater Geochemical Variation and Controls in Coal Seams and Overlying Strata in the Shennan Mining Area, Shaanxi, China - Chen Guo; Junzhe Gao; Shengquan Wang; Chi Zhang; Xiaolong Li; Jiang Gou; Lingling Lu (Mine Water and the Environment, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Preliminary establishment of a mass movement warning system for Taiwan using the soil water index - Chi-Wen Chen; Ching Hung; Guan-Wei Lin; Jun-Jih Liou; Shih-Yao Lin; Hsin-Chi Li; Yung-Ming Chen; Hongey Chen (Landslides, 2022)

The impacts of ambient relative humidity and temperature on supine position-related obstructive sleep apnea in adults - Wen-Te Liu; Yuan-Hung Wang; Li-Te Chang; Chih-Da Wu; Dean Wu; Cheng-Yu Tsai; Chen-Chen Lo; Kang Lo; Kian Fan Chung; Ta-Yuan Chang; Kai-Jen Chuang; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

The Characteristics and Expression Profile of Peptidoglycan Recognition Protein 2 in the Accessory Nidamental Gland of the Bigfin Reef Squid During Bacterial Colonization - Hau-Wen Li; Wei-Lun Kuo; Chi Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2022)
Some cephalopods carry microorganisms in two specialized organs, the light organ and the accessory nidamental gland (ANG). For the light organ, comprehensive mechanisms have been described for winnowing (bacterial selection) and maintenance of the symbiotic luminescent bacterium Vibrio fischeri ( V. fischeri ). However, the mechanisms controlling bacterial selection and maintenance during bacterial colonization of the ANG are open biological issues with physiological significance. Our recent study on bigfin reef squid ( Sepioteuthis lessoniana ) already showed that the ANG bacterial community shifts gradually and exhibits decreased diversity throughout maturation. This study further describes a potential role of an innate immunity-involved molecule, peptidoglycan recognition proteins (PGRPs), in the ANG of bigfin reef squid during bacterial transmission and colonization. First, we found that four homologs of the PGRP family are expressed in the ANG of bigfin reef squid ( sl PGRP2-5), but only slPgrp2 transcript levels are highly correlated with ANG development and bacterial colonization. Besides, slPgrp2 transcripts are mainly expressed in the epithelial cells of certain secondary tubules of ANG, and the expression levels are varied in the epithelial cells of other secondary tubules. This data reveals that slPgrp2 transcripts may associate with the composition of bacterial consortium and its secretary factors. Moreover, recombinant sl PGRP2 had a negative effect of Escherichia coli ( E.coli ) which inhibited bacterial growth in culture. Therefore, our data suggest slPgrp2 expression in the epithelial cells of secondary tubules in the ANG may have an essential role in the winnowing and maintenance of holobiont homeostasis in bigfin reef squid.

Monascuslactams A–D, cytotoxic γ-lactams from marine fungus Monascus albidus BB3 - Qi Guo; Xiao-Ming Dai; Wen-Jian Lan; Liu-Ping Chen; Chi-Keung Lam; Gong-Kan Feng; Rong Deng; Xiao-Feng Zhu; Hou-Jin Li (Natural Product Research, 2022)

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

First report of acanthocephalan parasite, Longicollum pagrosomi Yamaguti, 1935 in cultured red snapper ( Lutjanus erythropterus ) in Taiwan - Li‐Wu Cheng; Shreesha Rao; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2022)
For the first time, Longicollum pagrosomi Yamaguti, 1935, an acanthocephalan parasite, has been characterized with morphological, histopathological and molecular detail in farmed red snapper ( Lutjanus erythropterus ) in Taiwan. The diseased fish showed clinical signs of anorexia, emaciation and were gasping for air at the water's surface. Gross examination revealed extensive necrosis in the intestine and even penetration at the site of parasitic attachment, resulting in a large number of parasites being lodged in the peritoneal cavity, surrounded by black hyperplastic connective tissue. The parasites collected from the intestine were studied using optical microscopy, histopathology, scanning electron microscopy (SEM) and molecular phylogenetic analysis. They were creamy white in colour, and were separated into their proboscis, neck and metasoma (trunk) under optical microscopy. Histopathological examination revealed ovarian balls (floating ovaries) inside the ligament sac and eggs within the egg sorting apparatus. The SEM images revealed that the proboscis had 11–14 longitudinal rows with 9–12 recurrent, backward‐facing, organized hooks. In the 18S and 28S phylogenetic tree, sequences of the specimens were identical to those of other Longicollum pagrosomi , in addition to the morphological features. Thus, we confirmed that the parasites belonged to Longicollum pagrosomi in this study.

Comprehensive review on catalytic degradation of Cl-VOCs under the practical application conditions - Fawei Lin; Li Xiang; Zhiman Zhang; Na Li; BeiBei Yan; Chi He; Zhengping Hao; Guanyi Chen (Critical Reviews in Environmental Science and Technology, 2022)

Neutrophil Extracellular Traps may be a Potential Target for Treating Early Brain Injury in Subarachnoid Hemorrhage - Hanhai Zeng; Xiongjie Fu; Jing Cai; Chenjun Sun; Mengyan Yu; Yucong Peng; Jianfeng Zhuang; Jingyin Chen; Huaijun Chen; Qian Yu; Chaoran Xu; Hang Zhou; et al. (Translational Stroke Research, 2022)

Seepage field distribution and water inflow laws of tunnels in water-rich regions - Zheng Li; Zi-quan Chen; Chuan He; Chun-chi Ma; Chao-ran Duan (Journal of Mountain Science, 2022)

Synthesis, antiproliferative, and antimicrobial properties of novel phthalimide derivatives - Chun-Lan Chi; Lu Xu; Jun-Jie Li; Yang Liu; Bao-Quan Chen (Medicinal Chemistry Research, 2022)

Not out of the woods yet: Signatures of the prolonged negative genetic consequences of a population bottleneck in a rapidly re‐expanding wader, the black‐faced spoonbill Platalea minor - Shou‐Hsien Li; Yang Liu; Chia‐Fen Yeh; Yuchen Fu; Carol K. L. Yeung; Chun‐Cheng Lee; Chi‐Cheng Chiu; Tung Hui Kuo; Fang‐Tse Chan; Yu‐Chia Chen; Wen‐Ya Ko; Cheng‐Te Yao (Molecular Ecology, 2022)
The long‐term persistence of a population which has suffered a bottleneck partly depends on how historical demographic dynamics impacted its genetic diversity and the accumulation of deleterious mutations. Here we provide genomic evidence for the genetic effect of a recent population bottleneck in the endangered black‐faced spoonbill ( Platalea minor ) after its rapid population recovery. Our data suggest that the bird's effective population size, N e , had been relatively stable (7500–9000) since 22,000 years ago; however, a recent brief yet severe bottleneck ( N e = 20) which we here estimated to occur around the 1940s wiped out >99% of its historical N e in roughly three generations. Despite a >15‐fold population recovery since 1988, we found that black‐faced spoonbill population has higher levels of inbreeding (7.4 times more runs of homozygosity) than its sister species, the royal spoonbill ( P. regia ), which is not thought to have undergone a marked population contraction. Although the two spoonbills have similar levels of genome‐wide genetic diversity, our results suggest that selection on more genes was relaxed in the black‐faced spoonbill; moreover individual black‐faced spoonbills carry more putatively deleterious mutations (Grantham's score > 50), and may therefore express more deleterious phenotypic effects than royal spoonbills. Here we demonstrate the value of using genomic indices to monitor levels of genetic erosion, inbreeding and mutation load in species with conservation concerns. To mitigate the prolonged negative genetic effect of a population bottleneck, we recommend that all possible measures should be employed to maintain population growth of a threatened species.

Correction to: Considerations for Updates to ICH Q1 and Q5C Stability Guidelines: Embracing Current Technology and Risk Assessment Strategies - Megan E. McMahon; Alexander Abbott; Yelizaveta Babayan; Jenny Carhart; Chi-wan Chen; Elke Debie; Mingkun Fu; Cherokee Hoaglund-Hyzer; Andrew Lennard; Hanlin Li; Tony Mazzeo; Lori McCaig; et al. (The AAPS Journal, 2021)

Considerations for Updates to ICH Q1 and Q5C Stability Guidelines: Embracing Current Technology and Risk Assessment Strategies - Megan E. McMahon; Alexander Abbott; Yelizaveta Babayan; Jenny Carhart; Chi-wan Chen; Elke Debie; Mingkun Fu; Cherokee Hoaglund-Hyzer; Andrew Lennard; Hanlin Li; Tony Mazzeo; Lori McCaig; et al. (The AAPS Journal, 2021)

Genomic characterization of a rare Carica papaya X chromosome mutant reveals a candidate monodehydroascorbate reductase 4 gene involved in all-hermaphrodite phenomenon - Jen-Ren Chen; Hiroki Ueno; Hideo Matsumura; Naoya Urasaki; Chen-Yu Lee; Fure-Chyi Chen; Shih-Wen Chin; Chun-Chi Liu; Chan-Tai Chiu; Kazuhiko Tarora; Jing-Yi Li; Chieh Ying Lee; et al. (Molecular Genetics and Genomics, 2021)

Critical Shear Stress for Erosion of Sand-Mud Mixtures and Pure Mud - Dake Chen; Jinhai Zheng; Chi Zhang; Dawei Guan; Yuan Li; Yigang Wang (Frontiers in Marine Science, 2021)
The erosion threshold of sand-mud mixtures is investigated by analyzing the momentum balance of a sand particle or a mud parcel in the mixture bed surface, and a formula for the critical shear stress of sand-mud mixtures is developed, which also applies for pure sand and mud. The developed formula suggests that the variation of the critical shear stress of sand-mud mixtures over mud content is mainly caused by the varying dry bulk density of the mud component in the mixture. The developed formula reproduces well the variation of the critical shear stress of sand-mud mixtures over mud content and can predict the critical shear stress of both sand-mud mixtures and pure mud in the process of consolidation. The developed formula promises to be convenient for application by relating the critical shear stress to mud content and the dry bulk density of sediment.

Social disruption–induced stress pre-exposure aggravates, while the presence of conspecifics diminishes, acetic acid–induced writhing - Yi-Han Liao; Yi-Chi Su; Yu-Han Huang; Hao Chen; Ya-Hsuan Chan; Li-Han Sun; Chianfang G. Cherng; Ing-Tiau B. Kuo; Lung Yu (Psychopharmacology, 2021)

Genotype and virulence gene analyses of Bacillus cereus group clinical isolates from the Chinese softshell turtle ( Pelodiscus sinensis ) in Taiwan - Li‐Wu Cheng; Shreesha Rao; Sayuj Poudyal; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2021)
Chinese softshell turtles ( Pelodiscus sinensis ) (CST) are susceptible to infections by bacteria belonging to the Bacillus cereus group (Bcg). Bcg includes several closely related species, two of which, B . cereus and B . thuringiensis , are pathogens of aquatic animals or insects. In the present study, we collected 57 Bcg isolates from diseased CST from 2016 to 2019 in Kaohsiung and Pingtung, where most CST farms are located in Taiwan. All isolates were divided into four genotypes with two restriction enzymes, Sma I and Not I, by pulsed‐field gel electrophoresis and enterobacterial repetitive intergenic consensus–polymerase chain reaction (ERIC‐PCR). Representative isolates from each genotype were subjected to phylogenetic tree analysis using 16S rDNA and pyruvate carboxylase genes as phylogenetic markers, and these CST isolates appeared in different clades. PCR was performed targeting six selected virulence genes, four of which were detected in CST isolates, including cytotoxin K (1/57), hblC of the haemolysin BL complex (46/57), nheA of the non‐haemolytic enterotoxin complex (52/57) and enterotoxin FM (57/57), whereas cereulide synthetase and cereulide peptide synthase‐like genes were not detected in any isolates.

Anti-Inflammatory and anti-proliferative oleanane-type triterpene glycosides from the vine of Momordica cochinchinensis - Hung-Tse Huang; Yu-Chi Lin; Li-Jie Zhang; Chia-Ching Liaw; Hsin-Yen Chen; Ming-Tung Hsueh; Yao-Haur Kuo (Natural Product Research, 2021)

Wogonin Accelerates Hematoma Clearance and Improves Neurological Outcome via the PPAR-γ Pathway After Intracerebral Hemorrhage - Jianfeng Zhuang; Yucong Peng; Chi Gu; Huihui Chen; Zheng Lin; Hang Zhou; Xiao Wu; Jianru Li; Xiaobo Yu; Yang Cao; Hanhai Zeng; Xiongjie Fu; et al. (Translational Stroke Research, 2021)

Moisture source variations for summer rainfall in different intensity classes over Huaihe River Valley, China - Yubo Liu; Chi Zhang; Qiuhong Tang; Seyed-Mohammad Hosseini-Moghari; Gebremedhin Gebremeskel Haile; Laifang Li; Wenhong Li; Kun Yang; Ruud J. van der Ent; Deliang Chen (Climate Dynamics, 2021)

A Case Study of Whistle Detection and Localization for Humpback Dolphins in Taiwan - Ching-Tang Hung; Wei-Yen Chu; Wei-Lun Li; Yen-Hsiang Huang; Wei-Chun Hu; Chi-Fang Chen (Journal of Marine Science and Engineering, 2021)
In recent years, Taiwan’s government has focused on policies regarding offshore wind farming near the Indo-Pacific humpback dolphin habitat, where marine mammal observation is a critical consideration. The present research developed an algorithm called National Taiwan University Passive Acoustic Monitoring (NTU_PAM) to assist marine mammal observers (MMOs). The algorithm performs whistle detection processing and whistle localization. Whistle detection processing is based on image processing and whistle feature extraction; whistle localization is based on the time difference of arrival (TDOA) method. To test the whistle detection performance, we used the same data to compare NTU_PAM and the widely used software PAMGuard. To test whistle localization, we designed a real field experiment where a sound source projected simulated whistles, which were then recorded by several hydrophone stations. The data were analyzed to locate the moving path of the source. The results show that localization accuracy was higher when the sound source position was in the detection region composed of hydrophone stations. This paper provides a method for MMOs to conveniently observe the migration path and population dynamics of cetaceans without ecological disturbance.

Progress in fundamental research on thermal desorption remediation of organic compound-contaminated soil - Bo Wang; Angjian Wu; Xiaodong Li; Longjie Ji; Chen Sun; Zongze Shen; Tong Chen; Zuohe Chi (Waste Disposal & Sustainable Energy, 2021)

Bioactive polyketides from the pathogenic fungus of Epicoccum sorghinum - Ching-Chia Chang; Chi-Ying Li; Yi-Hong Tsai; Mohamed El-Shazly; Chien-Kei Wei; Zih-Jie Yang; Shu-Li Chen; Chin-Chung Wu; Yang-Chang Wu; Fang-Rong Chang (Planta, 2021)

Pomelo fruit wastes are potentially valuable antioxidants, anti-inflammatories, antihypertensives, and antihyperglycemics - Li-Yun Lin; Chi-Yun Huang; Kuan-Chou Chen; Robert Y. Peng (Horticulture, Environment, and Biotechnology, 2021)
Grapefruit (G) parts contain abundant phenolic acids and flavonoids (PPNs and FLVs). The wastes created from exocarps, mesocarps (G wastes, GW) and waste blanching water (WBW) lead to a considerable loss of PPNs and FLVs. Here, we assessed Buntan (CB), Buntan Hayata (CBH), and Peiyu (CP) cultivars and observed considerable amounts of PPNs and FLVs. The ethanolic extracts of GW (GWE) and WBW contained gallic acid, protocatechuic acid, chlorogenic acid, caffeic acid, ferulic acid, coumaric acid, naringin, hesperidin, diosmin, quercetin, hesperetin, nobiletin, and tangeretin (GWC). GWE has previously been reported to be a relatively active antioxidant, anti-inflammatory (based on the expression of TNF-α in Raw264.7 cells), antihypertensive, and anti-hyperglycemic compound. The IC 50 values for antihyperglycemic activity with WBW for α-amylase were as follows: CB (27.96 ± 0.03 mg/mL) < CP (28.13 ± 0.19 mg/mL) < CBH (41.60 ± 0.16 mg/mL), and those for α-glucosidase were CB (1.80 ± 0.03 mg/mL) < CP (2.97 ± 0.29 mg/mL) < CBH (9.10 ± 0.51 mg/mL). GWC upregulated Glut4 in HepG2 cells, as well as the insulin secretion capability, and intracellular levels in RIN-m5F cells, and it downregulated DPP4 in HepG2 cells. The IC 50 values for the angiotensin-converting enzyme activity were: CBP (5.10 ± 0.02 mg/mL) < CB (7.24 ± 0.65 mg/mL) < CP (8.60 ± 2.03 mg/mL). Our results indicate that PPNs and FLVs present in GW are worth reclaiming.

MiR-124 and Small Molecules Synergistically Regulate the Generation of Neuronal Cells from Rat Cortical Reactive Astrocytes - Yangyang Zheng; Zhehao Huang; Jinying Xu; Kun Hou; Yifei Yu; Shuang Lv; Lin Chen; Yulin Li; Chengshi Quan; Guangfan Chi (Molecular Neurobiology, 2021)

New contributions to the phylogeny of the ciliate class Heterotrichea (Protista, Ciliophora): analyses at family-genus level and new evolutionary hypotheses - Yong Chi; Xiangrui Chen; Yuqing Li; Chundi Wang; Tengteng Zhang; Alex Ayoub; Alan Warren; Weibo Song; Yuanyuan Wang (Science China Life Sciences, 2021)

Correction to: A Brush–Spin–Coating Method for Fabricating In Vitro Patient-Specific Vascular Models by Coupling 3D-Printing - Qing-Zhuo Chi; Li-Zhong Mu; Ying He; Yong Luan; Yu-Chen Jing (Cardiovascular Engineering and Technology, 2021)

A Brush–Spin–Coating Method for Fabricating In Vitro Patient-Specific Vascular Models by Coupling 3D-Printing - Qing-Zhuo Chi; Li-Zhong Mu; Ying He; Yong Luan; Yu-Chen Jing (Cardiovascular Engineering and Technology, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

The cellulose synthase (CesA) gene family in four Gossypium species: phylogenetics, sequence variation and gene expression in relation to fiber quality in Upland cotton - Sujun Zhang; Zhenxing Jiang; Jie Chen; Zongfu Han; Jina Chi; Xihua Li; Jiwen Yu; Chaozhu Xing; Mingzhou Song; Jianyong Wu; Feng Liu; Xiangyun Zhang; et al. (Molecular Genetics and Genomics, 2021)

High-Level Expression and Purification of Melittin in Escherichia coli Using SUMO Fusion Partner - Qiu-chi Chen; Lei Liu; Tian-Yi Yu; Lu Tang; Mo-li Yin; Wen-he Zhu; Xiu-yun Jiang; Hui-yan Wang (International Journal of Peptide Research and Therapeutics, 2021)

Degradation stage effects on vegetation and soil properties interactions in alpine steppe - Cheng-yang Li; Fei Peng; Xian Xue; Chi-min Lai; Wen-juan Zhang; Quan-gang You; Xiao-jie Chen; Xue-qin Zhang; Tao Wang (Journal of Mountain Science, 2021)

Synthesis and antitumor effects of a new class of 1,2,4-triazole derivatives - Zheng Wu; Xin Li; Chun-Lan Chi; Lu Xu; Yong-Yue Sun; Bao-Quan Chen (Medicinal Chemistry Research, 2021)

miR-146a Mimics Ameliorates Traumatic Brain Injury Involving JNK and NF-κB Signaling Pathway - Lei Zhang; Li Zhao; Wei Zhu; Yuexia Ding; Hongguang Chen; Nan Chi (NeuroMolecular Medicine, 2020)

Histopathology, Molecular Identification and Antifungal Susceptibility Testing of Nannizziopsis arthrosporioides from a Captive Cuban Rock Iguana (Cyclura nubila) - Yen-Han Chen; Meng-Jou Chi; Pei-Lun Sun; Pin-Huan Yu; Chen-Hsuan Liu; Jose F. Cano-Lira; Wen-Ta Li (Mycopathologia, 2020)

SUSLE: a slope and seasonal rainfall-based RUSLE model for regional quantitative prediction of soil erosion - Faming Huang; Jiawu Chen; Chi Yao; Zhilu Chang; Qinghui Jiang; Shu Li; Zizheng Guo (Bulletin of Engineering Geology and the Environment, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Latitudinal differences in early growth of largehead hairtail ( Trichiurus japonicus ) in relation to environmental variables - Peng Sun; Qi Chen; Caihong Fu; Yi Xu; Runlong Sun; Jianchao Li; Haiqing Yu; Chi Zhang; Yang Liu; Zhenjiang Ye; Yongjun Tian; Mikko Heino (Fisheries Oceanography, 2020)
Largehead hairtail ( Trichiurus japonicus ) in the China Seas shows an increasing catch trend, despite continued overexploitation, which could be attributed to improved recruitment as a result of strengthened early growth. To understand the early growth variability of largehead hairtail, we examined the linkages between early growth, as revealed by otolith microstructure, and the associated environmental variables over both spatial and temporal scales. Young‐of‐the‐Year largehead hairtail were collected from three regions in the Bohai, Yellow and East China Seas between 29° and 39° N. Daily increment widths of sagittal otoliths were measured and used as a proxy for somatic growth. We found two spawning cohorts, Spring‐ and Summer‐spawned cohorts, that showed latitudinal differences in both mean growth and growth pattern. The transition time from larval to juvenile stage was identified at around 40 days. Daily increment widths of two cohorts showed similar growth pattern in the first 40 days, while location had a marked effect on daily growth over 41–110 days. This suggests physiologically constrained growth pattern in larval stage, but more plastic growth subject to habitat‐specific influences in juvenile stage. The gradient forest analysis identified sea bottom temperature, vertical temperature gradient, and sea surface salinity, as the most important variables in determining early growth. Latitudinal differences in early growth pattern and their response to environmental variables suggest adaptive plasticity of early growth, which has notable implication for the management and sustainable utilization of this important but heavily exploited resource in the China Seas.

Small RNA profiling reveal regulation of microRNAs in field peanut pod rot pathogen infection - Mian Wang; Chao-xin Zhang; Li-juan Pan; Tong Wang; Na Chen; Ming-na Chen; Zhen Yang; Xin-gang Guo; Shan-lin Yu; Xiao-yuan Chi (Biologia, 2020)

Pattern Informatics and the Soup-of-Groups Model of Earthquakes: A Case Study of Italian Seismicity - Ling-Yun Chang; Chien-Chih Chen; Luciano Telesca; Hsien-Chi Li; S. A. Cheong (Pure and Applied Geophysics, 2020)

Neuroimaging Spectrum at Pre-, Early, and Late Symptomatic Stages of SCA17 Mice - Chiao-Chi Chen; Nai-Wei Yao; Chia-Wei Lin; Wei-Shuo Su; Chin-Tien Wu; Chen Chang; Hsiu Mei Hsieh-Li (The Cerebellum, 2020)

First report of leaf blight on Cattleya × hybrid caused by Neoscytalidium dimidiatum in Taiwan - Che-Wei Chang; Chi-Yu Chen; Chih-Li Wang; Wen-Hsin Chung (Journal of Plant Pathology, 2020)

Mechanical injury and IL-1β regulated LOXs and MMP-1, 2, 3 expression in ACL fibroblasts co-cultured with synoviocytes - Chunli Wang; Qingjia Chi; Yongqiang Sha; Kang Xu; Chunming Xu; Cheng Chen; Wei Huang; Peixing Chen; Peter Chen; Li Yang; K. L. Paul Sung (Biotechnology Letters, 2020)

Attenuated regenerative properties in human periodontal ligament–derived stem cells of older donor ages with shorter telomere length and lower SSEA4 expression - Tsz Kin Ng; Chong-Bo Chen; Ciyan Xu; Yanxuan Xu; Xiaowu Yao; Li Huang; Jia-Jian Liang; Herman S. Cheung; Chi Pui Pang; Yuqiang Huang (Cell and Tissue Research, 2020)

Anti-hypertensive effects of Radix Rehmanniae and its active ingredients - Chiu-Haw Chao; Jue-Liang Hsu; Mu-Fen Chen; Ya-Hu Shih; Chia-Hui Lee; Mei-Li Wu; Chi-I Chang (Natural Product Research, 2020)

Effects of high-frequency surface wind on the intraseasonal SST associated with the Madden-Julian oscillation - Yingxia Gao; Pang-Chi Hsu; Lin Chen; Lu Wang; Tim Li (Climate Dynamics, 2020)

A Familial Phenotypic and Genetic Study of Mutations in PFN1 Associated with Amyotrophic Lateral Sclerosis - Jieshan Chi; Junling Chen; Yan Li; Zhiheng Huang; Lijuan Wang; Yuhu Zhang (Neuroscience Bulletin, 2020)

Design, synthesis, and antitumor evaluation of novel naphthalimide derivatives - Xin Li; Zheng Wu; Lu Xu; Chun-Lan Chi; Bao-Quan Chen (Medicinal Chemistry Research, 2020)

Application of penalized linear regression and ensemble methods for drought forecasting in Northeast China - Zeng Li; Taotao Chen; Qi Wu; Guimin Xia; Daocai Chi (Meteorology and Atmospheric Physics, 2020)

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

Localization of Mucin 1 in endometrial luminal epithelium and its expression in women with reproductive failure during implantation window - Fangrong Wu; Di Mao; Yingyu Liu; Xiaoyan Chen; Hui Xu; Tin Chiu Li; Chi Chiu Wang (Journal of Molecular Histology, 2019)

The complete chloroplast genome of Saxifraga sinomontana (Saxifragaceae) and comparative analysis with other Saxifragaceae species - Yan Li; Liukun Jia; Zhihua Wang; Rui Xing; Xiaofeng Chi; Shilong Chen; Qingbo Gao (Brazilian Journal of Botany, 2019)
Saxifraga sinomontana J.-T. Pan & Gornall belongs to Saxifraga sect. Ciliatae subsect. Hirculoideae , a lineage containing ca. 110 species whose phylogenetic relationships are largely unresolved due to recent rapid radiations. Analyses of complete chloroplast genomes have the potential to significantly improve the resolution of phylogenetic relationships in this young plant lineage. The complete chloroplast genome of S. sinomontana was de novo sequenced, assembled and then compared with that of other six Saxifragaceae species. The S. sinomontana chloroplast genome is 147,240 bp in length with a typical quadripartite structure, including a large single-copy region of 79,310 bp and a small single-copy region of 16,874 bp separated by a pair of inverted repeats (IRs) of 25,528 bp each. The chloroplast genome contains 113 unique genes, including 79 protein-coding genes, four rRNAs and 30 tRNAs, with 18 duplicates in the IRs. The gene content and organization are similar to other Saxifragaceae chloroplast genomes. Sixty-one simple sequence repeats were identified in the S. sinomontana chloroplast genome, mostly represented by mononucleotide repeats of polyadenine or polythymine. Comparative analysis revealed 12 highly divergent regions in the intergenic spacers, as well as coding genes of matK , ndhK , accD , cemA , rpoA , rps19 , ndhF , ccsA , ndhD and ycf1 . Phylogenetic reconstruction of seven Saxifragaceae species based on 66 protein-coding genes received high bootstrap support values for nearly all identified nodes, suggesting a promising opportunity to resolve infrasectional relationships of the most species-rich section Ciliatae of Saxifraga .

Orthosilicic Acid Accelerates Bone Formation in Human Osteoblast-Like Cells Through the PI3K–Akt–mTOR Pathway - Hongming Zhou; Guangjun Jiao; Meng Dong; Hai Chi; Hongliang Wang; Wenliang Wu; Haichun Liu; Shanwu Ren; Meng Kong; Ci Li; Lu Zhang; Yunzhen Chen (Biological Trace Element Research, 2019)

Preparation of AgCl/TNTs nanocomposites for organic dyes and inorganic heavy metal removal - Cheng-Yen Tsai; Chen-Wuing Liu; Hsing-Cheng Hsi; Kuen-Song Lin; Yi-Wen Lin; Li-Chi Lai; Tsung-Nan Weng (Environmental Science and Pollution Research, 2019)

Removal of chlorpheniramine and variations of nitrosamine formation potentials in municipal wastewaters by adsorption onto the GO-Fe3O4 - Chih-Hsien Lin; Chi-Min Li; Chun-Hu Chen; Wei-Hsiang Chen (Environmental Science and Pollution Research, 2019)

RcMYBPA2 of Rosa chinensis functions in proanthocyanidin biosynthesis and enhances abiotic stress tolerance in transgenic tobacco - Zhuoya Li; Wen Chen; Chi Zhang; Changxia Du; Guoyuan Shao; Yongyi Cui; Ping Luo (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Nutritional regulation of pyruvate kinase and phosphoenolpyruvate carboxykinase at the enzymatic and molecular levels in cobia Rachycentron canadum - Ruixin Li; Hongyu Liu; Shuyun Li; Beiping Tan; Xiaohui Dong; Shuyan Chi; Qihui Yang; Shuang Zhang; Liqiao Chen (Fish Physiology and Biochemistry, 2019)

Resistance of alfalfa and Indian mustard to Cd and the correlation of plant Cd uptake and soil Cd form - Chunlai Zhang; Yongqin Chen; Weihong Xu; Sunlin Chi; Tao Li; Yanhua Li; Zhangmi He; Mei Yang; Deyu Feng (Environmental Science and Pollution Research, 2019)

Nattokinase-heparin exhibits beneficial efficacy and safety—an optimal strategy for CKD patients on hemodialysis - Hao Wu; Huan Wang; Wei Li; Chi Zhang; Yushan Liu; Feng Xu; Jiepeng Chen; Lili Duan; Fengjiao Zhang (Glycoconjugate Journal, 2019)

Revisiting the ca. 845–820-Ma S-type granitic magmatism in the Jiangnan Orogen: new insights on the Neoproterozoic tectono-magmatic evolution of South China - Teng Deng; Deru Xu; Guoxiang Chi; Yuhua Zhu; Zhilin Wang; Genwen Chen; Zenghua Li; Junling Zhang; Tingwei Ye; Deshui Yu (International Geology Review, 2019)

Bituminous coal combustion and Xuan Wei Lung cancer: a review of the epidemiology, intervention, carcinogens, and carcinogenesis - Jinhui Li; Jinjun Ran; Lung-chi Chen; Max Costa; Yunchao Huang; Xiao Chen; Linwei Tian (Archives of Toxicology, 2019)

Benefit analysis of flood adaptation under climate change scenario - Hsin-Chi Li; Shih-Yun Kuo; Wei-Bo Chen; Lee-yaw Lin (Natural Hazards, 2019)

N-(3-oxo-acyl) homoserine lactone induced germ cell apoptosis and suppressed the over-activated RAS/MAPK tumorigenesis via mitochondrial-dependent ROS in C. elegans - Bin Chen; Xianbin Cao; Huayi Lu; Pengbo Wen; Xiaojing Qi; Shaopeng Chen; Lijun Wu; Chi Li; An Xu; Guoping Zhao (Apoptosis, 2018)

Dendrocoumarin: a new benzocoumarin derivative from the stem of Dendrobium nobile - Xue-Ming Zhou; Bin Zhang; Guang-Ying Chen; Chang-Ri Han; Kun-Chi Jiang; Ming-Yue Luo; Bo-Zheng Meng; Wen-Xin Li; Shi-Dai Lin (Natural Product Research, 2018)

Curcumin-loaded self-nanomicellizing solid dispersion system: part II: in vivo safety and efficacy assessment against behavior deficit in Alzheimer disease - Ankit Parikh; Krishna Kathawala; Jintao Li; Chi Chen; Zhengnan Shan; Xia Cao; Xin-Fu Zhou; Sanjay Garg (Drug Delivery and Translational Research, 2018)

Cloning and characterization of SucNHX1, a novel vacular Na+/H+ antiporter from the halophyte Suaeda corniculata that enhances the saline-alkali tolerance in Arabidopsis by its overexpression - Xiaowei Li; Fawei Wang; Daqian Sun; Nan Wang; Yuanyuan Dong; Weican Liu; Xiuming Liu; Na Yao; Huan Chen; Menghan Chi; Shuhan Ji; Shijin Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Dynamic response of a dip slope with multi-slip planes revealed by shaking table tests - Hung-Hui Li; Cheng-Han Lin; Wei Zu; Chi-Chieh Chen; Meng-Chia Weng (Landslides, 2018)

Comparison of stomach microRNA transcriptomes of Tibetan and Yorkshire pigs by deep sequencing - Wen-kui Sun; Yanyue Li; Chi Cheng; Yi-hui Chen; Kai Zeng; Xiaohui Chen; Yiren Gu; Rui Liu; Xuebin Lv; Rong Gao (Genes & Genomics, 2018)

Comparison of a Manual and an Automated Tracking Method for Tibetan Plateau Vortices - Julia Curio; Yongren Chen; Reinhard Schiemann; Andrew G. Turner; Kai Chi Wong; Kevin Hodges; Yueqing Li (Advances in Atmospheric Sciences, 2018)
Tibetan Plateau vortices (TPVs) are mesoscale cyclones originating over the Tibetan Plateau (TP) during the extended summer season (April–September). Most TPVs stay on the TP, but a small number can move off the TP to the east. TPVs are known to be one of the main precipitation-bearing systems on the TP and moving-off TPVs have been associated with heavy precipitation and flooding downstream of the TP (e.g., in Sichuan province or over the Yangtze River Valley). Identifying and tracking TPVs is difficult because of their comparatively small horizontal extent (400–800 km) and the limited availability of soundings over the TP, which in turn constitutes a challenge for short-term predictions of TPV-related impacts and for the climatological study of TPVs. In this study k](i) manual tracking (MT) results using radiosonde data from a network over and downstream of the TP are compared with (ii) results obtained by an automated tracking (AT) algorithm applied to ERA-Interim data. Ten MT-TPV cases are selected based on method (i) and matched to and compared with the corresponding AT-TPVs identified with method (ii). Conversely k]ten AT-TPVs are selected and compared with the corresponding MT-TPVs. In general k]the comparison shows good results in cases where the underlying data are in good agreement k]but considerable differences are also seen in some cases and explained in terms of differences in the tracking methods k]data availability/coverage and disagreement between sounding and ERA-Interim data. Recommendations are given for future efforts in TPV detection and tracking k]including in an operational weather forecasting context.

Molecular surveillance of Vittaforma-like microsporidia by a small-volume procedure in drinking water source in Taiwan: evidence for diverse and emergent pathogens - Jung-Sheng Chen; Bing-Mu Hsu; Hsin-Chi Tsai; Yu-Pin Chen; Tung-Yi Huang; Kuan-Ying Li; Dar-Der Ji; Herng-Sheng Lee (Environmental Science and Pollution Research, 2018)

Establishment of two basal-like breast cancer cell lines with extremely low tumorigenicity from Taiwanese premenopausal women - Wen-Ling Kuo; Shir-Hwa Ueng; Chun-Hsing Wu; Li-Yu Lee; Yun-Shien Lee; Ming-Chin Yu; Shin-Cheh Chen; Chi-Chang Yu; Chi-Neu Tsai (Human Cell, 2018)

Permineralized Calamitean Axes from the Upper Permian of Xinjiang, Northwest China and Its Paleoecological Implication - Fayao Chen; Xiao Shi; Jianxin Yu; Hongfei Chi; Jun Zhu; Hui Li; Cheng Huang (Journal of Earth Science, 2018)

Role of the meridional dipole of SSTA and associated cross-equatorial flow in the tropical eastern Pacific in terminating the 2014 El Niño development - Yi-Kai Wu; Lin Chen; Chi-Cherng Hong; Tim Li; Cheng-Ta Chen; Lu Wang (Climate Dynamics, 2018)

Development of a generic method for inspection of tospoviruses - Kuo-Shiou Huang; Siang-Ling Li; Jing-Hua Sun; Yun-Chi Wang; Fuh-Jyh Jan; Tsung-Chi Chen (European Journal of Plant Pathology, 2018)

Enhanced activity and stability of La-doped CeO2 monolithic catalysts for lean-oxygen methane combustion - Wenjun Zhu; Jianhui Jin; Xiao Chen; Chuang Li; Tonghua Wang; Chi-Wing Tsang; Changhai Liang (Environmental Science and Pollution Research, 2018)

Effect of soil pH and organic matter on the adsorption and desorption of pentachlorophenol - Shui-Wen Chang Chien; Shou-Hung Chen; Chi-Jui Li (Environmental Science and Pollution Research, 2018)

Zoledronate dysregulates fatty acid metabolism in renal tubular epithelial cells to induce nephrotoxicity - Lili Cheng; Mengmeng Ge; Zhou Lan; Zhilong Ma; Wenna Chi; Wenhua Kuang; Kun Sun; Xinbin Zhao; Ye Liu; Yaqian Feng; Yuedong Huang; Maoguo Luo; et al. (Archives of Toxicology, 2018)

Association of lead exposure with cardiovascular risk factors and diseases in Chinese adults - Chi Chen; Qin Li; Xiaomin Nie; Bing Han; Yi Chen; Fangzhen Xia; Hualing Zhai; Ningjian Wang; Yingli Lu (Environmental Science and Pollution Research, 2017)

Characterization of a new isolate of pepper chlorotic spot virus from Yunnan province, China - Kuanyu Zheng; Tsung-Chi Chen; Shyi-Dong Yeh; Md. Siddiqur Rahman; Xiaoxia Su; Kuo Wu; Ting Li; Zhongkai Zhang; Jiahong Dong (Archives of Virology, 2017)

Dosage effects of ZP2 and ZP3 heterozygous mutations cause human infertility - Wenqiang Liu; Kunming Li; Dandan Bai; Jiqing Yin; Yuanyuan Tang; Fengli Chi; Linfeng Zhang; Yu Wang; Jiaping Pan; Shanshan Liang; Yi Guo; Jingling Ruan; et al. (Human Genetics, 2017)

Suppressive effect of microRNA319 expression on rice plant height - Wei-Ting Liu; Peng-Wen Chen; Li-Chi Chen; Chia-Chun Yang; Shu-Yun Chen; GuanFu Huang; Tzu Che Lin; Hsin-Mei Ku; Jeremy J. W. Chen (Theoretical and Applied Genetics, 2017)

The function of OsbHLH068 is partially redundant with its homolog, AtbHLH112, in the regulation of the salt stress response but has opposite functions to control flowering in Arabidopsis - Hung-Chi Chen; Vicki Hsieh-Feng; Pei-Chun Liao; Wan-Hsing Cheng; Li-Yu Liu; Yun-Wei Yang; Ming-Hsin Lai; Men-Chi Chang (Plant Molecular Biology, 2017)

Correlation between three-dimensional power Doppler and morphometric measurement of endometrial vascularity at the time of embryo implantation in women with unexplained recurrent miscarriage - Xiaoyan Chen; Sotirios H. Saravelos; Yingyu Liu; Jin Huang; Chi Chiu Wang; Tin Chiu Li (Journal of Molecular Histology, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Pharmacological Inhibition of PERK Attenuates Early Brain Injury After Subarachnoid Hemorrhage in Rats Through the Activation of Akt - Feng Yan; Shenglong Cao; Jianru Li; Brandon Dixon; Xiaobo Yu; Jingyin Chen; Chi Gu; Wang Lin; Gao Chen (Molecular Neurobiology, 2017)

Prebiotic effects of bovine lactoferrin on specific probiotic bacteria - Po-Wen Chen; Zhen-Shu Liu; Tai-Chen Kuo; Min-Chi Hsieh; Zhe-Wei Li (BioMetals, 2017)

Association of oral endothelin receptor antagonists with risks of cardiovascular events and mortality: meta-analysis of randomized controlled trials - Yu Pan; Chun Hu; Pei Hua Chen; Yan Hong Gu; Qing Yan Qiao; Li Hua Pan; Dong Chi Zhou; Hui Fang Gu; Shun Kun Fu; Hui Min Jin (European Journal of Clinical Pharmacology, 2017)

Removal of Congo red from aqueous solution by adsorption onto different amine compounds modified sugarcane bagasse - Jun-xia Yu; Wan-li Xiong; Jing Zhu; Jia-dong Chen; Ru-an Chi (Clean Technologies and Environmental Policy, 2017)

Goatpoxvirus ATPase activity is increased by dsDNA and decreased by zinc ion - Ming-Liang Lee; Wei-Li Hsu; Chi-Young Wang; Hui-Yu Chen; Fong-Yuan Lin; Ming-Huang Chang; Hong-You Chang; Min-Liang Wong; Kun-Wei Chan (Virus Genes, 2016)

Pioglitazone inhibits advanced glycation end product-induced matrix metalloproteinases and apoptosis by suppressing the activation of MAPK and NF-κB - Hai-Bin Zhang; Ying Zhang; Cheng Chen; Yu-Qing Li; Chi Ma; Zhao-Jun Wang (Apoptosis, 2016)

Brittle Rock Modeling Approach and its Validation Using Excavation-Induced Micro-Seismicity - Chun-Chi Ma; Tian-Bin Li; Hui-Lin Xing; Hang Zhang; Min-Jie Wang; Tian-Yi Liu; Guo-Qing Chen; Zi-Quan Chen (Rock Mechanics and Rock Engineering, 2016)

G protein-coupled estrogen receptor inhibits the P2Y receptor-mediated Ca2+ signaling pathway in human airway epithelia - Yuan Hao; Alison W. Chow; Wallace C. Yip; Chi H. Li; Tai F. Wan; Benjamin C. Tong; King H. Cheung; Wood Y. Chan; Yangchao Chen; Christopher H. Cheng; Wing H. Ko (Pflügers Archiv - European Journal of Physiology, 2016)

Steroid Probes Conjugated with Protein-Protected Gold Nanocluster: Specific and Rapid Fluorescence Imaging of Steroid Receptors in Target Cells - Chi-Yan Tsai; Chun-Wei Li; Jie-Ren Li; Bo-Han Jang; Shu-Hui Chen (Journal of Fluorescence, 2016)

Composition, distribution and habitat effects of vascular plants on the vertical surfaces of an ancient city wall - Yanning Qiu; Bin J. W. Chen; Yanjuan Song; Zheng Y. X. Huang; Li Wan; Cheng Huang; Maosong Liu; Chi Xu (Urban Ecosystems, 2016)

Heat shock protein 70 inhibits cardiomyocyte necroptosis through repressing autophagy in myocardial ischemia/reperfusion injury - Xiaojuan Liu; Chao Zhang; Chi Zhang; Jingjing Li; Wanwan Guo; Daliang Yan; Chen Yang; Jianhua Zhao; Tian Xia; Yuqing Wang; Rong Xu; Xiang Wu; et al. (In Vitro Cellular & Developmental Biology - Animal, 2016)

Minocycline Protects Against NLRP3 Inflammasome-Induced Inflammation and P53-Associated Apoptosis in Early Brain Injury After Subarachnoid Hemorrhage - Jianru Li; Jingsen Chen; Hangbo Mo; Jingyin Chen; Cong Qian; Feng Yan; Chi Gu; Qiang Hu; Lin Wang; Gao Chen (Molecular Neurobiology, 2016)

Blood Cadmium Level Associates with Lower Testosterone and Sex Hormone-Binding Globulin in Chinese men: from SPECT-China Study, 2014 - Chi Chen; Ningjian Wang; Xiaomin Nie; Bing Han; Qin Li; Yi Chen; Hualing Zhai; Chunfang Zhu; Yingchao Chen; Fangzhen Xia; Meng Lu; Dongping Lin; et al. (Biological Trace Element Research, 2016)

The tectonic setting of early Permian bimodal volcanism in central Inner Mongolia: continental rift, post-collisional extension, or active continental margin? - Jianfeng Liu; Jinyi Li; Xiaoguo Chi; Junfeng Qu; Junqiang Chen; Zhaochu Hu; Qianwen Feng (International Geology Review, 2016)

Genome-Scale Identification of Cell-Wall-Related Genes in Switchgrass through Comparative Genomics and Computational Analyses of Transcriptomic Data - Xin Chen; Qin Ma; Xiaolan Rao; Yuhong Tang; Yan Wang; Gaoyang Li; Chi Zhang; Xizeng Mao; Richard A. Dixon; Ying Xu (BioEnergy Research, 2016)

Anthropogenic activities drive the microbial community and its function in urban river sediment - Xu Zhang; Qing Gu; Xi-En Long; Zhao-Lei Li; Dong-Xiu Liu; Dan-Hua Ye; Chi-Quan He; Xiao-Yan Liu; Kristiina Väänänen; Xue-Ping Chen (Journal of Soils and Sediments, 2016)

Stress tolerance and biocontrol performance of the yeast antagonist, Candida diversa, change with morphology transition - Guangkun Li; Mengshan Chi; Huizhen Chen; Yuan Sui; Yan Li; Yongsheng Liu; Xiaojing Zhang; Zhiqiang Sun; Guoqing Liu; Qi Wang; Jia Liu (Environmental Science and Pollution Research, 2016)

Conditional Probabilities for Large Events Estimated by Small Earthquake Rate - Yi-Hsuan Wu; Chien-Chih Chen; Hsien-Chi Li (Pure and Applied Geophysics, 2016)

Short-Term Effects and Safety Analysis of Retrograde Autologous Blood Priming for Cardiopulmonary Bypass in Patients with Cardiac Valve Replacement Surgery - Ming Cheng; Jun-Quan Li; Tian-Chi Wu; Wei-Chen Tian (Cell Biochemistry and Biophysics, 2015)

CO Induces Nrf2-Dependent Heme Oxygenase-1 Transcription by Cooperating with Sp1 and c-Jun in Rat Brain Astrocytes - Pei-Ling Chi; Chih-Chung Lin; Yu-Wen Chen; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2015)

TM-1-1DP exerts protective effect against myocardial ischemia reperfusion injury via AKT-eNOS pathway - Hui-Chun Ku; Shih-Yi Lee; Chi-Hsuan Chen; Yao-Hsing Wang; Chin-Ting Lin; Shoei-Sheng Lee; Ting-Hsuan Li; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Carbon stock and its responses to climate change in C entral A sia - Chaofan Li; Chi Zhang; Geping Luo; Xi Chen; Bagila Maisupova; Abdullo A. Madaminov; Qifei Han; Bekmamat M. Djenbaev (Global Change Biology, 2015)
Central Asia has a land area of 5.6 × 10 6 km 2 and contains 80–90% of the world's temperate deserts. Yet it is one of the least characterized areas in the estimation of the global carbon (C) stock/balance. This study assessed the sizes and spatiotemporal patterns of C pools in Central Asia using both inventory (based on 353 biomass and 284 soil samples) and process‐based modeling approaches. The results showed that the C stock in Central Asia was 31.34–34.16 Pg in the top 1‐m soil with another 10.42–11.43 Pg stored in deep soil (1–3 m) of the temperate deserts. They amounted to 18–24% of the global C stock in deserts and dry shrublands. The C stock was comparable to that of the neighboring regions in Eurasia or major drylands around the world (e.g. Australia). However, 90% of Central Asia C pool was stored in soil, and the fraction was much higher than in other regions. Compared to hot deserts of the world, the temperate deserts in Central Asia had relatively high soil organic carbon density. The C stock in Central Asia is under threat from dramatic climate change. During a decadal drought between 1998 and 2008, which was possibly related to protracted La Niña episodes, the dryland lost approximately 0.46 Pg C from 1979 to 2011. The largest C losses were found in northern Kazakhstan, where annual precipitation declined at a rate of 90 mm decade −1 . The regional C dynamics were mainly determined by changes in the vegetation C pool, and the SOC pool was stable due to the balance between reduced plant‐derived C influx and inhibited respiration.

Characterization of regulatory regions involved in the inducible expression of chiB in Bacillus thuringiensis - Chi-Chu Xie; Jin Shi; Hai-Yun Jia; Peng-Fei Li; Yang Luo; Jun Cai; Yue-Hua Chen (Archives of Microbiology, 2015)

A prepared anti-MSTN polyclonal antibody reverses insulin resistance of diet-induced obese rats via regulation of PI3K/Akt/mTOR&FoxO1 signal pathways - Liang Tang; Chen-tao Liu; Xu-dan Wang; Kai Luo; Di-di Zhang; Ai-ping Chi; Jing Zhang; Li-jun Sun (Biotechnology Letters, 2014)

Some selected heavy metal concentrations in water, sediment, and oysters in the Er-Ren estuary, Taiwan: chemical fractions and the implications for biomonitoring - Yueh-Min Chen; Hong-Chun Li; Tsung-Ming Tsao; Liaug-Chi Wang; Yin Chang (Environmental Monitoring and Assessment, 2014)

Mapping near-surface air temperature, pressure, relative humidity and wind speed over Mainland China with high spatiotemporal resolution - Tao Li; Xiaogu Zheng; Yongjiu Dai; Chi Yang; Zhuoqi Chen; Shupeng Zhang; Guocan Wu; Zhonglei Wang; Chengcheng Huang; Yan Shen; Rongwei Liao (Advances in Atmospheric Sciences, 2014)

Yeast Oropharyngeal Colonization in Human Immunodeficiency Virus-Infected Patients in Central Taiwan - Mao-Wang Ho; Yun-Liang Yang; Chih-Chao Lin; Chih-Yu Chi; Hui-Ting Chen; Po-Chang Lin; Li-Yun Hsieh; Chia-Hui Chou; Wen-Li Chu; Chiou-Pyng Wu; Tsai-Ling Lauderdale; Hsiu-Jung Lo (Mycopathologia, 2014)

The Role of Pentacyclic Triterpenoids in the Allelopathic Effects of Alstonia scholaris - Chao-Min Wang; Hsiao-Ting Chen; Tsai-Chi Li; Jen-Hsien Weng; Yun-Lian Jhan; Shi-Xun Lin; Chang-Hung Chou (Journal of Chemical Ecology, 2014)

Developmental and LED Light Source Modulation of Carotenogenic Gene Expression in Oncidium Gower Ramsey Flowers - Wen-Li Lee; Jian-Zhi Huang; Li-Chi Chen; Chi-Chu Tsai; Fure-Chyi Chen (Plant Molecular Biology Reporter, 2013)

Brain Delivery of NAP with PEG-PLGA Nanoparticles Modified with Phage Display Peptides - Jingwei Li; Chi Zhang; Jing Li; Li Fan; Xinguo Jiang; Jun Chen; Zhiqing Pang; Qizhi Zhang (Pharmaceutical Research, 2013)

Proteomic and physiological analyses reveal detoxification and antioxidation induced by Cd stress in Kandelia candel roots - Zhao-Xia Weng; Ling-Xia Wang; Fang-lin Tan; Li Huang; Jian-Hong Xing; Shi-Pin Chen; Chi-Lien Cheng; Wei Chen (Trees, 2013)

The biochemical and immunological characterization of two serpins from Clonorchis sinensis - Huali Lei; Yanli Tian; Wenjun Chen; Xiaoyun Wang; Xuerong Li; Qiang Mao; Jiufeng Sun; Ran Li; Yanquan Xu; Chi Liang; Yan Huang; Xinbing Yu (Molecular Biology Reports, 2013)

Molecular characterization of the full-length L and M RNAs of Tomato yellow ring virus, a member of the genus Tospovirus - Tsung-Chi Chen; Ju-Ting Li; Ya-Shu Fan; Yi-Chun Yeh; Shyi-Dong Yeh; Richard Kormelink (Virus Genes, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Increased precipitation during the Little Ice Age in northern Taiwan inferred from diatoms and geochemistry in a sediment core from a subalpine lake - Liang-Chi Wang; Hermann Behling; Teh-Quei Lee; Hong-Chun Li; Chih-An Huh; Liang-Jian Shiau; Su-Hwa Chen; Jiunn-Tzong Wu (Journal of Paleolimnology, 2013)

Combretastatin A-4 derivatives: synthesis and evaluation of 2,4,5-triaryl-1H-imidazoles as potential agents against H1299 (non-small cell lung cancer cell) - Chih-Hua Tseng; Chi-Yi Li; Chien-Chih Chiu; Huei-Ting Hu; Chein-Hwa Han; Yeh-Long Chen; Cherng-Chyi Tzeng (Molecular Diversity, 2012)

Molecular identification and characterization of leucine aminopeptidase 2, an excretory-secretory product of Clonorchis sinensis - Chuanhuan Deng; Jiufeng Sun; Xuerong Li; Lexun Wang; Xuchu Hu; Xiaoyun Wang; Wenjun Chen; Xiaoli Lv; Chi Liang; Wenfang Li; Yan Huang; Ran Li; et al. (Molecular Biology Reports, 2012)

Secretome characteristics of pelletized Trichoderma reesei and cellulase production - Yapeng Chao; Deepak Singh; Liang Yu; Zhiming Li; Zhanyou Chi; Shulin Chen (World Journal of Microbiology and Biotechnology, 2012)

Cloning and expression analysis of an anti-lipopolysaccharide factor from giant freshwater prawn, Macrobrachium rosenbergii - Qian Ren; Zhi-Qiang Du; Meng Li; Chi-Yu Zhang; Ke-Ping Chen (Molecular Biology Reports, 2012)

Hyperglycemia as a Predictor of Poor Outcome at Discharge in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shao-Chi Lu; Liang-Cheng Chen; Heng-Yi Chu; Shang-Lin Chiang; Shin-Tsu Chang (The Cerebellum, 2012)

Heterologous interactions between NS1 proteins from different influenza A virus subtypes/strains - WeiZhong Li; Heng Zhang; GeFei Wang; Chi Zhang; XiangXing Zeng; Hui Liu; XiaoXuan Chen; YanXuan Xu; KangSheng Li (Science China Life Sciences, 2012)

Concentrations of polycyclic aromatic hydrocarbon in the surface sediments from inter-tidal areas of Kenting coast, Taiwan - Jing-O Cheng; Fung-Chi Ko; Jan-Jung Li; Te-Hao Chen; Ying-Ming Cheng; Chon-Lin Lee (Environmental Monitoring and Assessment, 2012)

Ergodicity examined by the Thirumalai-Mountain metric for Taiwanese seismicity - Hsien-Chi Li; Chien-Chih Chen (Acta Geophysica, 2012)

Baseline human papillomavirus infection, high vaginal parity, and their interaction on cervical cancer risks after a follow-up of more than 10 years - Shu-Fen Liao; Wen-Chung Lee; Hui-Chi Chen; Li-Chung Chuang; Mei-Hung Pan; Chien-Jen Chen (Cancer Causes & Control, 2012)

A drug-laden elastomer for surgical treatment of anal fistula - Hairui Li; Bin Jiang; Jun Yan; Zhonghua Yang; Yanni Chen; Weiping Zhang; Alex C. Choy; Chi-Ying M. Lee; Lifeng Kang (Drug Delivery and Translational Research, 2011)

Effect of diindolylmethane on Ca2+ movement and viability in HA59T human hepatoma cells - Jin-Shiung Cheng; Su-Shung Shu; Chun-Chi Kuo; Chiang-Ting Chou; Wei-Lun Tsai; Yi-Chien Fang; Li-Ni Kuo; Jeng-Hsien Yeh; Wei-Chuan Chen; Jau-Min Chien; Ti Lu; Chih-Chuan Pan; et al. (Archives of Toxicology, 2011)

A disease associated with phytoplasma in Parthenium hysterophorus - Zhengnan Li; Lei Zhang; Haiyan Che; Hongguang Liu; Ming Chi; Daquan Luo; Yan Li; Wang Chen; Yunfeng Wu (Phytoparasitica, 2011)

Relationship between temperature change and the requirement for a permanent pacemaker implantation in bradyarrhythmias - I-Fan Liu; Shih-Lin Chang; Li-Wei Lo; Yu-Feng Hu; Ta-Chuan Tuan; Chi-Woon Kong; Tsu-Juey Wu; Chern-En Chiang; Shih-Ann Chen; Yenn-Jiang Lin (International Journal of Biometeorology, 2011)

Anti-inflammatory effects of ivermectin in mouse model of allergic asthma - Shuhan Yan; Xinxin Ci; Na Chen; Chi Chen; Xiangchao Li; Xiao Chu; Jianhua Li; Xuming Deng (Inflammation Research, 2011)

Emerging threat of thrips-borne Melon yellow spot virus on melon and watermelon in Taiwan - Jui-Chu Peng; Shyi-Dong Yeh; Li-Hsin Huang; Ju-Ting Li; Yuan-Fu Cheng; Tsung-Chi Chen (European Journal of Plant Pathology, 2011)

Complete genomic sequence of watermelon bud necrosis virus - Ju-Ting Li; Yi-Chun Yeh; Shyi-Dong Yeh; Joseph A. J. Raja; Prem A. Rajagopalan; Lu-Yuan Liu; Tsung-Chi Chen (Archives of Virology, 2011)

Antigenically dominant proteins within the human liver mitochondrial proteome identified by monoclonal antibodies - YanFang Ju; JinJu Yang; Rong Liu; XiaoLan Liu; XueMei Du; Li Liu; ZhiCheng Chen; Jun Chi; ShuEr Liu; Yuan Gao; JianEn Gao; ShunChang Jiao; et al. (Science China Life Sciences, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Cavitation Phenomena in Mechanical Heart Valves: Studied by Using a Physical Impinging Rod System - Chi-Wen Lo; Sheng-Fu Chen; Chi-Pei Li; Po-Chien Lu (Annals of Biomedical Engineering, 2010)

Association Analysis Between 12 Genetic Variants of Ten Genes and Personality Traits in a Young Chinese Han Population - Pingyuan Gong; Anyun Zheng; Kejin Zhang; Xu Lei; Fengchao Li; Dongmei Chen; Wanyu Chi; Xueli Tong; Zijian Zheng; Xiaocai Gao; Fuchang Zhang (Journal of Molecular Neuroscience, 2010)

Serological relationship between Melon yellow spot virus and Watermelon silver mottle virus and differential detection of the two viruses in cucurbits - Tsung-Chi Chen; Yun-Yueh Lu; Ying-Huey Cheng; Ju-Ting Li; Yi-Chun Yeh; Ya-Chi Kang; Chia-Peng Chang; Li-Hsin Huang; Jui-Chu Peng; Shyi-Dong Yeh (Archives of Virology, 2010)

Characterization and expression of bone morphogenetic protein 4 gene in postnatal pigs - Ming Li; Qixin Chen; Guirong Sun; Xiaowei Shi; Qiaohui Zhao; Chi Zhang; Jianshe Zhou; Nan Qin (Molecular Biology Reports, 2010)

Gene expression profiles in the prefrontal cortex of SHR rats by cDNA microarrays - Jie Qiu; Qin Hong; Rong-hua Chen; Mei-ling Tong; Min Zhang; Li Fei; Xiao-qin Pan; Mei Guo; Xi-rong Guo; Xia Chi (Molecular Biology Reports, 2010)

Polymorphisms in arsenic metabolism genes, urinary arsenic methylation profile and cancer - Chi-Jung Chung; Yu-Mei Hsueh; Chyi-Huey Bai; Yung-Kai Huang; Ya-Li Huang; Mo-Hsiung Yang; Chien-Jen Chen (Cancer Causes & Control, 2009)

Chemical constituents from the leaves of Machilus zuihoensis Hayata var. mushaensis (Lu) Y.C. Liu - Chung-Yi Chen; Ming-Jen Cheng; Yi-Jung Chiang; Jia-Chi Bai; Chih-Tsao Chiu; Rong-Jyh Lin; Yen-Ray Hsui; Wen-Li Lo (Natural Product Research, 2009)

Expression and membrane integration of SARS-CoV E protein and its interaction with M protein - Shih-Chi Chen; Shih-Yen Lo; Hsin-Chieh Ma; Hui-Chun Li (Virus Genes, 2009)

A population-based, case–control study of green tea consumption and leukemia risk in southwestern Taiwan - Yau-Chang Kuo; Chu-Ling Yu; Chen-Yu Liu; Su-Fen Wang; Pi-Chen Pan; Ming-Tsang Wu; Chi-Kung Ho; Yu-Shing Lo; Yi Li; David C. Christiani (Cancer Causes & Control, 2009)

Neuronal dysfunction of a long projecting multisynaptic pathway in response to methamphetamine using manganese-enhanced MRI - Yi-Hua Hsu; Chiao-Chi V. Chen; Anil Zechariah; Cecil C. Yen; Li-Chuan Yang; Chen Chang (Psychopharmacology, 2008)

Comparative Physicochemical Characterization of Phospholipids Complex of Puerarin Formulated by Conventional and Supercritical Methods - Ying Li; Da-Jian Yang; Shi-Lin Chen; Si-Bao Chen; Albert Sun-Chi Chan (Pharmaceutical Research, 2008)

Responses of Helicoverpa armigera to Tomato Plants Previously Infected by ToMV or Damaged by H. armigera - Li Lin; Tse-Chi Shen; Yi-Hua Chen; Shaw-Yhi Hwang (Journal of Chemical Ecology, 2008)

Isolation and characterization of the zebrafish Danio rerio insulin-like growth factor binding protein-3 promoter region - Ming Jun CHOU; Jian Chyi CHEN; Jyh Yih CHEN; Hong Yi GONG; Li Tzu LI; Tzou Chi HUANG; Jen Leih WU; Ching Ming KUO (Fisheries Science, 2008)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Opposing Action of Estrogen Receptors α and β on Tumor Necrosis Factor-α Gene Expression and Caspase-8-mediated Apoptotic Effects in HA22T Cells - Erh-Jung Huang; Cheng-Chung Wu; Shin-Da Lee; Juen-Hau Chen; Jer-Yuh Liu; Jiunn-Liang Ko; James A. Lin; Min-Chi Lu; Li-Mien Chen; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2006)

Cardiomyoblast apoptosis induced by insulin-like growth factor (IGF)-I resistance is IGF-II dependent and synergistically enhanced by angiotensin II - Wei-Wen Kuo; Chung-Jung Liu; Li-Ming Chen; Chieh-Hsi Wu; Chun-Hsien Chu; Jer-Yuh Liu; Min-Chi Lu; James A. Lin; Shin-Da Lee; Chih-Yang Huang (Apoptosis, 2006)

Dynamic analysis of hepatoma spheroid formation: roles of E-cadherin and β1-integrin - Ruei-Zeng Lin; Li-Fang Chou; Chi-Chen Michael Chien; Hwan-You Chang (Cell and Tissue Research, 2006)

St. John’s Wort Modulates the Toxicities and Pharmacokinetics of CPT-11 (Irinotecan) in Rats - Zeping Hu; Xiaoxia Yang; Paul Chi-Liu Ho; Eli Chan; Sui Yung Chan; Congjian Xu; Xiaotian Li; Yi-Zhun Zhu; Wei Duan; Xiao Chen; Min Huang; Hongyuan Yang; et al. (Pharmaceutical Research, 2005)

The signature motif in human glucose-6-phosphate transporter is essential for microsomal transport of glucose-6-phosphate - Chi-Jiunn Pan; Li-Yuan Chen; Brian C. Mansfield; Barbara Salani; Luigi Varesio; Janice Yang Chou (Human Genetics, 2003)